Adaptive Variation Amid High Gene Flow Across a Broad Latitudinal Gradient in the Reef‐Building Honeycomb Worm, Sabellaria alveolata - Edward J. Wilson; Antony M. Knights; Louise B. Firth; Charlotte Corporeau; Amelia Curd; Stanislas F. Dubois; Fernando P. Lima; Rui Seabra; Flavia L. D. Nunes (Molecular Ecology, 2026)
Climate change is already altering, and will continue to reshape, the persistence and spatial structure of marine populations. Understanding metapopulation connectivity and local adaptation is therefore critical for identifying both vulnerable populations and those with adaptive resilience. We applied a seascape genomics approach to investigate connectivity patterns and adaptive responses in the honeycomb worm, Sabellaria alveolata —an intertidal ecosystem engineer that supports high biodiversity and provides essential ecological functions. A total of 286 individuals from 17 sites spanning the entire latitudinal range were genotyped to assess population structure and local adaptation. Outlier analyses (BayeScan and OutFlank) identified six adaptive and 2117 neutral SNPs. Neutral SNP analysis revealed low to moderate genetic differentiation, indicating well‐connected populations. Admixture with possible ancestral gene pools in Southern Edge and Biscay populations suggests the persistence of unique genetic diversity. While connectivity is likely driven by natural larval dispersal, human‐mediated transport resulting from support vessels, aquaculture, marine debris and expanding offshore and coastal infrastructure may also facilitate gene flow, shaping observed genetic patterns. Despite this high connectivity, we detected genetic signatures of adaptation to temperature, salinity and net primary productivity, with adaptive SNPs linked to genes involved in molecular and physiological responses to these environmental factors. Our findings suggest that S. alveolata is likely resilient to climate change and other anthropogenic pressures, making it a valuable model for investigating the genetic and physiological underpinnings of marine population resilience.

Associations Between Complementary Feeding Approach, Dietary Intake, and Growth: A Secondary Analysis of the Maternal and Infant Nutrition Trial - Kinzie L. Matzeller; Mikayla L. Hernandez; Gabrielle N.E. Glime; Claudia A. Schaefer; Edward L. Melanson; Daniel N. Frank; Audrey E. Hendricks; Nancy F. Krebs; Minghua Tang (Journal of the Academy of Nutrition and Dietetics, 2026)

Multiphysics modeling of high-surface area carbon supports for polymer electrolyte fuel cells - Alper Can Ince; Mustafa Fazil Serincan; Siddharth Komini Babu; Jacob S. Spendelow; Edward F. Holby; Ugur Pasaogullari; Wilton J.M. Kort-Kamp (Chemical Engineering Journal, 2026)

Animal responses and physiological indicators of stress in late pregnant alpacas on cultivated pastures in the High Peruvian Andes - Diannett Benito López; Laura B. Gualdrón-Duarte; Rassiel Macedo Sucari; Guadalupe Orellana Ligas; Yemi Sanca Uscamayta; Feliciano Rivera Pachiño; Nancy F. Huanca-Marca; Francisco E. Franco; Rubén García-Ticllacuri; Joel Pacheco Curie; Bernardo Roque Huanca; Víctor M. Vélez-Marroquín; et al. (Tropical Animal Health and Production, 2026)

Groundwater–surface water interactions and resilience to hydrological extremes in a data-sparse arid transboundary river basin: Insights from collaborative groundwater modelling - Syed Md Touhidul Mustafa; Jean-Christophe Comte; Fulvio Franchi; Alessia Matano; Anne F. Van Loon; Sithabile Tirivarombo; Luis Artur; Zareen Bharucha; Annatoria Chinyama; Farisse Chirindja; Rosie Day; Joyce Dube; et al. (Hydrogeology Journal, 2026)
Sustainable groundwater management is key to building resilience to hydrological extremes but remains challenging in data-scarce transboundary river basins. In this study, a transboundary, collaborative, physically based groundwater modelling approach has been developed for the Limpopo River Basin (LRB), which is highly vulnerable to floods and droughts. Monitoring data and model results consistently suggest that prolonged wet periods and floods significantly raised groundwater levels, whereas prolonged droughts decreased them, particularly in the upstream and central regions of the basin characterized by low-storage fractured bedrock aquifers. Groundwater–surface water interactions are greater downstream, where water tables are shallower in unconsolidated superficial materials, and intensify during floods, especially in the central region. Modelling results also suggest that baseflow is less responsive to extremes than groundwater recharge across the LRB, highlighting the groundwater system’s attenuation capacity. The model was subsequently used to assess and discuss a series of co-created management scenarios focused specifically on improving groundwater storage during wet periods for use during dry periods. They included: (1) managed aquifer recharge (MAR), using (1a) injection well(s) next to large dams, (1b) rainwater and runoff harvesting (RRH) and infiltration through local wells, (1c) RRH through local ponds and (1d) small reservoirs (e.g. sand dams); (2) deforestation; (3) afforestation; and (4) increased groundwater abstraction. Scenarios suggest that strategy (1b), when widely applied across the basin, may be the most effective to reduce the risk and impact of floods, droughts, and groundwater depletion by supporting the maintenance of groundwater levels and baseflow, while reducing storm runoff.

Flowering of Strawberry (Fragaria X ananassa Duch.) Under Supplemental LED Lighting During the Nyctoperiod, with Nitrogen and Chilling - Edward F. Durner (Applied Fruit Science, 2026)
Newer light-emitting diode (LED) lighting technology increases the feasibility of inexpensively regulating strawberry ( Fragaria x ananassa Duch.) plant development during propagation to enhance fruit production. Nitrogen fertilization and short-term cold storage also influence flowering and fruit production. Two experiments were designed to develop specific treatment combinations to enhance off-season productivity of both long-day (LD) and short-day (SD) cultivars. In one experiment, plugs of ‘Albion’ were conditioned with far-red + red light as a night interruption, ± elevated nitrogen, ± short-term cold storage (chilling) followed by greenhouse forcing. Elevated nitrogen or a night interruption enhanced inflorescence production and, combined with short-term chilling, enhanced precocity. In a second experiment, plugs of ‘Chandler’, ‘Ruby June’, ‘Ashley Jay’, ‘Sensation’, ‘Miss Jo’ and the Lassen Canyon Nursery selection ‘122 × 08’ were exposed to far-red and red light during the nyctoperiod, followed by short-term cold storage, flower mapping and greenhouse forcing. Initiation in ‘Chandler’ was inhibited by far-red + red as a night interruption. In ‘Miss Jo’, red at the end of the nyctoperiod enhanced initiation, and in ‘122 × 08’, far-red at the end of the nyctoperiod enhanced initiation. Similar effects on differentiation were observed. In ‘122 × 08’, red at the end of the nyctoperiod enhanced inflorescence production (development), and in ‘Ashley Jay’, chilling enhanced development, albeit by a very small amount. In ‘Ruby June’, chilling enhanced development, but only for the far-red + red night interruption treatment. Short-term chilling of ‘Albion’ plugs prior to planting is not recommended for conditioned plants since chilling may delay flowering by 2.5 weeks. Conditioning of SD cultivars is minimally effective and thus not recommended.

Computational Modelling of Selective Capture Mechanisms in Conduction System Pacing - Mohammadreza Kariman; Matthias A. F. Gsell; Edward J. Vigmond; Aurel Neic; Christoph M. Augustin; Gernot Plank (Annals of Biomedical Engineering, 2026)
Purpose Conduction system pacing (CSP) is gaining clinical significance owing to its ability to restore a physiological activation sequence in the ventricles. Whilst His bundle pacing producing the most physiological activation is preferable, due to implant complications the selective activation of the left bundle branch (LBB) by LBB area pacing is considered an alternative, offering both a simpler implant and a physiological activation sequence. However, the physical mechanisms facilitating selective activation of the LBB remain poorly understood. Methods We developed a structurally and biophysically detailed computer model of the interventricular septum and LBB to quantitatively elucidate the role of lead position, orientation and polarity in achieving optimal selective left bundle branch pacing (LBBP) thresholds, using a geometrically detailed model of a clinically widely used CSP lead. Results A deep implant within the left ventricular subendocardium ensuring a direct contact between electrode and LBB is key for effective selective LBBP. For low strength, selective LBBP is feasible, but capturing the LBB in its entirety could only be achieved using higher strengths that led to non-selective LBBP. Switching the tip polarity to anodal was not beneficial, requiring higher strengths to activate the LBB. Lead orientation relative to the LBB bundles was found to influence the selective LBBP capture threshold and the number of synchronously activating bundles. Conclusion The model explains the impedance trends that are clinically observed when advancing the tip through the interventricular septum into the LBB region, as well as sudden impedance drops associated with implant complications such as septal perforation or lead dislodgement. Quantitative consistency with clinically observed trends supports model credibility, and indicates that simulation may offer an effective approach for guiding the design of improved CSP leads, facilitating a selective and synchronous activation of the entire LBB.

Ensuring adaptability and applicability of long-term contaminant monitoring initiatives: A discussion of NOAA’s National Mussel Watch Program current practices and future approaches - N. A. Castillo; L. M. Swam-Jaramillo; M. M. Rider; A. Morozova; K. L. Kimbrough; E. D. Davenport; M. A. Edwards; F. Arzayus; D. A. Apeti (Environmental Monitoring and Assessment, 2026)

An integrated approach identifying seasonal variation in allergenic grass pollen in southern Australia - Josh Boyte; Sarah M. Sherson; Lachlan Tegart; Nithya Fernandopulle; Hee Sung Kang; Edwin R. Lampugnani; Jonathan Pham; Graham A. Mackay; Edward J. Newbigin; John F. Golz (Environmental Research, 2026)

Radiopaque microsphere-hydrogel composite for extended-release intratumoral immunotherapy in a large animal model - Anup Kumar Patel; Imran Shair Mohammad; Marcin Kortylewski; Steven T Rosen; Jonathan Kessler; Julie Ressler; Cherng H Chao; Taedo Jake Choi; Chandana Lall; Catalina Guerra; F. Edward Boas (Drug Delivery and Translational Research, 2026)
Intratumoral injection of immune stimulants could potentially reverse the immunosuppressive tumor microenvironment, but the injected drug rapidly washes out into the systemic circulation. This results in systemic toxicity, and reduced efficacy, potentially requiring daily injections to generate an antitumor immune response. To address this problem, we developed an extended-release hydrogel that retains the immunotherapy agent at the injection site, and releases it over several days, even in highly vascular liver tumors. The extended-release hydrogel is a composite material containing drug-loaded microspheres (for sustained, tunable drug release), embedded in a radiopaque cross-linked hydrogel (for local retention). Using these new intratumoral drug carriers, we demonstrate the ability to safely deliver a wide range of different immunotherapy agents (cytokines, oligonucleotides, small molecules) into pig liver tumors, with no acute systemic toxicity. The microsphere gel reduces burst release by 7.8x (compared to microspheres), and increases half-life by > 15x (compared to hydrogel). Thus, the immunotherapy-loaded microsphere gel enables sustained intratumoral delivery of immune stimulants from a single injection, with low systemic toxicity.

The Role of Gene Flow in the Diversification of the Monkey Treefrog Complex Across the South American Dry Diagonal - Felipe Camurugi; Vinícius A. São Pedro; Felipe Magalhães; Marcelo Gehara; Eliana F. Oliveira; Gabriel C. Costa; Frank T. Burbrink; Edward A. Myers; Guarino R. Colli; Miguel T. Rodrigues; Adrian A. Garda (Zoologica Scripta, 2026)
Understanding Neotropical megadiversity remains challenging due to fundamental taxonomic issues, including identifying and describing cryptic species and their distribution, and the limited knowledge of key factors driving biological diversification. Such challenges are especially prominent in diverse clades with high levels of cryptic species, such as many Neotropical frogs. Herein, we conduct a mitochondrial phylogenetic study on monkey treefrogs in the genus Pithecopus and a multilocus analysis of the P. hypochondrialis species group throughout its distribution in the South American dry diagonal (DD). Our goals were to infer the main lineages and identify historical factors that led to their divergence. Among nine currently recognised species, we found 14 well‐structured mitochondrial lineages in two main clades, which diversified during the Paleogene/Neogene transition. The lowland clade is widely distributed in the DD, and our multilocus analysis suggests it comprises seven geographically structured lineages: P. azureus , two lineages of P. hypochondrialis , two species and one lineage for the P. nordestinus complex, and Pithecopus sp. Considering the geomorphological history of the region, diversification may have been promoted by allopatric speciation during Miocene paleogeographic events, especially the Brazilian Plateau compartmentalization and fluctuations in the São Francisco River water volume. Furthermore, gene flow between some lineages may be explained by niche conservatism and demographic expansions during the late Pleistocene, a period marked by climatic fluctuations and biome shifts. Our results reinforce the importance of both Neogene tectonic activity and Quaternary climatic fluctuations in shaping the Neotropical biota.

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Lake sturgeon ( Acipenser fulvescens ) growth and longevity estimated from adult capture–mark–recapture data - Edward A. Baker; Scott F. Colborne; Nancy A. Auer; Kim T. Scribner; Douglas L. Larson; Andrew S. Briggs; Ronald M. Bruch; Margaret H. Stadig; Michael C. Donofrio (Journal of Fish Biology, 2026)
Effective fishery management policy depends on accurate life‐history data, particularly for harvested species. Longevity is a core life‐history trait that is directly related to annual survival and lifetime reproductive potential, but fish longevity is generally not well documented, particularly for long‐lived species. We used capture–mark–recapture data spanning 44 years as an alternative method to estimate sex‐specific adult lake sturgeon ( Acipenser fulvescens ) average annual growth and longevity for five populations in the Laurentian Great Lakes. We determined individual fish average annual growth and fit population and sex‐specific exponential lines for average annual growth as a function of fish length at initial capture. We used the exponential equations to estimate age for 180 cm fork length (FL) female and 160 cm FL male lake sturgeon from each population by sequential subtraction of annual growth increments and assuming age at onset of sexual maturity of 24 and 15 years for females and males, respectively. Average annual growth estimates varied between sexes and among populations and ranged from 0.26 to 1.15 cm year −1 . Estimated ages also varied among populations. Age estimated for a 160 cm FL male lake sturgeon across the five populations ranged from 90 to 279 years. Age for a 180 cm FL female across populations ranged from 99 to 427 years. Our data suggest lake sturgeons live much longer than currently believed. High longevity and inferentially higher adult survival have important implications for sturgeons in general and support conservative harvest regulations for lake sturgeon fisheries.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

A laboratory-based spectrometer intercomparison for the measurement of snow spectra - Benjamin M. Roberts-Pierel; Christopher J. Crawford; Steven W. Brown; Raymond F. Kokaly; Kelly E. Gleason; Anne W. Nolin; Edward H. Bair; Brenton A. Wilder; Anton J. Surunis; S. McKenzie K. Skiles; Joachim Meyer; Allyson E. Fitts; et al. (Cold Regions Science and Technology, 2026)

Accessing crop genetic diversity via pangenomics - Tessa R. MacNish; Venkataramana Kopalli; Silvia F. Zanini; Rod J. Snowdon; Agnieszka A. Golicz; David Edwards (Theoretical and Applied Genetics, 2026)
With the increasing accuracy and decreasing cost of sequencing technology, the extent of structural variation (SV) and its importance in crop species has become increasingly evident. SVs such as insertions, deletions, and inversions have been associated with genetic variation of agronomically important traits and the diversification of crop species. Pangenomes aim to capture the genetic diversity of a species, population or genus, by incorporating the genomes of multiple individuals. The additional genetic diversity represented by a pangenome compared to a single-genome reference can aid the association of variation with traits and support crop improvement. Genus-wide pangenomes representing related crop species as well as their wild relatives can be used to identify and introduce novel genetic variation associated with agronomically important traits into crops. Pangenomes can aid crop improvement through pangenome assisted breeding (PAB) and genome editing. PAB is an adaption of marker assisted breeding that associates pangenome-based markers, including single nucleotide polymorphisms (SNPs) and SVs, with a trait of interest. Genome editing can use CRISPR/cas9 or similar tools to introduce or change the expression of agronomically important SVs. Pan-epigenomics is an emerging field that can complement pangenomics studies by identifying epigenetic modifications such as DNA methylation, histone modifications, and chromatin accessibility, which play important roles in regulating gene expression and have been shown to contribute to intraspecific diversity and agronomically important traits. We highlight the advances of crop pangenomics and their use in crop breeding and improvement.

Hormonal and behavioral variation during release from reproductive suppression in an extreme cooperative breeder - Phoebe D. Edwards; Juweriah Munir; Ilapreet Toor; Bruce D. Goldman; Rudy Boonstra; Rupert Palme; Gabriela F. Mastromonaco; Melissa M. Holmes (Mammalian Biology, 2026)

Beyond the Guinea Pig Myth: Understanding Complex Attitudes Toward Clinical Trials Participation in a Community Clinic - J. Edward Murrell; Ashleigh Allgood; Arya Tamhane; Regan Gaskin; Luis F. Pineda; Barry P. Sleckman; Raegan W. Durant; Soumya J. Niranjan (Journal of Cancer Education, 2026)

Informing spatial conservation prioritization with species’ traits - Liam A. Trethowan; Laura Jennings; Haerul Arifin; Renata Borosova; Gemma L. C. Bramley; Marie Briggs; Osanna Chu; Ruth P. Clark; Sally Dawson; Kiran L. Dhanjal‐Adams; Yance de Freitas; James Hartup; et al. (Conservation Biology, 2026)
New Guinea, the most botanically diverse island on the planet, is the location for one of the boldest conservation initiatives. The Manokwari Declaration aims to achieve 70% conservation designation for the Bird's Head Peninsula. This is 40% higher than the 2022 Global Biodiversity Framework target. However, there is a lack of species occurrence data to support evidence of where biodiversity can be best protected. To address this, we integrated plant trait data from taxonomic descriptions in species occurrence models that can inform conservation planning. Inclusion of traits improved the performance of co‐occurrence models of ∼800 plant species across the 100,000‐km 2 landscape. Traits generally improved model performance, but not all traits contributed equally (e.g., leaf size and red flower color most improved accuracy of occurrence prediction). Likewise, trait‐parameterized models tended to be most useful with rare species occurrence prediction, but this was inconsistent among traits. Under 70% protection, three‐quarters of the areas selected conserved trait diversity. Critically, trait diversity also increased the chances that areas at high risk of deforestation were selected as conservation priorities. Overall, we found that plant species’ traits, often key parameters of ecosystem function and resilience, improved spatial conservation planning.

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

Extracellular enzyme activities under adaptive multi-paddock and conventional grazing in grassland soils of western Canada - Dauren Kaliaskar; Edward W. Bork; Cameron N. Carlyle; Bharat M. Shrestha; Timm F. Döbert; Cole D. Gross; Upama Khatri-Chhetri; Mark S. Boyce; Scott X. Chang (Pedobiologia, 2026)

Evaluating the performance differences between standard and elasticized EPS used in integral abutments - Yasin Karakus; Burak F. Tanyu; Erol Guler; Edward J. Hoppe (Transportation Geotechnics, 2026)

Elevated organic carbon in African Dark Earths is not exclusively attributable to pyrogenic organic matter - Maura P. Slocum; Riley B. Barton; Sasha J. Wagner; Johannes Lehmann; Dawit Solomon; Edward Yeboah; Alain F. Plante (Science of The Total Environment, 2026)

Acute toxicity assessment and real-time metabolic rate responses of early life stage Macrobrachium rosenbergii to ammonia exposures at different salinities - Cameron M. Emadi; Fabio Dos Santos Neto; Jason R. Bohenek; Breana Smithers; Miguel F. Acevedo; Edward M. Mager (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Speleothem-based reconstruction of Holocene changes in monsoonal patterns and environmental conditions in Central Brazil - Marcela Eduarda Della Libera; Julio Cauhy; Cintia Stumpf; Roberto V. Santos; Francisco W. Cruz; Nicolas M. Stríkis; Luciana F. Prado; Jean-Sebastian Moquet; Michael Weber; Rebecca Orrison; Hai Cheng; R. Lawrence Edwards; et al. (Global and Planetary Change, 2026)

Microtopography and surface features of the mid-Pleistocene Kalkkop impact crater and Palaeolake, South Africa - K.L. Kirsten; A.F. Blackwood; D.L. Delaney; T.R. Edwards; F. Fourie; T. Haberzettl; K. Hadebe; J. Hellstrom; M. Huber; M. Keebine; A.M. Muasya; A.H.I. Razafimanantsoa; et al. (CATENA, 2026)

Soil carbon stocks in cultivated Luvisols respond positively to long-term agronomic practices with different degrees of perennial forage inclusion - Jamin N. Achtymichuk; Miles F. Dyck; Sylvie A. Quideau; Erick R.S. Santos; Dick Puurveen; Scott R. Jeffrey; Edward W. Bork (Geoderma Regional, 2025)

Challenging the conductive paradigm: The unexpected role of sand in anaerobic digestion - Nicolás Hoffmann; Cátia S.N. Braga; Olga Rubilar; Gustavo Ciudad; Gonzalo Tortella; Edward Hermosilla; M.Salomé Duarte; Luciana Pereira; Andreia F. Salvador; Gilberto Martins (Bioresource Technology, 2025)

Linking crystal shape and dynamic undercooling: a new framework for inferring magmatic crystallization histories - Amanda Lindoo; Madeleine C. S. Humphreys; Charlotte Gordon; Martin F. Mangler; Edward W. Llewellin; Richard A. Brooker; Fabian B. Wadsworth; Eshbal Geifman (Contributions to Mineralogy and Petrology, 2025)
Magmas contain crystals exhibiting diverse shapes and sizes, yet the relationship between crystal shape (specifically aspect ratio) and undercooling ( $$Δ T$$ ), the driving force for crystallization, remains poorly constrained. Crystal shape should correlate with undercooling because undercooling governs the growth regime (interface-controlled versus diffusion-controlled) and thus the resulting crystal form. Prior experiments confirm that large nominal undercoolings drive transitions from polyhedral to hopper, skeletal, or dendritic forms. Large undercoolings reflect rapid decompression or cooling, differing from slower cooling rates typical of magmatic intrusions and storage systems. In such slowly cooled environments, crystals remain polyhedral, exhibiting subtle shape variations. Accurately quantifying crystal shape evolution at relatively low undercoolings could provide critical insights into crystallization histories, improving interpretations of the timescales and processes governing magma storage and eruption dynamics. Experimental verification of correlations between aspect ratios of polyhedral crystals and cooling rates remains inconclusive, possibly because nominal undercooling neglects the dynamic evolution of undercooling throughout crystallization. To address this, we introduce average instantaneous undercooling ( $$\overline{{Δ T_{I} }}$$ ), a metric capturing dynamic undercooling history during crystallization. Through controlled cooling experiments and numerical modelling, we demonstrate that higher $$\overline{{Δ T_{I} }}$$ histories produce tabular, high aspect ratio plagioclase crystals, whereas lower $$\overline{{Δ T_{I} }}$$ produces more prismatic crystals with lower aspect ratios. These variations in shape reflect undercooling-driven shifts in the predominant growth mechanism operating on different crystal faces. By quantitatively linking crystal shape to $$\overline{{Δ T_{I} }}$$ , our study provides a new approach for reconstructing crystallization histories in magmas under varying pH2O-T-t conditions.

Hydrological variability in the Black Sea region during the last 670,000 years recorded in multi-proxy speleothem records from northern Türkiye - F. Held; H. Cheng; R.L. Edwards; T. Kipfer; O. Tüysüz; K. Koç; S. Affolter; D. Fleitmann (Quaternary Science Reviews, 2025)

Transgressive gene expression disrupts the molting process in hybrids of two invasive termites - Kyung Seok Kim; Darshan Chetty; Thomas Chouvenc; Joseph F. Velenovsky; Sang-Bin Lee; Seema Rana; Edward L. Vargo (Insect Biochemistry and Molecular Biology, 2025)

Transformations of particulate organic matter from the surface to the abyssal plain in the North Pacific as inferred from compound-specific stable isotope and microbial community analyses - Lee C. Miller; Hilary G. Close; Kalina C. Grabb; Christine L. Huffard; Fuyan Li; David M. Karl; Kenneth L. Smith; Edward F. DeLong; Claudia R. Benitez-Nelson; Jeffrey C. Drazen; Brian N. Popp (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Functional traits mediate the effect of environmental conditions on tree growth of common Andean trees - Eduardo Aguirre-Mazzi; Carla Maldonado; Leslie Cayola; Alfredo F. Fuentes; M. Isabel Loza; Christine E. Edwards; J. Sebastián Tello (Forest Ecology and Management, 2025)

Context-dependent controls of periphyton across the littoral-benthic habitat of deep, clear lakes - Aldo San Pedro; Facundo Scordo; Carina Seitz; Edward M. Krynak; Scott F. Girdner; Joanna Blaszczak; Sudeep Chandra (Aquatic Sciences, 2025)

Nosema or Vairimorpha: Genomic/proteomic support to a complex socio-economic issue rooted in taxonomic change - Jamie Bojko; James Becnel; Edouard Bessette; Sam Edwards; Jing Gao; Wei-Fone Huang; Nataša Katanić; Amjad Khalaf; Tian Li; Jonathan W. Snow; Leellen F. Solter; Cheyenne E. Stratton; et al. (Journal of Invertebrate Pathology, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Corrigendum to FTIR spectra from grass pollen: A quest for species-level resolution of Poaceae and Cerealia-type pollen grains [Review of Palaeobotany and Palynology, 321 (2024): 105039] - F. Katsi; M.S. Kent; M. Jones; W.T. Fraser; P.E. Jardine; W. Eastwood; M. Mariani; C. Osborne; S. Edwards; B.H. Lomax (Review of Palaeobotany and Palynology, 2025)

Sea-level rise and freshwater management are reshaping coastal landscapes - Amanda Richey; Steven F. Oberbauer; Edward Castañeda-Moya; Tiffany Troxler; John S. Kominoski; Paulo Olivas; Sparkle L. Malone (Journal of Environmental Management, 2025)

Contrasting grazing practices alter plant community trajectories across western Canada’s grasslands with implications for ecosystem function - Timm F. Döbert; Lysandra A. Pyle; Carter Case; Edward W. Bork; Cameron N. Carlyle; Scott X. Chang; Laio Silva Sobrinho; Majid Iravani; Mark S. Boyce (Agriculture, Ecosystems & Environment, 2025)

Onset and evolution of summit lava fountaining during the Mauna Loa 2022 eruption - Natália G. Pasqualon; Bruce F. Houghton; Matthew R. Patrick; Edward W. Llewellin; Caroline M. Tisdale (Bulletin of Volcanology, 2025)

Interference of PFAS sorption on zeolites from natural water characteristics - Nathaniel P. Sheehan; Charles A. Ponge; Abe Pankratz; Justin M. Hutchison; Brian B. Laird; Nuong P. Nguyen; Mark B. Shiflett; Deepak Timalsina; Michael Zhuo Wang; Edward F. Peltier (Chemosphere, 2025)

Informatics for toxicokinetics - Gilberto Padilla Mercado; Christopher Cook; Norman Adkins; Lucas Albrecht; Grace Cary; Brenda Edwards; Derik E. Haggard; Nancy M. Hanley; Michael F. Hughes; Anna Jarnagin; Tirumala D. Kodavanti; Evgenia Korol-Bexell; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2025)

Quantifying explosive processes of the 2022 Meradalir eruption of the Fagradalsfjall Fires, Iceland - Caroline M. Tisdale; Bruce F. Houghton; Thorvaldur Thorsdarson; Edward W. Llewellin; Jóna S. Pálmadóttir (Bulletin of Volcanology, 2025)

Burn parameters affect PAH emissions at conditions relevant for prescribed fires - Karl Töpperwien; Guillaume Vignat; Alexandra J. Feinberg; Conner Daube; Mitchell W. Alton; Edward C. Fortner; Manjula R. Canagaratna; Matthias F. Kling; Mary Johnson; Kari Nadeau; Scott Herndon; John T. Jayne; et al. (Atmospheric Pollution Research, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Self-report and actigraphy measures of sleep and domain-specific cognitive performance in older adults - Kelsey R. Sewell; Audrey M. Collins; Miranda G. Chappel-Farley; Shivangi Jain; Haiqing Huang; George Grove; Arthur F. Kramer; Edward McAuley; Jeffrey Burns; Charles Hillman; Eric Vidoni; Anna Marsland; et al. (GeroScience, 2025)

Ingestive behaviour, performance, and methane emissions of pregnant alpacas grazing cultivated pastures in the high Peruvian Andes - Laura B. Gualdrón-Duarte; Cecilia Loza; José I. Gere; Nancy F. Huanca-Marca; Francisco E. Franco; Yemi Sanca Uscamayta; Rubén García‐Ticllacuri; Guadalupe Orellana Ligas; Diannett Benito López; Feliciano Rivera Pachiño; Juan E. Moscoso-Muñoz; Medardo A. Díaz-Céspedes; et al. (Livestock Science, 2025)

John Raven, FRS, FRSE: a truly great innovator in plant physiology, photosynthesis and much more - A. W. D. Larkum; P. G. Falkowski; Dianne Edwards; C. B. Osmond; H. Lambers; P. Sanchez-Baracaldo; R. J. Ritchie; J. W. Runcie; P. J. Ralph; M. Westoby; S. Maberly; H. Griffiths; et al. (Photosynthesis Research, 2025)
This is a tribute to a truly inspirational plant biologist, Prof. John A. Raven, FRS, FRSE (25th June 1941– 23rd May 2024), who died at the age of 82. He was a leader in the field of evolution and physiology of algae and land plants. His research touched on many areas including photosynthesis, ion transport, carbon utilisation, mineral use, such as silicon, iron and molybdenum, the evolution of phytoplankton, the evolution of root systems, the impact of global change, especially on the acidification of the oceans, carbon gain and water use in early land plants, and ways of detecting extraterrestrial photosynthesis. Beginning his research career in the Botany School, University of Cambridge, John studied ion uptake in a giant algal cell. This was at the time of great strides brought about by Peter Mitchell (1920–1992) in elucidating the role of energy generation in mitochondria and chloroplasts and the coupling of ion transport systems to energy generation. With Enid MacRobbie and Andrew Smith, John pioneered early work on the involvement of ion transport in the growth and metabolism of plant cells.On leaving Cambridge John took up a lectureship at the University of Dundee in 1971, where he was still attached upon his death. His primary focus over the years, with one of us (Paul Falkowski), was on phytoplankton, the photosynthetic microalgae of the oceans. Still, his publication list of 5 books and over 600 scientific papers spans a very broad range. The many highly cited papers (see Table 1) attest to an outstanding innovator, who influenced a multitude of students and coworkers and a very wide readership worldwide. At the personal level, John Raven was a wonderful human being; he had an extraordinary memory, dredging up facts and little-known scientific papers, like a scientific magician, but at the same time making humorous jokes and involving his colleagues in fun and sympathetic appreciation. Table 1 Ten best cited articles (from google scholar) Citations Date Aquatic Photosynthesis, 3rd EditionP.G. Falkowski & J.A. RavenPrinceton University Press, 2013 3854 2013 The evolution of modern eukaryotic phytoplanktonP.G. Falkowski, M.E. Katz, A.H. Knoll, A. Quigg, J.A. Raven, et alScience 305 , 354–360 1790 2004 C O 2 concentrating mechanisms in algae:mechanisms, environmental modulation, and evolutionM. Giordano, J. Beardall & J.A. RavenAnnu. Rev. Plant Biol. 56 (1), 99–131 1648 2005 Algae as nutritional food sources: revisiting our understandingM.L. Wells, P. Potin, J.S. Craigie, J.A. Raven, S.S. Merchant, et alJournal of applied phycology 29 , 949–982 1527 2017 Plant Nutrient acquisition strategies change with soil ageH. Lambers, J.A. Raven, G.R. Shaver & S.E. SmithTrends in ecology & evolution 23 , 95–103 1488 2008 Ocean acidification due to increasing atmospheric carbon dioxideJ. Raven, K. Caldeira, H. Elderfield, O. Hoegh-Guldberg, P. Liss, et alThe Royal Society, Policy Document, June 2005 1470 2005 Phytoplankton in a changing world: cell size and elemental stoichiometryZ.V. Finkel, J. Beardall, K.J. Flynn, A. Quigg, T.A.V. Rees & J.A. RavenJournal of plankton research 32 , 119–137 1198 2010 Opportunities for improving phosphorus efficiency in crop plantsE.J. Veneklaas, H. Lambers, J. Bragg, P.M. Finnegan, C.E. Lovelock, et alNew phytologist 195 , 306–320 951 2012 Adaptation of unicellular algae to irradiance: an analysis of strategiesK. Richardson, J. Beardall & J.A. RavenNew Phytologist 93 , 157–191 914 1983 N itrogen assimilation and transport in vascular land plants in relation to Intracellular pH regulationJ.A. Raven & F.A. SmithNew Phytologist 76 , 415–431 893 1976 Temperature and algal growth J.A. Raven & R.J. GeiderNew phytologist 110 , 441–461 867 1988 The role of trace metals in photosynthetic electron transport in O 2 -evolving organismsJ.A. Raven, M.C.W. Evans & R.E. KorbPhotosynthesis Research 60 , 111–150 840 1999

Eddy dipole differentially influences particle‐associated and water column protistan community composition - Jennifer L. Beatty; Brittany P. Stewart; Lisa Y. Mesrop; Edward F. DeLong; David M. Karl; David A. Caron (Limnology and Oceanography, 2025)
Ocean eddies are mesoscale features that can extend > 100 km and maintain cohesiveness for months, impacting planktonic community structure and water column biogeochemical cycles. Standing stocks of protists in the water column and on sinking particles were investigated using microscopy, in situ imagery, and metabarcoding across an anticyclonic to cyclonic eddy dipole in the North Pacific Subtropical Gyre during July 2017. The water column was sampled from the surface to 500 m and particle interceptor traps were deployed at 150 m. Protistan assemblage composition varied substantially between sample type and analytical approach across the eddy dipole. Alveolates represented 63% of sequences from water samples. In contrast to water samples, rhizarian protists represented 79% of trap sequences obtained by metabarcoding of sediment trap material. Microscopy of trap material supported the important contribution of Rhizaria to sinking particles and revealed increased relative abundances of ciliates in the anticyclonic eddy and diatoms in the cyclonic eddy. In situ imagery confirmed the presence of relatively large Rhizaria that were not adequately assessed from water samples but contributed significantly to particle flux. Together, these data demonstrate differing perspectives of planktonic protistan community composition and contributions to sinking particles gained from the application of different sampling and analytic approaches. Our observations and analyses indicate a specific subset of the protistan community contributed disproportionately to organic matter downward export.

The function of love: A signaling-to-alternatives account of the commitment device hypothesis - Benjamin Gelbart; Kathryn V. Walter; Daniel Conroy-Beam; Casey Estorque; David M. Buss; Kelly Asao; Agnieszka Sorokowska; Piotr Sorokowski; Toivo Aavik; Grace Akello; Mohammad Madallh Alhabahba; Charlotte Alm; et al. (Evolution and Human Behavior, 2025)

Resilience to Hurricanes Is High in Mangrove Blue Carbon Forests - David Reed; Selena Chavez; Edward Castañeda‐Moya; Steven F. Oberbauer; Tiffany Troxler; Sparkle Malone (Global Change Biology, 2025)
Mangrove forests are typically considered resilient to natural disturbances, likely caused by the evolutionary adaptation of species‐specific traits. These ecosystems play a vital role in the global carbon cycle and are responsible for an outsized contribution to carbon burial and enhanced sedimentation rates. Using eddy covariance data from two coastal mangrove forests in the Florida Coastal Everglades, we evaluated the impact hurricanes have on mangrove forest structure and function by measuring recovery to pre‐disturbance conditions following Hurricane Wilma in 2005 and Hurricane Irma in 2017. We determined the “recovery debt,” the deficit in ecosystem structure and function following a disturbance, using the leaf area index (LAI) and the net ecosystem exchange (NEE) of carbon dioxide (CO 2 ). Calculated as the cumulative deviation from pre‐disturbance conditions, the recovery debt incorporated the recapture of all the carbon lost due to the disturbance. In Everglades mangrove forests, LAI returned to pre‐disturbance levels within a year, and ecosystem respiration and maximum photosynthetic rates took much longer, resulting in an initial recovery debt of 178 g C m −2 at the tall forest with limited impacts at the scrub forest. At the landscape scale, the initial recovery debt was 0.40 Mt C, and in most coastal mangrove forests, all lost carbon was recovered within just 4 years. While high‐intensity storms could have prolonged impacts on the structure of subtropical forests, fast canopy recovery suggests these ecosystems will remain strong carbon sinks.

Achieving multifunctionality in green infrastructure projects: a fuzzy evaluation and Gini index of Key drivers in developing countries - S. Seidu; D. J. Edwards; D. Owusu-Manu; D. W. M. Chan; S. F. Abdulai; J. I. T. Buertey (Environment, Development and Sustainability, 2025)
While many developed countries are well advanced in green infrastructure (GI), more efforts are needed to bring less developed regions to speed. Existing evidence shows that GI understanding differs significantly among stakeholders due to the multifunctionality concept. As key technical stakeholders in GI implementation, there is little empirical knowledge of the multifunctional attributes of GI systems among built environment professionals in developing regions. This study provides an in-depth analysis to fill this knowledge gap through a combination of the Gini coefficient and fuzzy synthetic evaluation toward understanding the multifunctionality concept of GI among built environment professionals in developing regions. As a measure of dispersion, the stationary driver points to a constant factor that underpins the implementation of GI across several geographic regions. The need to mitigate urban heat islands and enhance ecosystem services were revealed as the anchors among built environment professionals in supporting GI development; hence, specific attention needs to be accorded to these dimensions in GI policies. Ecosystem services, water resources management, and thermal regulation were identified as the three broad multifunctional drivers of GI in developing nations. For effective water management in GI projects, integrated green-grey infrastructure systems are recommended. To achieve thermal objectives, insulation materials are pivotal. The ecosystem properties are more passive as compared to thermal and water management; hence, specific considerations must be accorded to ensure GI success. The key contribution of the study was the delineation of the key multifunctional factors that support GI adoption and implementation success in developing regions.

Competing mechanisms for the buckling of an epithelial monolayer identified using multicellular simulation - Phillip J. Brown; J. Edward F. Green; Benjamin J. Binder; James M. Osborne (Mathematical Biosciences, 2025)

A bioinformatic examination of indole-3-acetic acid biosynthesis in insecta and hexapoda - Joshua Natahusada; Scott W. Roy; Edward F. Connor (Arthropod-Plant Interactions, 2025)

Divergence in Regulatory Regions and Gene Duplications May Underlie Chronobiological Adaptation in Desert Tortoises - N. Jade Mellor; Timothy H. Webster; Hazel Byrne; Avery S. Williams; Taylor Edwards; Dale F. DeNardo; Melissa A. Wilson; Kenro Kusumi; Greer A. Dolby (Molecular Ecology, 2025)
Many cellular processes and organismal behaviours are time‐dependent, and asynchrony of these phenomena can facilitate speciation through reinforcement mechanisms. The Mojave and Sonoran desert tortoises ( Gopherus agassizii and G. morafkai respectively) reside in adjoining deserts with distinct seasonal rainfall patterns and they exhibit asynchronous winter brumation and reproductive behaviours. We used whole genome sequencing of 21 individuals from the two tortoise species and an outgroup to understand genes potentially underlying these characteristics. Genes within the most diverged 1% of the genome ( F ST ≥ 0.63) with putatively functional variation showed extensive divergence in regulatory elements, particularly promoter regions. Such genes related to UV nucleotide excision repair, mitonuclear and homeostasis functions. Genes mediating chronobiological (cell cycle, circadian and circannual) processes were also among the most highly diverged regions (e.g., XPA and ZFHX3 ). Putative promoter variants had significant enrichment of genes related to regulatory machinery (ARC‐Mediator complex), suggesting that transcriptional cascades driven by regulatory divergence may underlie the behavioural differences between these species, leading to asynchrony‐based prezygotic isolation. Further investigation revealed extensive expansion of respiratory and intestinal mucins (MUC5B and MUC5AC) within Gopherus , particularly G. morafkai . This expansion could be a xeric‐adaptation to water retention and/or contribute to differential Mycoplasma agassizii infection rates between the two species, as mucins help clear inhaled dust and bacterial. Overall, results highlight the diverse array of genetic changes underlying divergence, adaptation and reinforcement during speciation.

Patterns of siderophore production and utilization at Station ALOHA from the surface to mesopelagic waters - Randelle M. Bundy; Lauren E. Manck; Daniel J. Repeta; Matthew J. Church; Nicholas J. Hawco; Rene M. Boiteau; Jiwoon Park; Edward F. DeLong; Mak A. Saito (Limnology and Oceanography, 2025)
The North Pacific subtropical gyre is a globally important contributor to carbon uptake despite being a persistently oligotrophic ecosystem. Supply of the micronutrient iron to the upper ocean varies seasonally to episodically, and when coupled with rapid biological consumption, results in low iron concentrations. In this study, we examined changes in iron uptake rates, along with siderophore concentrations and biosynthesis potential at Station ALOHA across time (2013–2016) and depth (surface to 500 m) to observe changes in iron acquisition and internal cycling by the microbial community. The genetic potential for siderophore biosynthesis was widespread throughout the upper water column, and biosynthetic gene clusters peaked in spring and summer along with siderophore concentrations, suggesting changes in nutrient delivery, primary production, and carbon export seasonally impact iron acquisition. Dissolved iron turnover times, calculated from iron‐amended experiments in surface (15 m) and mesopelagic (300 m) waters, ranged from 9 to 252 d. The shortest average turnover times at both depths were associated with inorganic iron additions (14 9 d) and the longest with iron bound to strong siderophores (148 225 d). Uptake rates of siderophore‐bound iron were faster in mesopelagic waters than in the surface, leading to high Fe : C uptake ratios of heterotrophic bacteria in the upper mesopelagic. The rapid cycling and high demand for iron at 300 m suggest differences in microbial metabolism and iron acquisition in the mesopelagic compared to surface waters. Together, changes in siderophore production and consumption over the seasonal cycle suggest organic carbon availability impacts iron cycling at Station ALOHA.

Small grants advance global ocean conservation and management equity - Elizabeth H. Stephenson; Bess-Lyn Edwards; Emily Duwan; Benny Berger; Asha de Vos; Kerstin Forsberg; Nelly Isigi Kadagi; Michael F. Tlusty; Jessica V. Redfern (Biological Conservation, 2024)

A Transcriptomic Comparative Study of Cranial Vasculature - Jianing Zhang; Jee-Yeon Ryu; Selena-Rae Tirado; Lawrence D. Dickinson; Aviva Abosch; M. Ali Aziz-Sultan; Alan S. Boulos; Daniel L. Barrow; H. Hunt Batjer; Tamar R. Binyamin; Spiros L. Blackburn; Edward F. Chang; et al. (Translational Stroke Research, 2024)

Combustion of solid fuels containing boron, borides, and boron based composites in a solid fuel ramjet - Chase Leuchtmann; Dominic F. Gallegos; Gregory Young; Mirko Schoenitz; Edward L. Dreizin (Fuel, 2024)

Numerical investigation of peripheral fuel injection to increase performance in diesel engines - Edward F. Bogdanowicz; Joshua A. Bittle; Ajay K. Agrawal (Fuel, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Bioenergetic mapping of ‘healthy microbiomes’ via compound processing potential imprinted in gut and soil metagenomes - Craig Liddicoat; Robert A. Edwards; Michael Roach; Jake M. Robinson; Kiri Joy Wallace; Andrew D. Barnes; Joel Brame; Anna Heintz-Buschart; Timothy R. Cavagnaro; Elizabeth A. Dinsdale; Michael P. Doane; Nico Eisenhauer; et al. (Science of The Total Environment, 2024)

Emotional and functional well-being in long-term breast cancer survivorship - Yumeng Ren; Joanna Maselko; Xianming Tan; Andrew F. Olshan; Angela M. Stover; Antonia V. Bennett; Katherine E. Reeder-Hayes; Jessie K. Edwards; Bryce B. Reeve; Melissa A. Troester; Marc A. Emerson (Cancer Causes & Control, 2024)

Transient, context‐dependent fitness costs accompanying viral resistance in isolates of the marine microalga Micromonas sp. (class Mamiellophyceae) - Anamica Bedi de Silva; Shawn W. Polson; Christopher R. Schvarcz; Grieg F. Steward; Kyle F. Edwards (Environmental Microbiology, 2024)
Marine microbes are important in biogeochemical cycling, but the nature and magnitude of their contributions are influenced by their associated viruses. In the presence of a lytic virus, cells that have evolved resistance to infection have an obvious fitness advantage over relatives that remain susceptible. However, susceptible cells remain extant in the wild, implying that the evolution of a fitness advantage in one dimension (virus resistance) must be accompanied by a fitness cost in another dimension. Identifying costs of resistance is challenging because fitness is context‐dependent. We examined the context dependence of fitness costs in isolates of the picophytoplankton genus Micromonas and their co‐occurring dsDNA viruses using experimental evolution. After generating 88 resistant lineages from two ancestral Micromonas strains, each challenged with one of four distinct viral strains, we found resistance led to a 46% decrease in mean growth rate under high irradiance and a 19% decrease under low. After a year in culture, the experimentally selected lines remained resistant, but fitness costs had attenuated. Our results suggest that the cost of resistance in Micromonas is dependent on environmental conditions and the duration of population adaptation, illustrating the dynamic nature of fitness costs of viral resistance among marine protists.

Trophic strategies of picoeukaryotic phytoplankton vary over time and with depth in the North Pacific Subtropical Gyre - Kyle F. Edwards; Yoshimi M. Rii; Qian Li; Logan M. Peoples; Matthew J. Church; Grieg F. Steward (Environmental Microbiology, 2024)
In oligotrophic oceans, the smallest eukaryotic phytoplankton are both significant primary producers and predators of abundant bacteria such as Prochlorococcus . However, the drivers and consequences of community dynamics among these diverse protists are not well understood. Here, we investigated how trophic strategies along the autotrophy‐mixotrophy spectrum vary in importance over time and across depths at Station ALOHA in the North Pacific Subtropical Gyre. We combined picoeukaryote community composition from a 28‐month time‐series with traits of diverse phytoplankton isolates from the same location, to examine trophic strategies across 13 operational taxonomic units and 8 taxonomic classes. We found that autotrophs and slower‐grazing mixotrophs tended to prevail deeper in the photic zone, while the most voracious mixotrophs were relatively abundant near the surface. Within the mixed layer, there was greater phagotrophy when conditions were most stratified and when Chl a concentrations were lowest, although the greatest temporal variation in trophic strategy occurred at intermediate depths (45–100 m). Dynamics at this site are consistent with previously described spatial patterns of trophic strategies. The success of relatively phagotrophic phytoplankton at shallower depths in the most stratified waters suggests that phagotrophy is a competitive strategy for acquiring nutrients when energy from light is plentiful.

Where the rubber meets the road: Emerging environmental impacts of tire wear particles and their chemical cocktails - Paul M. Mayer; Kelly D. Moran; Ezra L. Miller; Susanne M. Brander; Stacey Harper; Manuel Garcia-Jaramillo; Victor Carrasco-Navarro; Kay T. Ho; Robert M. Burgess; Leah M. Thornton Hampton; Elise F. Granek; Margaret McCauley; et al. (Science of The Total Environment, 2024)

Catalytic production of light Olefins: Perspective and prospective - Naif S. Almuqati; Afrah M. Aldawsari; Khalid N. Alharbi; Sergio González-Cortés; Mohammed F. Alotibi; Fawaz Alzaidi; Jonathan R. Dilworth; Peter P. Edwards (Fuel, 2024)

Adapting the Marine Stewardship Council risk-based framework to estimate impacts on seabirds, marine mammals, marine turtles and sea snakes - Stephanie D. Good; Kate Dewar; Polly Burns; Keith Sainsbury; Richard A. Phillips; Bryan P. Wallace; Caterina Fortuna; Vinay Udyawer; Bruce Robson; Edward F. Melvin; Rohan J.C. Currey (Marine Policy, 2024)

Risk factors affecting the feeding site predilection of ticks on cattle in Ghana - Seth Offei Addo; Ronald Essah Bentil; Mba-tihssommah Mosore; Eric Behene; Julian Adinkrah; Janice Tagoe; Clara Yeboah; Bernice Olivia Ama Baako; Dorcas Atibila; Sandra Abankwa Kwarteng; Kwaku Poku-Asante; Ellis Owusu-Darbo; et al. (Experimental and Applied Acarology, 2024)
Ticks are important disease vectors affecting animal health and causing substantial economic loss, especially in the tropics and subtropics. To examine the tick burden of cattle and associated risk factors for tick infestation, ticks were collected from 388 cattle within five regions in Ghana. Most of the cattle were males (50.3%) and generally older than 3 years (65%). Of the animals sampled, 2187 ticks were collected with a mean tick burden of 5.6 ticks per cattle, and the average tick burden on the udder/scrotum being significantly higher than in the anal region (Generalized Linear Mix Model [GLMM], p = 0.01197). The tick species identified were predominantly Amblyomma variegatum (42.6%) and Hyalomma rufipes (26.2%). High proportions of cattle examined were found to have A. variegatum infesting the udder/scrotum. Furthermore, H. rufipes infested mostly the anal region compared to other examined body parts (OR 14.8, 95% CI 8.6–25.4, p < 0.001). Using the GLMM, tick abundance was found to be significantly higher in cattle older than 3 years. The tick burden in the udder/scrotum was higher than that from the chest and leg/thigh of the cattle (GLMM, p < 0.05). The tick burden at the anal region was also significantly higher than the leg/thigh and chest. This study indicates that the preferred attachment sites of ticks on cattle are species-dependent and effective treatment with acaricides should take into consideration the udder/scrotum and anal regions as well as prioritizing older cattle.

The structural–functional-connectivity coupling of the aging brain - Hui Zhang; Peng Cao; Henry K. F. Mak; Edward S. Hui (GeroScience, 2024)
Aging primarily affects memory and executive functions, a relationship that may be underpinned by the fact that almost all adults over 60 years old develop small vessel disease (SVD). The fact that a wide range of neuropathologies could only explain up to 43% of the variation in age-related cognitive impairment suggests that other factors, such as cognitive reserve, may play a role in the brain’s resilience against aging-related cognitive decline. This study aims to examine the relationship between structural–functional-connectivity coupling (SFC), and aging, cognitive abilities and reserve, and SVD-related neuropathologies using a cohort of n = 176 healthy elders from the Harvard Aging Brain Study. The SFC is a recently proposed biomarker that reflects the extent to which anatomical brain connections can predict coordinated neural activity. After controlling for the effect of age, sex, and years of education, global SFC, as well as the intra-network SFC of the dorsolateral somatomotor and dorsal attention networks, and the inter-network SFC between dorsolateral somatomotor and frontoparietal networks decreased with age. The global SFC decreased with total cognitive score. There were significant interaction effects between years of education versus white matter hyperintensities and between years of education versus cerebral microbleeds on inter-network SFC. Enlarged perivascular space in basal ganglia was associated with higher inter-network SFC. Our results suggest that cognitive ability is associated with brain coupling at the global level and cognitive reserve with brain coupling at the inter-functional-brain-cluster level with interaction effect from white matter hyperintensities and cerebral microbleed in a cohort of healthy elderlies.

Adverse consequences of herbicide residues on legumes in dryland agriculture - Ronald J. Yates; Emma J. Steel; Tom J. Edwards; Robert J. Harrison; Belinda F. Hackney; John G. Howieson (Field Crops Research, 2024)

State of the California Current Ecosystem report in 2022: a tale of two La Niñas - Andrew R. Thompson; Rasmus Swalethorp; Michaela Alksne; Jarrod A. Santora; Elliott L. Hazen; Andrew Leising; Erin Satterthwaite; William J. Sydeman; Clarissa R. Anderson; Toby D. Auth; Simone Baumann-Pickering; Timothy Baumgardner; et al. (Frontiers in Marine Science, 2024)
2022 marked the third consecutive La Niña and extended the longest consecutive stretch of negative Oceanic Niño Index since 1998-2001. While physical and biological conditions in winter and spring largely adhered to prior La Niña conditions, summer and fall were very different. Similar to past La Niña events, in winter and spring coastal upwelling was either average or above average, temperature average or below average, salinity generally above average. In summer and fall, however, upwelling and temperature were generally average or slightly below average, salinity was close to average and chlorophyll a was close to average. Again, as during prior La Niña events, biomass of northern/southern copepods was above/below average off Oregon in winter, and body size of North Pacific krill in northern California was above average in winter. By contrast, later in the year the abundance of northern krill dropped off Oregon while southern copepods increased and body sizes of North Pacific krill fell in northern California. Off Oregon and Washington abundances of market squid and Pacific pompano (indicators of warm, non-typical La Niña conditions) were high. In the 20 th century, Northern anchovy recruitment tended to be high during cold conditions, but despite mostly warm conditions from 2015-2021 anchovy populations boomed and remained high in 2022. Resident seabird reproductive success, which tended in the past to increase during productive La Niña conditions was highly variable throughout the system as common murre and pelagic cormorant, experienced complete reproductive failure at Yaquina Head, Oregon while Brandt’s cormorant reproduction was average. At three sampling locations off central California, however, common murre reproduction was close to or above average while both pelagic and Brandt’s cormorant were above average. California sealion reproduction has been above average each year since 2016, and pup weight was also above average in 2022, likely in response not to La Niña or El Niño but continuous high abundance of anchovy. The highly variable and often unpredictable physical and biological conditions in 2022 highlight a growing recognition of disconnects between basin-scale indices and local conditions in the CCE. “July-December 2022 is the biggest outlier from individual “strong” La Niña (events) ever going back to the 50s.” – Nate Mantua

FTIR spectra from grass pollen: A quest for species-level resolution of Poaceae and Cerealia-type pollen grains - F. Katsi; M.S. Kent; M. Jones; W.T. Fraser; P.E. Jardine; W. Eastwood; M. Mariani; C. Osborne; S. Edwards; B.H. Lomax (Review of Palaeobotany and Palynology, 2024)

How well do existing surveys track fish community performance measures in the St. Clair-Detroit River System? - Corbin D. Hilling; Megan L. Belore; James Boase; Justin A. Chiotti; Robin L. DeBruyne; Susan E. Doka; Richard Drouin; Christine M. Mayer; Jeff. T. Tyson; Todd Wills; Edward F. Roseman (Environmental Monitoring and Assessment, 2024)

Cytokinin biosynthesis in Hexapoda and Insecta: a bioinformatic analysis - Nate Mooi; Scott W. Roy; Edward F. Connor (Arthropod-Plant Interactions, 2024)

The dimensionality of infection networks among viruses infecting microbial eukaryotes and bacteria - Kyle F. Edwards; Colleen Hayward (Ecology Letters, 2024)
Diverse viruses and their hosts are interconnected through complex networks of infection, which are thought to influence ecological and evolutionary processes, but the principles underlying infection network structure are not well understood. Here we focus on network dimensionality and how it varies across 37 networks of viruses infecting eukaryotic phytoplankton and bacteria. We find that dimensionality is often strikingly low, with most networks being one‐ or two‐dimensional, although dimensionality increases with network richness, suggesting that the true dimensionality of natural systems is higher. Low‐dimensional networks generally exhibit a mixture of host partitioning among viruses and nestededness of host ranges. Networks of bacteria‐infecting and eukaryote‐infecting viruses possess comparable distributions of dimensionality and prevalence of nestedness, indicating that fundamentals of network structure are similar among domains of life and different viral lineages. The relative simplicity of many infection networks suggests that coevolutionary dynamics are often driven by a modest number of underlying mechanisms.

Closing the gap between existing large‐area imaging research and marine conservation needs - Orion S. McCarthy; Kanisha Contractor; Will F. Figueira; Arthur C. R. Gleason; T. Shay Viehman; Clinton B. Edwards; Stuart A. Sandin (Conservation Biology, 2024)
Emerging technology has immense potential to increase the scale and efficiency of marine conservation. One such technology is large‐area imaging (LAI), which relies on structure‐from‐motion photogrammetry to create composite products, including 3‐dimensional (3‐D) environmental models, that are larger in spatial extent than the individual images used to create them. Use of LAI has become widespread in certain fields of marine science, primarily to measure the 3D structure of benthic ecosystems and track change over time. However, the use of LAI in the field of marine conservation appears limited. We conducted a review of the coral reef literature on the use of LAI to identify research themes and regional trends in applications of this technology. We also surveyed 135 coral reef scientists and conservation practitioners to determine community familiarity with LAI, evaluate barriers practitioners face in using LAI, and identify applications of LAI believed to be most exciting or relevant to coral conservation. Adoption of LAI was limited primarily to researchers at institutions based in advanced economies and was applied infrequently to conservation, although conservation practitioners and survey respondents from emerging economies indicated they expect to use LAI in the future. Our results revealed disconnect between current LAI research topics and conservation priorities identified by practitioners, highlighting the need for more diverse, conservation‐relevant research using LAI. We provide recommendations for how early adopters of LAI (typically Global North scientists from well‐resourced institutions) can facilitate access to this conservation technology. These recommendations include developing training resources, creating partnerships for data storage and analysis, publishing standard operating procedures for LAI workflows, standardizing methods, developing tools for efficient data extraction from LAI products, and conducting conservation‐relevant research using LAI.

Surface ocean warming near the core of hurricane Sam and its representation in forecast models - Andrew M. Chiodi; Hristina Hristova; Gregory R. Foltz; Jun A. Zhang; Calvin W. Mordy; Catherine R. Edwards; Chidong Zhang; Christian Meinig; Dongxiao Zhang; Edoardo Mazza; Edward D. Cokelet; Eugene F. Burger; et al. (Frontiers in Marine Science, 2024)
On September 30, 2021, a saildrone uncrewed surface vehicle intercepted Hurricane Sam in the northwestern tropical Atlantic and provided continuous observations near the eyewall. Measured surface ocean temperature unexpectedly increased during the first half of the storm. Saildrone current shear and upper-ocean structure from the nearest Argo profiles show an initial trapping of wind momentum by a strong halocline in the upper 30 m, followed by deeper mixing and entrainment of warmer subsurface water into the mixed layer. The ocean initial conditions provided to operational forecast models failed to capture the observed upper-ocean structure. The forecast models failed to simulate the warming and developed a surface cold bias of ~0.5°C by the time peak winds were observed, resulting in a 12-17% underestimation of surface enthalpy flux near the eyewall. Results imply that enhanced upper-ocean observations and, critically, improved assimilation into the hurricane forecast systems, could directly benefit hurricane intensity forecasts.

The underwater soundscape of the North Sea - F. Basan; J.-G. Fischer; R. Putland; J. Brinkkemper; C.A.F. de Jong; B. Binnerts; A. Norro; D. Kühnel; L.-A. Ødegaard; M. Andersson; E. Lalander; J. Tougaard; et al. (Marine Pollution Bulletin, 2024)

Radon decay product particle radioactivity and oxidative stress biomarkers in patients with COPD - Christopher Romero-Gutierrez; Petros Koutrakis; Man Liu; Carolina L. Zilli Vieira; Brent A. Coull; Edward F. Maher; Junfeng (Jim) Zhang; Eric Garshick (Environmental Research, 2024)

Habitat modelling of native freshwater mussels distinguishes river specific differences in the Detroit and St. Clair rivers of the Laurentian Great Lakes - Shay S. Keretz; Daelyn A. Woolnough; Todd J. Morris; Edward F. Roseman; David T. Zanatta (Ecological Modelling, 2024)

Fine-mapping of a major locus for Fusarium wilt resistance in flax (Linum usitatissimum L.) - S. Cloutier; T. Edwards; C. Zheng; H. M. Booker; T. Islam; K. Nabetani; H. R. Kutcher; O. Molina; F. M. You (Theoretical and Applied Genetics, 2024)
Key message Fine-mapping of a locus on chromosome 1 of flax identified an S-lectin receptor-like kinase (SRLK) as the most likely candidate for a major Fusarium wilt resistance gene. Abstract Fusarium wilt, caused by the soil-borne fungal pathogen Fusarium oxysporum f. sp. lini , is a devastating disease in flax. Genetic resistance can counteract this disease and limit its spread. To map major genes for Fusarium wilt resistance, a recombinant inbred line population of more than 700 individuals derived from a cross between resistant cultivar ‘Bison’ and susceptible cultivar ‘Novelty’ was phenotyped in Fusarium wilt nurseries at two sites for two and three years, respectively. The population was genotyped with 4487 single nucleotide polymorphism (SNP) markers. Twenty-four QTLs were identified with IciMapping, 18 quantitative trait nucleotides with 3VmrMLM and 108 linkage disequilibrium blocks with RTM-GWAS. All models identified a major QTL on chromosome 1 that explained 20–48% of the genetic variance for Fusarium wilt resistance. The locus was estimated to span ~ 867 Kb but included a ~ 400 Kb unresolved region. Whole-genome sequencing of ‘CDC Bethune’, ‘Bison’ and ‘Novelty’ produced ~ 450 Kb continuous sequences of the locus. Annotation revealed 110 genes, of which six were considered candidate genes. Fine-mapping with 12 SNPs and 15 Kompetitive allele-specific PCR (KASP) markers narrowed down the interval to ~ 69 Kb, which comprised the candidate genes Lus10025882 and Lus10025891 . The latter, a G-type S-lectin receptor-like kinase (SRLK) is the most likely resistance gene because it is the only polymorphic one. In addition, Fusarium wilt resistance genes previously isolated in tomato and Arabidopsis belonged to the SRLK class. The robust KASP markers can be used in marker-assisted breeding to select for this major Fusarium wilt resistance locus.

Peatland pools are tightly coupled to the contemporary carbon cycle - Joshua F. Dean; Michael F. Billett; T. Edward Turner; Mark H. Garnett; Roxane Andersen; Rebecca M. McKenzie; Kerry J. Dinsmore; Andy J. Baird; Pippa J. Chapman; Joseph Holden (Global Change Biology, 2024)
Peatlands are globally important stores of soil carbon (C) formed over millennial timescales but are at risk of destabilization by human and climate disturbance. Pools are ubiquitous features of many peatlands and can contain very high concentrations of C mobilized in dissolved and particulate organic form and as the greenhouses gases carbon dioxide (CO 2 ) and methane (CH 4 ). The radiocarbon content ( 14 C) of these aquatic C forms tells us whether pool C is generated by contemporary primary production or from destabilized C released from deep peat layers where it was previously stored for millennia. We present novel 14 C and stable C (δ 13 C) isotope data from 97 aquatic samples across six peatland pool locations in the United Kingdom with a focus on dissolved and particulate organic C and dissolved CO 2 . Our observations cover two distinct pool types: natural peatland pools and those formed by ditch blocking efforts to rewet peatlands (restoration pools). The pools were dominated by contemporary C, with the majority of C (~50%–75%) in all forms being younger than 300 years old. Both pool types readily transform and decompose organic C in the water column and emit CO 2 to the atmosphere, though mixing with the atmosphere and subsequent CO 2 emissions was more evident in natural pools. Our results show little evidence of destabilization of deep, old C in natural or restoration pools, despite the presence of substantial millennial‐aged C in the surrounding peat. One possible exception is CH 4 ebullition (bubbling), with our observations showing that millennial‐aged C can be emitted from peatland pools via this pathway. Our results suggest that restoration pools formed by ditch blocking are effective at preventing the release of deep, old C from rewetted peatlands via aquatic export.

Fungal community dissimilarity predicts plant–soil feedback strength in a lowland tropical forest - Camille S. Delavaux; Janika K. Angst; Hilario Espinosa; Makenna Brown; Daniel F. Petticord; John W. Schroeder; Kirk Broders; Edward A. Herre; James D. Bever; Thomas W. Crowther (Ecology, 2024)
Soil microbes impact plant community structure and diversity through plant–soil feedbacks. However, linking the relative abundance of plant pathogens and mutualists to differential plant recruitment remains challenging. Here, we tested for microbial mediation of pairwise feedback using a reciprocal transplant experiment in a lowland tropical forest in Panama paired with amplicon sequencing of soil and roots. We found evidence that plant species identity alters the microbial community, and these changes in microbial composition alter subsequent growth and survival of conspecific plants. We also found that greater community dissimilarity between species in their arbuscular mycorrhizal and nonpathogenic fungi predicted increased positive feedback. Finally, we identified specific microbial taxa across our target functional groups that differentially accumulated under conspecific settings. Collectively, these findings clarify how soil pathogens and mutualists mediate net feedback effects on plant recruitment, with implications for management and restoration.

Sampling method drives differing detection of responses to land-use change in small mammals - Mariana F. Rocha; Luiz Fernando S. Magnago; Marcelo Passamani; Vinicius Chaga Lopes; Sergio Barbiero Lage; David P. Edwards (Journal for Nature Conservation, 2023)

Hydrodynamic response to bathymetric changes in Tampa Bay, Florida - Jing Chen; Yonggang Liu; Robert H. Weisberg; Steven A. Murawski; Sherryl Gilbert; David F. Naar; Lianyuan Zheng; Matthew Hommeyer; Catherine Dietrick; Mark E. Luther; Cheryl Hapke; Edward Myers; et al. (Deep Sea Research Part II: Topical Studies in Oceanography, 2023)

Global responses to the COVID-19 pandemic by recreational anglers: considerations for developing more resilient and sustainable fisheries - J. Robert Britton; Adrian C. Pinder; Josep Alós; Robert Arlinghaus; Andy J. Danylchuk; Wendy Edwards; Kátia M. F. Freire; Casper Gundelund; Kieran Hyder; Ivan Jarić; Robert Lennox; Wolf-Christian Lewin; et al. (Reviews in Fish Biology and Fisheries, 2023)
The global COVID-19 pandemic resulted in many jurisdictions implementing orders restricting the movements of people to inhibit virus transmission, with recreational angling often either not permitted or access to fisheries and/or related infrastructure being prevented. Following the lifting of restrictions, initial angler surveys and licence sales suggested increased participation and effort, and altered angler demographics, but with evidence remaining limited. Here, we overcome this evidence gap by identifying temporal changes in angling interest, licence sales, and angling effort in world regions by comparing data in the ‘pre-pandemic’ (up to and including 2019); ‘acute pandemic’ (2020) and ‘COVID-acclimated’ (2021) periods. We then identified how changes can inform the development of more resilient and sustainable recreational fisheries. Interest in angling (measured here as angling-related internet search term volumes) increased substantially in all regions during 2020. Patterns in licence sales revealed marked increases in some countries during 2020 but not in others. Where licence sales increased, this was rarely sustained in 2021; where there were declines, these related to fewer tourist anglers due to movement restrictions. Data from most countries indicated a younger demographic of people who participated in angling in 2020, including in urban areas, but this was not sustained in 2021. These short-lived changes in recreational angling indicate efforts to retain younger anglers could increase overall participation levels, where efforts can target education in appropriate angling practices and create more urban angling opportunities. These efforts would then provide recreational fisheries with greater resilience to cope with future global crises, including facilitating the ability of people to access angling opportunities during periods of high societal stress.

Review of Solar Energetic Particle Prediction Models - Kathryn Whitman; Ricky Egeland; Ian G. Richardson; Clayton Allison; Philip Quinn; Janet Barzilla; Irina Kitiashvili; Viacheslav Sadykov; Hazel M. Bain; Mark Dierckxsens; M. Leila Mays; Tilaye Tadesse; et al. (Advances in Space Research, 2023)

Top ten priorities for global saltmarsh restoration, conservation and ecosystem service research - Julien Pétillon; Emma McKinley; Meghan Alexander; Janine B. Adams; Christine Angelini; Thorsten Balke; John N. Griffin; Tjeerd Bouma; Sally Hacker; Qiang He; Marc J.S. Hensel; Carles Ibáñez; et al. (Science of The Total Environment, 2023)

Abrupt permafrost thaw drives spatially heterogeneous soil moisture and carbon dioxide fluxes in upland tundra - Heidi Rodenhizer; Susan M. Natali; Marguerite Mauritz; Meghan A. Taylor; Gerardo Celis; Stephanie Kadej; Allison K. Kelley; Emma R. Lathrop; Justin Ledman; Elaine F. Pegoraro; Verity G. Salmon; Christina Schädel; et al. (Global Change Biology, 2023)
Permafrost thaw causes the seasonally thawed active layer to deepen, causing the Arctic to shift toward carbon release as soil organic matter becomes susceptible to decomposition. Ground subsidence initiated by ice loss can cause these soils to collapse abruptly, rapidly shifting soil moisture as microtopography changes and also accelerating carbon and nutrient mobilization. The uncertainty of soil moisture trajectories during thaw makes it difficult to predict the role of abrupt thaw in suppressing or exacerbating carbon losses. In this study, we investigated the role of shifting soil moisture conditions on carbon dioxide fluxes during a 13‐year permafrost warming experiment that exhibited abrupt thaw. Warming deepened the active layer differentially across treatments, leading to variable rates of subsidence and formation of thermokarst depressions. In turn, differential subsidence caused a gradient of moisture conditions, with some plots becoming consistently inundated with water within thermokarst depressions and others exhibiting generally dry, but more variable soil moisture conditions outside of thermokarst depressions. Experimentally induced permafrost thaw initially drove increasing rates of growing season gross primary productivity (GPP), ecosystem respiration ( R eco ), and net ecosystem exchange (NEE) (higher carbon uptake), but the formation of thermokarst depressions began to reverse this trend with a high level of spatial heterogeneity. Plots that subsided at the slowest rate stayed relatively dry and supported higher CO 2 fluxes throughout the 13‐year experiment, while plots that subsided very rapidly into the center of a thermokarst feature became consistently wet and experienced a rapid decline in growing season GPP, R eco , and NEE (lower carbon uptake or carbon release). These findings indicate that Earth system models, which do not simulate subsidence and often predict drier active layer conditions, likely overestimate net growing season carbon uptake in abruptly thawing landscapes.

Reproductive quality evaluation of male Indian white prawn Penaeus indicus broodstock fed diets supplemented with polychaete extracts ( Marphysa sp.) - Sheryll S. Santander-Avanceña; Rex Ferdinand M. Traifalgar; Erish G. Estante-Superio; Steve P. Janagap; Roger Edward P. Mamauag; Harold M. Monteclaro; Liberato V. Laureta; Gerald F. Quinitio (Invertebrate Reproduction & Development, 2023)

Decadal impacts of wildfire fuel reduction treatments on ecosystem characteristics and fire behavior in alaskan boreal forests - Melissa A. Boyd; Xanthe J. Walker; Jennifer Barnes; Gerardo Celis; Scott J. Goetz; Jill F. Johnstone; Nicholas T. Link; April M. Melvin; Lisa Saperstein; Edward A.G. Schuur; Michelle C. Mack (Forest Ecology and Management, 2023)

Differential sensitivity of above- and belowground plant biomass to drought and defoliation in temperate grasslands - Amgaa Batbaatar; Cameron N. Carlyle; Edward W. Bork; Scott X. Chang; James F. Cahill (Agriculture, Ecosystems & Environment, 2023)

Genetic epidemiology of late blight in Australia using ancient DNA - Brittney M. Caruana; Rudolf F de Boer; Brendan Rodoni; Noel O.I. Cogan; Jacqueline Edwards (Australasian Plant Pathology, 2023)
Late blight caused by Phytophthora infestans is the most destructive disease of potatoes worldwide and is most notable as the cause of the Irish potato famine of the mid 1840’s. Whole mitochondrial genome sequences were generated from 44 Australian, two UK and one US isolates of P. infestans stored as either herbarium specimens or as recent samples on FTA cards, spanning the period 1873–2019. Mitochondrial (mt) genome sequence comparison confirmed that over the past c. 110 years, an old A1 strain of P. infestans has been present in Australia. There was evidence, however, that P. infestans had been introduced on multiple separate occasions in the early 1900s prior to the introduction of quarantine measures. The 44 Australian samples included six infected specimens of the Australian native kangaroo apple ( Solanum aviculare ) collected in 1911. The P. infestans mt genome sequences from these isolates clustered with P. infestans from infected potatoes collected in Victoria (1910, 1911, 1986, 1989), South Australia (1909, 2003) and Tasmania (1910, 2019), supporting the hypothesis that Australia has one old strain that has survived since the first arrival of the pathogen into the country. The study highlights the success of Australia’s potato biosecurity setting and supports the need for ongoing surveillance and biosecurity measures to prevent the introduction of the newer more aggressive strains of the pathogen.

A complete COI library of Samoan butterflies reveals layers of endemic diversity on oceanic islands - Claudia Bruschini; Eric D. Edwards; Gerard Talavera; Varea D. Vaurasi; Galumalemana F. Latu; Leonardo Dapporto (Zoologica Scripta, 2023)
We investigated the entire butterfly fauna of the Samoan Archipelago (Pacific Ocean) by combining COI barcode sequences for specimens from these islands with those available in repositories at larger biogeographic scale. Haplotype networks and a generalized mixed Yule‐coalescent (GMYC) model were applied to identify evolutionary significant units (ESUs). The ESUs from Samoan islands were compared with ESUs of the same or sister taxa regionally and worldwide to explore the level of endemicity and of congruence between established taxonomy and COI barcodes. The level of ESUs endemicity was similar to that shown by species and subspecies. Australia was the most frequent origin for Samoan lineages, followed by Orient‐Asia. When comparing the agreement and mismatch between established taxonomy and ESUs between the Australia‐Oceania region and Europe and North America, the COI molecular marker revealed a similar performance in taxonomic identification. Despite this overall convergent pattern, the degree of mtDNA divergence and the analysis of functional traits suggested that the mechanisms producing patterns of genetic differentiation in temperate butterflies over ancient continental lands differ to those occurring across a vast ocean into geologically young islands. Mechanisms on Samoan islands include relatively recent and exceptional oceanic dispersal, possibly followed by repeated extinction events. In the Australia‐Oceania region we found a similar fraction of species showing introgression with the maintenance of phenotypic differences as it occurs on the mainland, but the phenomenon was limited to sectors of each species distribution area. Regular gene flow among the Samoan islands seems to prevent allopatric speciation within the archipelago.

PALEO‐PGEM‐Series : A spatial time series of the global climate over the last 5 million years ( Plio‐Pleistocene ) - Elisa Barreto; Philip B. Holden; Neil R. Edwards; Thiago F. Rangel (Global Ecology and Biogeography, 2023)
Motivation Climate change plays an important role in the generation and maintenance of biodiversity by driving processes such as diversification and range shifts. As a result, biodiversity patterns are often found to carry the imprints of palaeoclimatic changes. However, we still know little about the spatial and temporal variation in climate over the scale of millennia affecting eco‐evolutionary dynamics, mostly because of the scarcity of user‐friendly and freely available spatio‐temporal palaeoclimate series at such temporal scales. Here, we address this gap by presenting PALEO‐PGEM‐Series, a global spatio‐temporal dataset of the last 5 Myr, with 1 kyr resolution, spatially downscaled from emulations performed with the intermediate‐complexity atmosphere–ocean general circulation model PALEO‐PGEM. PALEO‐PGEM‐Series holds the potential to advance our understanding of the mechanisms behind the strong relationship between biodiversity and climate, a pressing need given projected biodiversity responses to anthropogenic climatic change. Main Types of Variables Contained Spatio‐temporal series of monthly temperature and precipitation and 17 derived bioclimatic variables over the Pliocene–Pleistocene, along with standard error estimates from multiple runs of the emulator. Spatial Location and Grain Global landmasses, at 1° × 1°. Time Period and Grain Last 5 Myr at 1000 year resolution. Major Taxa and Level of Measurement Not applicable. Software Format Tab‐delimited text files and accompanying R code to derive bioclimatic variables.

Recombinant equine FSH superovulation in the mare - Patrick M McCue; Emily M May; Brittany T Middlebrooks; Janet F Roser; Pablo J Ross; Edward L Squires (Journal of Equine Veterinary Science, 2023)

Corrigendum to “A functional size-spectrum model of the global marine ecosystem that resolves zooplankton composition”, Ecological Modelling, 2020, 435: 109265 - Ryan F. Heneghan; Jason D. Everett; Patrick Sykes; Sonia D. Batten; Martin Edwards; Kunio Takahashi; Iain M. Suthers; Julia L. Blanchard; Anthony J. Richardson (Ecological Modelling, 2023)

Mechanistic inference of the metabolic rates underlying $$^{13}$$C breath test curves - Andrew F. Brouwer; Gwenyth O. Lee; Robert J. Schillinger; Christine A. Edwards; Hannah Van Wyk; Roger Yazbeck; Douglas J. Morrison (Journal of Pharmacokinetics and Pharmacodynamics, 2023)

SIPN South: six years of coordinated seasonal Antarctic sea ice predictions - François Massonnet; Sandra Barreira; Antoine Barthélemy; Roberto Bilbao; Edward Blanchard-Wrigglesworth; Ed Blockley; David H. Bromwich; Mitchell Bushuk; Xiaoran Dong; Helge F. Goessling; Will Hobbs; Doroteaciro Iovino; et al. (Frontiers in Marine Science, 2023)
Antarctic sea ice prediction has garnered increasing attention in recent years, particularly in the context of the recent record lows of February 2022 and 2023. As Antarctica becomes a climate change hotspot, as polar tourism booms, and as scientific expeditions continue to explore this remote continent, the capacity to anticipate sea ice conditions weeks to months in advance is in increasing demand. Spurred by recent studies that uncovered physical mechanisms of Antarctic sea ice predictability and by the intriguing large variations of the observed sea ice extent in recent years, the Sea Ice Prediction Network South (SIPN South) project was initiated in 2017, building upon the Arctic Sea Ice Prediction Network. The SIPN South project annually coordinates spring-to-summer predictions of Antarctic sea ice conditions, to allow robust evaluation and intercomparison, and to guide future development in polar prediction systems. In this paper, we present and discuss the initial SIPN South results collected over six summer seasons (December-February 2017-2018 to 2022-2023). We use data from 22 unique contributors spanning five continents that have together delivered more than 3000 individual forecasts of sea ice area and concentration. The SIPN South median forecast of the circumpolar sea ice area captures the sign of the recent negative anomalies, and the verifying observations are systematically included in the 10-90% range of the forecast distribution. These statements also hold at the regional level except in the Ross Sea where the systematic biases and the ensemble spread are the largest. A notable finding is that the group forecast, constructed by aggregating the data provided by each contributor, outperforms most of the individual forecasts, both at the circumpolar and regional levels. This indicates the value of combining predictions to average out model-specific errors. Finally, we find that dynamical model predictions (i.e., based on process-based general circulation models) generally perform worse than statistical model predictions (i.e., data-driven empirical models including machine learning) in representing the regional variability of sea ice concentration in summer. SIPN South is a collaborative community project that is hosted on a shared public repository. The forecast and verification data used in SIPN South are publicly available in near-real time for further use by the polar research community, and eventually, policymakers.

Uranus ring occultation observations: 1977–2006 - Richard G. French; Colleen A. McGhee-French; Mitchell Gordon; Richard L. Baron; Amanda S. Bosh; Marc W. Buie; Nancy Chanover; Mary Ann Clark; Edward W. Dunham; Linda M. French; Ian S. Glass; Jay D. Goguen; et al. (Icarus, 2023)

Updated guidelines for gene nomenclature in wheat - S. A. Boden; R. A. McIntosh; C. Uauy; S. G. Krattinger; J. Dubcovsky; W. J. Rogers; X. C. Xia; E. D. Badaeva; A. R. Bentley; G. Brown-Guedira; M. Caccamo; L. Cattivelli; et al. (Theoretical and Applied Genetics, 2023)
Key message Here, we provide an updated set of guidelines for naming genes in wheat that has been endorsed by the wheat research community. Abstract The last decade has seen a proliferation in genomic resources for wheat, including reference- and pan-genome assemblies with gene annotations, which provide new opportunities to detect, characterise, and describe genes that influence traits of interest. The expansion of genetic information has supported growth of the wheat research community and catalysed strong interest in the genes that control agronomically important traits, such as yield, pathogen resistance, grain quality, and abiotic stress tolerance. To accommodate these developments, we present an updated set of guidelines for gene nomenclature in wheat. These guidelines can be used to describe loci identified based on morphological or phenotypic features or to name genes based on sequence information, such as similarity to genes characterised in other species or the biochemical properties of the encoded protein. The updated guidelines provide a flexible system that is not overly prescriptive but provides structure and a common framework for naming genes in wheat, which may be extended to related cereal species. We propose these guidelines be used henceforth by the wheat research community to facilitate integration of data from independent studies and allow broader and more efficient use of text and data mining approaches, which will ultimately help further accelerate wheat research and breeding.

Contractile Adaptation of the Left Ventricle Post-myocardial Infarction: Predictions by Rodent-Specific Computational Modeling - Emilio A. Mendiola; Sunder Neelakantan; Qian Xiang; Samer Merchant; Ke Li; Edward W. Hsu; Richard A. F. Dixon; Peter Vanderslice; Reza Avazmohammadi (Annals of Biomedical Engineering, 2023)

Ingestion kinetics of mixotrophic and heterotrophic flagellates - Kyle F. Edwards; Qian Li; Grieg F. Steward (Limnology and Oceanography, 2023)
In sunlit waters, significant predation is performed by unicellular, phagotrophic mixotrophs, that is, predators that also possess plastids. The success of a mixotrophic lifestyle will depend in part on how well mixotrophs acquire prey relative to specialized heterotrophs. Likewise, consequences of mixotrophy for productivity and element cycling will depend on the rate and efficiency at which mixotrophs consume prey biomass relative to heterotrophs. However, trait differences between mixotrophs and heterotrophs are not well characterized. In addition, cell size of mixotrophs varies widely, and constitutive mixotrophs include small flagellates deriving from diverse taxa, while larger species are primarily dinoflagellates. To determine whether similar constraints apply to phagotrophs across this broad range of size and taxa, we compiled 83 measurements of flagellate functional responses and compared maximum clearance rates ( C max ) and maximum ingestion rates ( I max ) between trophic modes. We found that the average mixotroph has a 3.7‐fold lower C max and 7.8‐fold lower I max than the average heterotroph, after controlling for cell size. The smaller penalty for C max suggests that relative fitness of mixotrophs will be enhanced under dilute prey concentrations that are common in pelagic ecosystems. We also find that growth efficiency is greater for mixotrophs and for flagellates with lower C max , indicating a spectrum of trophic strategies that may be driven by phototrophy vs. phagotrophy allocation as well as fast vs. slow metabolic variation. Allometric scaling shows that I max is constrained by a common relationship among dinoflagellates and other taxa, but dinoflagellates achieve a greater volume‐specific C max . These results should aid in interpreting protistan communities and modeling mixotrophy.

The effects of resistance exercise on appetite sensations, appetite related hormones and energy intake in hormone receptor-positive breast cancer survivors - Sarah A. Purcell; Edward L. Melanson; Anosheh Afghahi; Virginia F. Borges; Isabella Sinelli; Marc-Andre Cornier (Appetite, 2023)

Coexisting Strombolian and Hawaiian activity during the 2018 fissure eruption of Kīlauea – Implications for processes of weak explosions - Brett Halsey Walker; Bruce F. Houghton; Edward W. Llewellin (Journal of Volcanology and Geothermal Research, 2023)

Freshwater Flow Affects Subsidies of a Copepod (Pseudodiaptomus forbesi) to Low-Salinity Food Webs in the Upper San Francisco Estuary - Jason L. Hassrick; Josh Korman; Wim J. Kimmerer; Edward S. Gross; Lenny F. Grimaldo; Calvin Lee; Andrew A. Schultz (Estuaries and Coasts, 2023)
Productivity of the food web supporting small pelagic fishes in the upper San Francisco Estuary is chronically low, and some of the native fish species are in a long-term decline. The low-salinity (oligohaline) zone (LSZ) is particularly depauperate in phytoplankton and zooplankton. Based on prior empirical studies, it is hypothesized that freshwater flow increases the subsidy of a key copepod prey species ( Pseudodiaptomus forbesi ) from its freshwater population center into the LSZ. We combined hydrodynamic and particle-tracking modeling with Bayesian analysis in a box-model approach to estimate the magnitude of this subsidy and its dependence on freshwater flow rates. Net gains of P. forbesi into the LSZ came mostly from freshwater, landward regions of higher copepod abundance. The subsidy increased with freshwater flow, a finding that supports previous empirical analyses. However, in the context of persistent drought and ongoing climate change, the levels required to achieve a detectable net gain may be difficult and costly to achieve.

Survival of epithelial ovarian cancer in Black women: a society to cell approach in the African American cancer epidemiology study (AACES) - Joellen M. Schildkraut; Courtney Johnson; Lauren F. Dempsey; Bo Qin; Paul Terry; Maxwell Akonde; Edward S. Peters; Hannah Mandle; Michele L. Cote; Lauren Peres; Patricia Moorman; Ann G. Schwartz; et al. (Cancer Causes & Control, 2023)
Purpose The causes for the survival disparity among Black women with epithelial ovarian cancer (EOC) are likely multi-factorial. Here we describe the African American Cancer Epidemiology Study (AACES), the largest cohort of Black women with EOC. Methods AACES phase 2 (enrolled 2020 onward) is a multi-site, population-based study focused on overall survival (OS) of EOC. Rapid case ascertainment is used in ongoing patient recruitment in eight U.S. states, both northern and southern. Data collection is composed of a survey, biospecimens, and medical record abstraction. Results characterizing the survival experience of the phase 1 study population (enrolled 2010–2015) are presented. Results Thus far, ~ 650 patients with EOC have been enrolled in the AACES. The five-year OS of AACES participants approximates those of Black women in the Surveillance Epidemiology and End Results (SEER) registry who survive at least 10-month past diagnosis and is worse compared to white women in SEER, 49 vs. 60%, respectively. A high proportion of women in AACES have low levels of household income (45% < $25,000 annually), education (51% ≤ high school education), and insurance coverage (32% uninsured or Medicaid). Those followed annually differ from those without follow-up with higher levels of localized disease (28 vs 24%) and higher levels of optimal debulking status (73 vs 67%). Conclusion AACES is well positioned to evaluate the contribution of social determinants of health to the poor survival of Black women with EOC and advance understanding of the multi-factorial causes of the ovarian cancer survival disparity in Black women.

Plant phenology drives seasonal changes in shear stress partitioning in a semi-arid rangeland - Nancy P. Ziegler; Nicholas P. Webb; John A. Gillies; Brandon L. Edwards; George Nikolich; Justin W. Van Zee; Brad F. Cooper; Dawn M. Browning; Ericha M. Courtright; Sandra L. LeGrand (Agricultural and Forest Meteorology, 2023)

Vulnerability to climate change of managed stocks in the California Current large marine ecosystem - Michelle M. McClure; Melissa A. Haltuch; Ellen Willis-Norton; David D. Huff; Elliott L. Hazen; Lisa G. Crozier; Michael G. Jacox; Mark W. Nelson; Kelly S. Andrews; Lewis A.K. Barnett; Aaron M. Berger; Sabrina Beyer; et al. (Frontiers in Marine Science, 2023)
Introduction Understanding how abundance, productivity and distribution of individual species may respond to climate change is a critical first step towards anticipating alterations in marine ecosystem structure and function, as well as developing strategies to adapt to the full range of potential changes. Methods This study applies the NOAA (National Oceanic and Atmospheric Administration) Fisheries Climate Vulnerability Assessment method to 64 federally-managed species in the California Current Large Marine Ecosystem to assess their vulnerability to climate change, where vulnerability is a function of a species’ exposure to environmental change and its biological sensitivity to a set of environmental conditions, which includes components of its resiliency and adaptive capacity to respond to these new conditions. Results Overall, two-thirds of the species were judged to have Moderate or greater vulnerability to climate change, and only one species was anticipated to have a positive response. Species classified as Highly or Very Highly vulnerable share one or more characteristics including: 1) having complex life histories that utilize a wide range of freshwater and marine habitats; 2) having habitat specialization, particularly for areas that are likely to experience increased hypoxia; 3) having long lifespans and low population growth rates; and/or 4) being of high commercial value combined with impacts from non-climate stressors such as anthropogenic habitat degradation. Species with Low or Moderate vulnerability are either habitat generalists, occupy deep-water habitats or are highly mobile and likely to shift their ranges. Discussion As climate-related changes intensify, this work provides key information for both scientists and managers as they address the long-term sustainability of fisheries in the region. This information can inform near-term advice for prioritizing species-level data collection and research on climate impacts, help managers to determine when and where a precautionary approach might be warranted, in harvest or other management decisions, and help identify habitats or life history stages that might be especially effective to protect or restore.

Particle radioactivity from radon decay products and reduced pulmonary function among chronic obstructive pulmonary disease patients - Veronica A. Wang; Petros Koutrakis; Longxiang Li; Man Liu; Carolina L.Z. Vieira; Brent A. Coull; Edward F. Maher; Choong-Min Kang; Eric Garshick (Environmental Research, 2023)

Lava-ice interactions during historical eruptions of Veniaminof Volcano, Alaska and the potential for meltwater floods and lahars - Christopher F. Waythomas; Benjamin R. Edwards; Thomas P. Miller; Robert G. McGimsey (Natural Hazards, 2023)
Veniaminof Volcano on the Alaska Peninsula of southwest Alaska is one of a small group of ice-clad volcanoes globally that erupts lava flows in the presence of glacier ice. Here, we describe the nature of lava-ice-snow interactions that have occurred during historical eruptions of the volcano since 1944. Lava flows with total volumes on the order of 0.006 km 3 have been erupted in 1983–1984, 1993–1994, 2013, and 2018. Smaller amounts of lava (1 × 10 −4 km 3 or less) were generated during eruptions in 1944 and 2021. All known historical eruptions have occurred at a 300-m-high cinder cone (informally named cone A) within the 8 × 10-km-diameter ice-filled caldera that characterizes Veniaminof Volcano. Supraglacial lava flows erupted at cone A, resulted in minor amounts of melting and did not lead to any significant outflows of water in nearby drainages. Subglacial effusion of lava in 1983–1984, 2021 and possibly in 1944 and 1993–1994 resulted in more significant melting including a partially water-filled melt pit, about 0.8 km 2 in area, that developed during the 1983–1984 eruption. The 1983–1984 event created an impression that meltwater floods from Mount Veniaminof’s ice-filled caldera could be significant and hazardous given the large amount of glacier ice resident within the caldera (ice volume about 8 km 3 ). To date, no evidence supporting catastrophic outflow of meltwater from lava-ice interactions at cone A has been found. Analysis of imagery from the 1983–1984 eruption shows that the initial phase erupted englacial lavas that melted ice/snow/firn from below, producing surface subsidence outward from the cone with no discernable surface connection to the summit vent on cone A. This also happened during the 2021 eruption, and possibly during the 1993–1994 eruption although meltwater lakes did not form during these events. Thus, historical eruptions at Veniaminof Volcano appear to have two different modes of effusive eruptive behavior, where lava reaches the ice subglacially from flank vents, or where lava flows are erupted subaerially from vents near the summit of cone A and flow down the cone on to the ice surface. When placed in the context of global lava-ice eruptions, in cases where lava flows melt the ice from the surface downward, the main hazards are from localized phreatic explosions as opposed to potential flood/lahar hazards. However, when lava effusion/emplacement occurs beneath the ice surface, melting is more rapid and can produce lakes whose drainage could plausibly produce localized floods and lahars.

Dissolved Organic Carbon Mobilization Across a Climate Transect of Mesic Boreal Forests Is Explained by Air Temperature and Snowpack Duration - Keri L. Bowering; Kate A. Edwards; Yolanda F. Wiersma; Sharon A. Billings; Jamie Warren; Andrea Skinner; Susan E. Ziegler (Ecosystems, 2023)

Sign-oriented Dirichlet Normal Energy: Aligning Dental Topography and Dental Function in the R-package molaR - James D. Pampush; Paul E. Morse; Edward J. Fuselier; Matthew M. Skinner; Richard F. Kay (Journal of Mammalian Evolution, 2022)

State of the California Current Ecosystem in 2021: Winter is coming? - Andrew R. Thompson; Eric P. Bjorkstedt; Steven J. Bograd; Jennifer L. Fisher; Elliott L. Hazen; Andrew Leising; Jarrod A. Santora; Erin V. Satterthwaite; William J. Sydeman; Michaela Alksne; Toby D. Auth; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2022)
In late 2020, models predicted that a strong La Niña would take place for the first time since 2013, and we assessed whether physical and biological indicators in 2021 were similar to past La Niñas in the California Current Ecosystem (CCE). The Pacific Decadal Oscillation and Oceanic Niño Index indeed remained negative throughout 2021; the North Pacific Gyre Oscillation Index, however, remained strongly negative. The seventh largest marine heatwave on record was unexpectedly present from April to the end of 2021; however, similar to past La Niñas, this mass of warm water mostly remained seaward of the continental shelf. As expected from past La Niñas, upwelling and chlorophyll were mostly high and sea surface temperature was low throughout the CCE; however, values were close to average south of Point Conception. Similar to past La Niñas, abundances of lipid-rich, northern copepods off Oregon increased. In northern California, unlike past La Niñas, the body size of North Pacific krill ( Euphausia pacifica ) was close to average. Predictably, overall krill abundance was above average in far northern California but, unexpectedly, below average south of Cape Mendocino. Off Oregon, similar to past La Niñas, larval abundances of three of six coastal species rose, while five of six southern/offshore taxa decreased in 2021. Off California, as expected based on 2020, Northern Anchovy ( Engraulis mordax ) were very abundant, while Pacific Sardine ( Sardinops sagax ) were low. Similar to past La Niñas, market squid ( Doryteuthis opalescens ) and young of the year (YOY) Pacific Hake ( Merluccius pacificus ), YOY sanddabs ( Citharichthys spp.), and YOY rockfishes ( Sebastes spp.) increased. Southern mesopelagic (e.g., Panama lightfish Vinciguerria lucetia , Mexican lampfish Triphoturus mexicanus ) larvae decreased as expected but were still well above average, while northern mesopelagic (e.g., northern lampfish Stenobrachius leucopsarus ) larvae increased but were still below average. In line with predictions, most monitored bird species had above-average reproduction in Oregon and California. California sea lion ( Zalophus californianus ) pup count, growth, and weight were high given the abundant Anchovy forage. The CCE entered an enduring La Niña in 2021, and assessing the responses of various ecosystem components helped articulate aspects of the system that are well understood and those that need further study.

Total Dental Occlusal Area as a Feeding Constraint Feature in Extant Walruses (Odobenus rosmarus), and Implications for the Evolution of Molluscivory in Odobenidae - Win N. F. McLaughlin; Caitlyn J. Boatman; Edward B. Davis; Samantha S. B. Hopkins (Journal of Mammalian Evolution, 2022)

Benthic assemblages are more predictable than fish assemblages at an island scale - Stuart A. Sandin; Esmeralda Alcantar; Randy Clark; Ramón de León; Faisal Dilrosun; Clinton B. Edwards; Andrew J. Estep; Yoan Eynaud; Beverly J. French; Michael D. Fox; Dave Grenda; Scott L. Hamilton; et al. (Coral Reefs, 2022)
Decades of research have revealed relationships between the abundance of coral reef taxa and local conditions, especially at small scales. However, a rigorous test of covariation requires a robust dataset collected across wide environmental or experimental gradients. Here, we surveyed spatial variability in the densities of major coral reef functional groups at 122 sites along a 70 km expanse of the leeward, forereef habitat of Curaçao in the southern Caribbean. These data were used to test the degree to which spatial variability in community composition could be predicted based on assumed functional relationships and site-specific anthropogenic, physical, and ecological conditions. In general, models revealed less power to describe the spatial variability of fish biomass than cover of reef builders (R 2 of best-fit models: 0.25 [fish] and 0.64 [reef builders]). The variability in total benthic cover of reef builders was best described by physical (wave exposure and reef relief) and ecological (turf algal height and coral recruit density) predictors. No metric of anthropogenic pressure was related to spatial variation in reef builder cover. In contrast, total fish biomass showed a consistent (albeit weak) association with anthropogenic predictors (fishing and diving pressure). As is typical of most environmental gradients, the spatial patterns of both fish biomass density and reef builder cover were spatially autocorrelated. Residuals from the best-fit model for fish biomass retained a signature of spatial autocorrelation while the best-fit model for reef builder cover removed spatial autocorrelation, thus reinforcing our finding that environmental predictors were better able to describe the spatial variability of reef builders than that of fish biomass. As we seek to understand spatial variability of coral reef communities at the scale of most management units (i.e., at kilometer- to island-scales), distinct and scale-dependent perspectives will be needed when considering different functional groups.

Giant Tree Frog diversification in West and Central Africa: Isolation by physical barriers, climate, and reproductive traits - Kyle E. Jaynes; Edward A. Myers; Václav Gvoždík; David C. Blackburn; Daniel M. Portik; Eli Greenbaum; Gregory F. M. Jongsma; Mark‐Oliver Rödel; Gabriel Badjedjea; Abraham Bamba‐Kaya; Ninda L. Baptista; Jeannot B. Akuboy; et al. (Molecular Ecology, 2022)
Secondary sympatry amongst sister lineages is strongly associated with genetic and ecological divergence. This pattern suggests that for closely related species to coexist in secondary sympatry, they must accumulate differences in traits that mediate ecological and/or reproductive isolation. Here, we characterized inter‐ and intraspecific divergence in three giant tree frog species whose distributions stretch across West and Central Africa. Using genome‐wide single‐nucleotide polymorphism data, we demonstrated that species‐level divergence coincides temporally and geographically with a period of large‐scale forest fragmentation during the late Pliocene. Our environmental niche models further supported a dynamic history of climatic suitability and stability, and indicated that all three species occupy distinct environmental niches. We found modest morphological differentiation amongst the species with significant divergence in tympanum diameter and male advertisement call. In addition, we confirmed that two species occur in secondary sympatry in Central Africa but found no evidence of hybridization. These patterns support the hypothesis that cycles of genetic exchange and isolation across West and Central Africa have contributed to globally significant biodiversity. Furthermore, divergence in both ecology and reproductive traits appear to have played important roles in maintaining distinct lineages. At the intraspecific level, we found that climatic refugia, precipitation gradients, marine incursions, and potentially riverine barriers generated phylogeographic structure throughout the Pleistocene and into the Holocene. Further studies examining phenotypic divergence and secondary contact amongst these geographically structured populations may demonstrate how smaller scale and more recent biogeographic barriers contribute to regional diversification.

A remote sensing-based classification approach for river mouths of the Amazon-influenced Guianas coast - Antoine Gardel; Edward J. Anthony; Valdenira F. Santos; Nicolas Huybrechts; Sandric Lesourd; Aldo Sottolichio; Tanguy Maury (Regional Environmental Change, 2022)
The mouths of the rivers on the 1500-km-long Guianas coast, South America, are strongly influenced by large mud banks migrating alongshore from the Amazon River. To probe this influence, a river-mouth morphological classification scheme was carried out from satellite images, complemented by data from rare previous studies of estuarine hydrodynamics. The classification highlights a variety of morphological and dynamic river-mouth types that are further influenced by both fluvial water discharge and fluvial catchment rock type. Three basic types are identified: (1) river mouths diverted westward by capes and spits built from multi-decadal to multi-millennial accumulation of mud supplied by the Amazon; among these, mouths close to the Amazon are fixed by bedrock surrounded by mud; (2) small river mouths in French Guiana fixed by outcrops of Precambrian rocks that form headlands devoid of Amazon mud; and (3) large river mouths characterized by high water discharge that imparts an orientation normal to the coast; the largest two belonging to this type (the Essequibo in Guyana and the Maroni on the border between French Guiana and Suriname) exhibit infilled mouths that are transitioning towards deltas. These river mouths show a tropical seasonal estuarine circulation regime strongly influenced by Amazon mud. The influence of mud from the distant Amazon constitutes a unique aspect of the river mouths on the Guianas coast. Field and modelling studies in the future will be needed in order to achieve better characterization of the influence of Amazon mud on the estuarine circulation systems and of the distribution of sediment types within these river mouths, including sand supplied by the rivers.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Wildfire, Smoke Exposure, Human Health, and Environmental Justice Need to be Integrated into Forest Restoration and Management - Savannah M. D’Evelyn; Jihoon Jung; Ernesto Alvarado; Jill Baumgartner; Pete Caligiuri; R. Keala Hagmann; Sarah B. Henderson; Paul F. Hessburg; Sean Hopkins; Edward J. Kasner; Meg A. Krawchuk; Jennifer E. Krenz; et al. (Current Environmental Health Reports, 2022)
Purpose of Review Increasing wildfire size and severity across the western United States has created an environmental and social crisis that must be approached from a transdisciplinary perspective. Climate change and more than a century of fire exclusion and wildfire suppression have led to contemporary wildfires with more severe environmental impacts and human smoke exposure. Wildfires increase smoke exposure for broad swaths of the US population, though outdoor workers and socially disadvantaged groups with limited adaptive capacity can be disproportionally exposed. Exposure to wildfire smoke is associated with a range of health impacts in children and adults, including exacerbation of existing respiratory diseases such as asthma and chronic obstructive pulmonary disease, worse birth outcomes, and cardiovascular events. Seasonally dry forests in Washington, Oregon, and California can benefit from ecological restoration as a way to adapt forests to climate change and reduce smoke impacts on affected communities. Recent Findings Each wildfire season, large smoke events, and their adverse impacts on human health receive considerable attention from both the public and policymakers. The severity of recent wildfire seasons has state and federal governments outlining budgets and prioritizing policies to combat the worsening crisis. This surging attention provides an opportunity to outline the actions needed now to advance research and practice on conservation, economic, environmental justice, and public health interests, as well as the trade-offs that must be considered. Summary Scientists, planners, foresters and fire managers, fire safety, air quality, and public health practitioners must collaboratively work together. This article is the result of a series of transdisciplinary conversations to find common ground and subsequently provide a holistic view of how forest and fire management intersect with human health through the impacts of smoke and articulate the need for an integrated approach to both planning and practice.

Use of a 360-Degree Underwater Camera to Characterize Artificial Reef and Fish Aggregating Effects around Marine Energy Devices - Lenaïg G. Hemery; Kailan F. Mackereth; Cailene M. Gunn; Edward B. Pablo (Journal of Marine Science and Engineering, 2022)
Marine energy devices must be attached to the seafloor by their foundations, pilings, or anchors, and will have other parts in the water column like the devices themselves, mooring lines, and power export cables running along the seafloor. The installation and presence of these artificial structures will create physical changes that can disrupt or create new habitats, and potentially alter the behavior of mobile organisms such as fish around a device by attracting them to these new artificial reefs and fish aggregating devices. In this study, we tested a new approach for monitoring fish activity around a marine energy device anchor: a 360-degree underwater camera to keep the target (a wave energy converter’s anchor) in the field of view of the camera. The camera was deployed in three configurations (hand-held, tripod, video lander) at sites with different hydrodynamics and underwater visibilities. The video lander was the best configuration: very stable, versatile, and easy to handle. The 360-degree field of view enabled observing and counting fishes, which were more abundant at dusk than dawn or noon, around the anchor. Despite remaining challenges, 360-degree cameras are useful tools for monitoring animal interactions with marine energy devices.

Using structured decision making to guide habitat restoration for butterflies: a case study of Oregon silverspots - Cassandra F. Doll; Sarah J. Converse; Collin B. Edwards; Cheryl B. Schultz (Journal of Insect Conservation, 2022)

Corrigendum: State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2022)

A National Status Report on United States Coral Reefs Based on 2012–2018 Data From National Oceanic and Atmospheric Administration’s National Coral Reef Monitoring Program - Erica K. Towle; E. Caroline Donovan; Heath Kelsey; Mary E. Allen; Hannah Barkley; Jeremiah Blondeau; Russell E. Brainard; Annie Carew; Courtney S. Couch; Maria K. Dillard; C. Mark Eakin; Kimberly Edwards; et al. (Frontiers in Marine Science, 2022)
National Oceanic and Atmospheric Administration’s Coral Reef Conservation Program supports the National Coral Reef Monitoring Program (NCRMP) in the United States Pacific, Atlantic, Caribbean, and Gulf of Mexico. NCRMP conducts standardized observations of biological, climatic, and socioeconomic indicators across American Samoa, Guam, the Main Hawaiian Islands, the Northwestern Hawaiian Islands, the Northern Mariana Islands, the Pacific Remote Islands, Florida, the Flower Garden Banks, Puerto Rico, and the United States Virgin Islands. NCRMP provides periodic, national-level assessments of the status of United States coral reef ecosystems and communities connected to them. In 2014, NCRMP partnered with the University of Maryland Center for Environmental Science on an unprecedented collaboration between federal and jurisdictional/state agencies, academia, and non-governmental organizations to synthesize NCRMP data into a reporting format designed to be accessible and relevant to the public and policy makers. The process involved multi-year data analyses of key benthic, fish, and climate indicators. In populated jurisdictions, socioeconomic data were integrated to assess public support for management actions, participation in pro-environmental behaviors, and awareness of threats to coral reefs. Jurisdictions were scored using a report-card scale (0–100%) by establishing references for each indicator using best-available historical data or expert opinion where historical data did not exist or were not statistically comparable. Despite overall ecosystem scores of Fair for all combined Atlantic (70%) and Pacific (74%) jurisdictions, the current trend is downward with a majority of United States coral reefs declining and vulnerable to further degradation. Remote, uninhabited reefs had an advantage with respect to reef fish population scores, i.e., Flower Garden Banks (85%) and Pacific Remote Islands (93%), when compared to populated location scores, i.e., Puerto Rico (63%) and Main Hawaiian Islands (66%). All coral reefs are highly impacted by climate change, and climate impacts were more pronounced than expected on remote reefs, i.e., the Northwestern Hawaiian Islands (58%). Presenting results in a report-card style facilitates communication to the public and policy makers, and provides a useful mechanism to garner support for management actions such as expanding protected areas; enforcing existing regulations; increasing climate change education; reducing land-based sources of pollution; and other actions to improve the trajectory of coral reef ecosystem conditions.

Using groundwater noble gas measurements to confirm paleorecharge hypotheses at Pahute Mesa, Nevada National Security Site, Nevada, USA - Ate Visser; Edward Kwicklis; Irene Farnham; Andrew F. B. Tompson; Ronald L. Hershey (Hydrogeology Journal, 2022)

Genomic predictors of testosterone levels are associated with muscle fiber size and strength - João Paulo L. F. Guilherme; Ekaterina A. Semenova; Oleg V. Borisov; Andrey K. Larin; Ethan Moreland; Edward V. Generozov; Ildus I. Ahmetov (European Journal of Applied Physiology, 2022)
Purpose Circulating testosterone levels are a heritable trait with anabolic properties in various tissues, including skeletal muscle. So far, hundreds of single nucleotide polymorphisms (SNPs) associated with testosterone levels have been identified in nonathletic populations. The aim of the present study was to test the association of 822 testosterone-increasing SNPs with muscle-related traits (muscle fiber size, fat-free mass and handgrip strength) and to validate the identified SNPs in independent cohorts of strength and power athletes. Methods One hundred and forty-eight physically active individuals (47 females, 101 males) were assessed for cross-sectional area (CSA) of fast-twitch muscle fibers. Significant SNPs were further assessed for fat-free mass and handgrip strength in > 354,000 participants from the UK Biobank cohort. The validation cohorts included Russian elite athletes. Results From an initial panel of 822 SNPs, we identified five testosterone-increasing alleles ( DOCK3 rs77031559 G, ESR1 rs190930099 G, GLIS3 rs34706136 TG, GRAMD1B rs850294 T, TRAIP rs62260729 C) nominally associated ( P < 0.05) with CSA of fast-twitch muscle fibers, fat-free mass and handgrip strength. Based on these five SNPs, the number of testosterone-increasing alleles was positively associated with testosterone levels in male athletes ( P = 0.048) and greater strength performance in weightlifters ( P = 0.017). Moreover, the proportion of participants with ≥ 2 testosterone-increasing alleles was higher in power athletes compared to controls (68.9 vs. 55.6%; P = 0.012). Conclusion Testosterone-related SNPs are associated with muscle fiber size, fat-free mass and strength, which combined can partially contribute to a greater predisposition to strength/power sports.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

In Memoriam: John Allan Hobson (1933–2021) - Edward F. Pace-Schott; Robert Stickgold (Sleep and Vigilance, 2021)

Effects of oil palm and human presence on activity patterns of terrestrial mammals in the Colombian Llanos - Lain E. Pardo; William Edwards; Mason J. Campbell; Bibiana Gómez-Valencia; Gopalasamy Reuben Clements; William F. Laurance (Mammalian Biology, 2021)
The ability of animals to adjust their behaviour can influence how they respond to environmental changes and human presence. We quantified activity patterns of terrestrial mammals in oil palm plantations and native riparian forest in Colombia to determine if species exhibited behavioural changes depending on the type of habitat and the presence of humans. Despite the large sampling effort (12,403 camera-days), we were only able to examine the activity patterns of ten species in riparian forests and seven species in oil palm plantations, with four species (capybara, giant anteater, lesser anteater and common opossum) being represented by enough records (i.e. n > 20) in both oil palm and forest to allow robust comparisons. Only capybaras showed an apparent change in activity patterns between oil palm plantations and riparian forests, shifting from being crepuscular in forest to predominantly nocturnal inside oil palm plantations. Further, capybaras, giant anteaters and white-tailed deer appeared to modify their activities to avoid human presence inside oil palm plantations by increasing nocturnality (temporal overlap $$\widehat{\Delta }$$ Δ ^ ranged from 0.13 to 0.36), whereas jaguarundi had high overlap with human activities [ $$\widehat{\Delta }$$ Δ ^ =0.85 (0.61–0.90)]. Species pair-wise analysis within oil palm revealed evidence for temporal segregation between species occupying the same trophic position (e.g. foxes and jaguarundi), whereas some predators and their prey (e.g. ocelots and armadillos) had high overlaps in temporal activity patterns as might be expected. Our findings shed light on the potential behavioural adaptation of mammals to anthropogenic landscapes, a feature not captured in traditional studies that focus on measures such as species richness or abundance.

Automated Framework for the Inclusion of a His–Purkinje System in Cardiac Digital Twins of Ventricular Electrophysiology - Karli Gillette; Matthias A. F. Gsell; Julien Bouyssier; Anton J. Prassl; Aurel Neic; Edward J. Vigmond; Gernot Plank (Annals of Biomedical Engineering, 2021)
Personalized models of cardiac electrophysiology (EP) that match clinical observation with high fidelity, referred to as cardiac digital twins (CDTs), show promise as a tool for tailoring cardiac precision therapies. Building CDTs of cardiac EP relies on the ability of models to replicate the ventricular activation sequence under a broad range of conditions. Of pivotal importance is the His–Purkinje system (HPS) within the ventricles. Workflows for the generation and incorporation of HPS models are needed for use in cardiac digital twinning pipelines that aim to minimize the misfit between model predictions and clinical data such as the 12 lead electrocardiogram (ECG). We thus develop an automated two stage approach for HPS personalization. A fascicular-based model is first introduced that modulates the endocardial Purkinje network. Only emergent features of sites of earliest activation within the ventricular myocardium and a fast-conducting sub-endocardial layer are accounted for. It is then replaced by a topologically realistic Purkinje-based representation of the HPS. Feasibility of the approach is demonstrated. Equivalence between both HPS model representations is investigated by comparing activation patterns and 12 lead ECGs under both sinus rhythm and right-ventricular apical pacing. Predominant ECG morphology is preserved by both HPS models under sinus conditions, but elucidates differences during pacing.

Stratification strength and light climate explain variation in chlorophyll a at the continental scale in a European multilake survey in a heatwave summer - Daphne Donis; Evanthia Mantzouki; Daniel F. McGinnis; Dominic Vachon; Irene Gallego; Hans‐Peter Grossart; Lisette N. de Senerpont Domis; Sven Teurlincx; Laura Seelen; Miquel Lürling; Yvon Verstijnen; Valentini Maliaka; et al. (Limnology and Oceanography, 2021)
To determine the drivers of phytoplankton biomass, we collected standardized morphometric, physical, and biological data in 230 lakes across the Mediterranean, Continental, and Boreal climatic zones of the European continent. Multilinear regression models tested on this snapshot of mostly eutrophic lakes (median total phosphorus [TP] = 0.06 and total nitrogen [TN] = 0.7 mg L −1 ), and its subsets (2 depth types and 3 climatic zones), show that light climate and stratification strength were the most significant explanatory variables for chlorophyll a (Chl a ) variance. TN was a significant predictor for phytoplankton biomass for shallow and continental lakes, while TP never appeared as an explanatory variable, suggesting that under high TP, light, which partially controls stratification strength, becomes limiting for phytoplankton development. Mediterranean lakes were the warmest yet most weakly stratified and had significantly less Chl a than Boreal lakes, where the temperature anomaly from the long‐term average, during a summer heatwave was the highest (+4°C) and showed a significant, exponential relationship with stratification strength. This European survey represents a summer snapshot of phytoplankton biomass and its drivers, and lends support that light and stratification metrics, which are both affected by climate change, are better predictors for phytoplankton biomass in nutrient‐rich lakes than nutrient concentrations and surface temperature.

Toward trait‐based food webs: Universal traits and trait matching in planktonic predator–prey and host–parasite relationships - Elena Litchman; Kyle F. Edwards; Philip W. Boyd (Limnology and Oceanography, 2021)
There is a growing consensus that traits offer a powerful way to examine the relationship between the environment, organismal strategies, species interactions, and ecological success. To date, trait‐based research has largely been focusing on individual trophic levels and not on cross‐level interactions. Looking at traits not only within but across trophic levels and identifying traits that together define trophic interactions holds a great potential for understanding the mechanisms of interactions. Here, we outline the conceptual foundation for cross‐trophic trait‐based frameworks, using planktonic food webs as an example. First, we compile a list of traits important within different individual trophic levels and show that there are traits that are common across trophic levels (“universal” traits), as well as trophic level‐specific traits. Next, we focus on traits that characterize interactions across trophic levels, focusing on two types of interaction—grazer–primary producer and host–parasite, identifying the similarities and differences between these interactions. We outline the trait hierarchies that define possible and realized intertrophic interactions and their strengths. We then highlight the importance of trade‐offs among those traits in shaping interactions and explaining general patterns in the structure and function of food webs. Finally, we discuss the environmental influences on traits, their eco‐evolutionary responses to changing conditions and how those responses may alter trophic interactions. The extension of trait‐based approaches from individual trophic levels to food webs and different trophic interactions should stimulate further conceptual development, enrich the field of aquatic sciences, and provide a framework to better predict global change effects on ecosystems.

Saltmarsh Resilience to Periodic Shifts in Tidal Channels - Cai John Tomos Ladd; Mollie Frances Duggan-Edwards; Jordi F. Pagès; Martin Wiggers Skov (Frontiers in Marine Science, 2021)
Resilience of coastal ecosystems to climate change is largely determined by the interaction between plants and the surrounding tidal environment. Research has tended to focus on processes operating at the local scale to explain resilience mechanisms, overlooking potentially important landscape-scale processes and patterns. We show from aerial images spanning 67 years across 3 estuaries that saltmarsh loss was compensated by expansion elsewhere in the estuary when tidal channels shifted position. Compensatory expansion rates were as high as 6 m/yr. This phenomenon of “geomorphic compensation” represents a hitherto overlooked large-scale self-organizing pattern that facilitates the long-term persistence of marshes in estuaries. The geomorphic compensation pattern likely also occurs in other hydrological systems including mangrove forests, and seagrass meadows, and river islands. Compensatory erosion-expansion patterns occurred at the same time as net marsh extent increased by between 120 and 235% across all three estuaries. Marsh expansion mostly occurred in the lower parts of each estuary, where channel migration and compensatory expansion was less evident. Patterns of geomorphic compensation therefore appear to operate at discrete spatio-temporal scales, nested within a hierarchy of coastal morphodynamic processes that govern longer-term patterns of either net marsh gain or loss. Coastal ecosystem resilience can therefore only be fully appreciated when examining erosion and expansion patterns at both local and landscape scales. The intrinsic dynamics of marshes described here have important implications for the long-term delivery of ecosystem services.

Megadroughts and pluvials in southwest Australia: 1350–2017 CE - Alison J. O’Donnell; W. Lachlan McCaw; Edward R. Cook; Pauline F. Grierson (Climate Dynamics, 2021)
Declining winter rainfall coupled with recent prolonged drought poses significant risks to water resources and agriculture across southern Australia. While rainfall declines over recent decades are largely consistent with modelled climate change scenarios, particularly for southwest Australia, the significance of these declines is yet to be assessed within the context of long-term hydroclimatic variability. Here, we present a new 668-year (1350–2017 CE) tree-ring reconstruction of autumn–winter rainfall over inland southwest Australia. This record reveals that a recent decline in rainfall over inland southwest Australia (since 2000 CE) is not unusual in terms of either magnitude or duration relative to rainfall variability over the last seven centuries. Drought periods of greater magnitude and duration than those in the instrumental record occurred prior to 1900 CE, including two ‘megadroughts’ of > 30 years duration in the eighteenth and nineteenth centuries. By contrast, the wettest > decadal periods of the last seven centuries occurred after 1900 CE, making the twentieth century the wettest of the last seven centuries. We conclude that the instrumental rainfall record (since ~ 1900 CE) does not capture the full scale of natural hydroclimatic variability for inland southwest Australia and that the risk of prolonged droughts in the region is likely much higher than currently estimated.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Development and anatomical traits of black pine on an abandoned agricultural land compared to forested areas - Ferhat Kara; Seray Özden Keleş; Edward F. Loewenstein (Environmental Monitoring and Assessment, 2021)

Healthy Aging Requires a Healthy Home Care Workforce: the Occupational Safety and Health of Home Care Aides - M. M. Quinn; P. K. Markkanen; C. J. Galligan; S. R. Sama; J. E. Lindberg; M. F. Edwards (Current Environmental Health Reports, 2021)
Purpose of Review To identify important home care (HC) aide occupational safety and health (OSH) hazards and examine how addressing these can improve aide health and the delivery of HC services overall. Specifically, this review seeks to answer: Why is HC aide OSH important? What are the most significant OSH challenges? How can improving HC aide OSH also improve the safety and health of their clients? What implications do the findings have for future research? Recent Findings HC is one of the fastest growing US industries. Aides comprise its largest workforce and are increasingly needed to care for the rapidly aging population. There is an aide shortage due in part to instabilities in HC work organization and to serious job-specific hazards, resulting in aides losing work time. Recent social, economic, and technological factors are rapidly changing the nature of HC work, creating OSH hazards similar to those found in nursing homes. At the same time, aides are experiencing social and economic inequities that increase their vulnerability to OSH hazards. These hazards are also a burden on employers who are challenged to recruit, retain, and train aides. OSH injuries and illness interrupt the continuity of care delivery to clients. Many OSH hazards also put HC clients and families at risk. Summary A new framework and methodologies are needed to assess aide and client safety together in order to guide future HC research, policies, and practices. Government, industry, and labor commitment is needed to fund and coordinate a comprehensive, multidisciplinary research program.

Association between weight cycling and risk of kidney cancer: a prospective cohort study and meta-analysis of observational studies - Dong Hoon Lee; NaNa Keum; Leandro F. M. Rezende; Fred K. Tabung; SungEun Hong; Edward L. Giovannucci (Cancer Causes & Control, 2021)

Statistical upscaling of ecosystem CO 2 fluxes across the terrestrial tundra and boreal domain: Regional patterns and uncertainties - Anna‐Maria Virkkala; Juha Aalto; Brendan M. Rogers; Torbern Tagesson; Claire C. Treat; Susan M. Natali; Jennifer D. Watts; Stefano Potter; Aleksi Lehtonen; Marguerite Mauritz; Edward A. G. Schuur; John Kochendorfer; et al. (Global Change Biology, 2021)
The regional variability in tundra and boreal carbon dioxide (CO 2 ) fluxes can be high, complicating efforts to quantify sink‐source patterns across the entire region. Statistical models are increasingly used to predict (i.e., upscale) CO 2 fluxes across large spatial domains, but the reliability of different modeling techniques, each with different specifications and assumptions, has not been assessed in detail. Here, we compile eddy covariance and chamber measurements of annual and growing season CO 2 fluxes of gross primary productivity (GPP), ecosystem respiration (ER), and net ecosystem exchange (NEE) during 1990–2015 from 148 terrestrial high‐latitude (i.e., tundra and boreal) sites to analyze the spatial patterns and drivers of CO 2 fluxes and test the accuracy and uncertainty of different statistical models. CO 2 fluxes were upscaled at relatively high spatial resolution (1 km 2 ) across the high‐latitude region using five commonly used statistical models and their ensemble, that is, the median of all five models, using climatic, vegetation, and soil predictors. We found the performance of machine learning and ensemble predictions to outperform traditional regression methods. We also found the predictive performance of NEE‐focused models to be low, relative to models predicting GPP and ER. Our data compilation and ensemble predictions showed that CO 2 sink strength was larger in the boreal biome (observed and predicted average annual NEE −46 and −29 g C m −2 yr −1 , respectively) compared to tundra (average annual NEE +10 and −2 g C m −2 yr −1 ). This pattern was associated with large spatial variability, reflecting local heterogeneity in soil organic carbon stocks, climate, and vegetation productivity. The terrestrial ecosystem CO 2 budget, estimated using the annual NEE ensemble prediction, suggests the high‐latitude region was on average an annual CO 2 sink during 1990–2015, although uncertainty remains high.

State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2021)
The California Current System (CCS) has experienced large fluctuations in environmental conditions in recent years that have dramatically affected the biological community. Here we synthesize remotely sensed, hydrographic, and biological survey data from throughout the CCS in 2019–2020 to evaluate how recent changes in environmental conditions have affected community dynamics at multiple trophic levels. A marine heatwave formed in the north Pacific in 2019 and reached the second greatest area ever recorded by the end of summer 2020. However, high atmospheric pressure in early 2020 drove relatively strong Ekman-driven coastal upwelling in the northern portion of the CCS and warm temperature anomalies remained far offshore. Upwelling and cooler temperatures in the northern CCS created relatively productive conditions in which the biomass of lipid-rich copepod species increased, adult krill size increased, and several seabird species experienced positive reproductive success. Despite these conditions, the composition of the fish community in the northern CCS remained a mixture of both warm- and cool-water-associated species. In the southern CCS, ocean temperatures remained above average for the seventh consecutive year. Abundances of juvenile fish species associated with productive conditions were relatively low, and the ichthyoplankton community was dominated by a mixture of oceanic warm-water and cosmopolitan species. Seabird species associated with warm water also occurred at greater densities than cool-water species in the southern CCS. The population of northern anchovy, which has been resurgent since 2017, continued to provide an important forage base for piscivorous fishes, offshore colonies of seabirds, and marine mammals throughout the CCS. Coastal upwelling in the north, and a longer-term trend in warming in the south, appeared to be controlling the community to a much greater extent than the marine heatwave itself.

Physiological responses to maximal 4 s sprint interval cycling using inertial loading: the influence of inter-sprint recovery duration - Emre Vardarli; Remzi Satiroglu; Jacob R. Allen; Ryan Bjellquist-Ledger; Heath M. Burton; Edward F. Coyle (European Journal of Applied Physiology, 2021)

Assessment of the efficacy of six field cleaning protocols for hydrocarbon quantification - Emily C. Pisarski; Edward F. Wirth; Paul L. Pennington; Ian Hartwell; Brian S. Shaddrix; David R. Whitall; Dennis A. Apeti; Gregory Baker (Environmental Science and Pollution Research, 2021)

Are visual working memory and episodic memory distinct processes? Insight from stroke patients by lesion-symptom mapping - Selma Lugtmeijer; Linda Geerligs; Frank Erik de Leeuw; Edward H. F. de Haan; Roy P. C. Kessels; Anouk R. Smits; Ben A. Schmand; Edward H. F. de Haan; Frank Erik de Leeuw; Gert jan Luijckx; H. Steven Scholte; Joke M. Spikman; et al. (Brain Structure and Function, 2021)
Working memory and episodic memory are two different processes, although the nature of their interrelationship is debated. As these processes are predominantly studied in isolation, it is unclear whether they crucially rely on different neural substrates. To obtain more insight in this, 81 adults with sub-acute ischemic stroke and 29 elderly controls were assessed on a visual working memory task, followed by a surprise subsequent memory test for the same stimuli. Multivariate, atlas- and track-based lesion-symptom mapping (LSM) analyses were performed to identify anatomical correlates of visual memory. Behavioral results gave moderate evidence for independence between discriminability in working memory and subsequent memory, and strong evidence for a correlation in response bias on the two tasks in stroke patients. LSM analyses suggested there might be independent regions associated with working memory and episodic memory. Lesions in the right arcuate fasciculus were more strongly associated with discriminability in working memory than in subsequent memory, while lesions in the frontal operculum in the right hemisphere were more strongly associated with criterion setting in subsequent memory. These findings support the view that some processes involved in working memory and episodic memory rely on separate mechanisms, while acknowledging that there might also be shared processes.

The Impact of Atmosphere–Ocean–Wave Coupling on the Near-Surface Wind Speed in Forecasts of Extratropical Cyclones - Emanuele S. Gentile; Suzanne L. Gray; Janet F. Barlow; Huw W. Lewis; John M. Edwards (Boundary-Layer Meteorology, 2021)
Accurate modelling of air–sea surface exchanges is crucial for reliable extreme surface wind-speed forecasts. While atmosphere-only weather forecast models represent ocean and wave effects through sea-state independent parametrizations, coupled multi-model systems capture sea-state dynamics by integrating feedbacks between the atmosphere, ocean and wave model components. Here, we investigate the sensitivity of extreme surface wind speeds to air–sea exchanges at the kilometre scale using coupled and uncoupled configurations of the Met Office’s UK Regional Coupled Environmental Prediction system. The case period includes the passage of extra-tropical cyclones Helen, Ali, and Bronagh, which brought maximum gusts of 36 m s $$^{-1}$$ - 1 over the UK. Compared with the atmosphere-only results, coupling to the ocean decreases the domain-average sea-surface temperature by up to 0.5 K. Inclusion of coupling to waves reduce the 98th percentile 10-m wind speed by up to 2 m s $$^{-1}$$ - 1 as young, growing wind waves reduce the wind speed by increasing the sea-surface aerodynamic roughness. Impacts on gusts are more modest, with local reductions of up to 1 m s $$^{-1}$$ - 1 , due to enhanced boundary-layer turbulence which partially offsets air–sea momentum transfer. Using a new drag parametrization based on the Coupled Ocean–Atmosphere Response Experiment 4.0 parametrization, with a cap on the neutral drag coefficient and reduction for wind speeds exceeding 27 m s $$^{-1}$$ - 1 , the atmosphere-only model achieves equivalent impacts on 10-m wind speeds and gusts as from coupling to waves. Overall, the new drag parametrization achieves the same 20% improvement in forecast 10-m wind-speed skill as coupling to waves, with the advantage of saving the computational cost of the ocean and wave models.

The localization of phytohormones within the gall-inducing insect Eurosta solidaginis (Diptera: Tephritidae) - Gabriela E. Ponce; Megumi Fuse; Annette Chan; Edward F. Connor (Arthropod-Plant Interactions, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Exploring the Pacific Arctic Seasonal Ice Zone With Saildrone USVs - Andrew M. Chiodi; Chidong Zhang; Edward D. Cokelet; Qiong Yang; Calvin W. Mordy; Chelle L. Gentemann; Jessica N. Cross; Noah Lawrence-Slavas; Christian Meinig; Michael Steele; Don E. Harrison; Phyllis J. Stabeno; et al. (Frontiers in Marine Science, 2021)
More high-quality, in situ observations of essential marine variables are needed over the seasonal ice zone to better understand Arctic (or Antarctic) weather, climate, and ecosystems. To better assess the potential for arrays of uncrewed surface vehicles (USVs) to provide such observations, five wind-driven and solar-powered saildrones were sailed into the Chukchi and Beaufort Seas following the 2019 seasonal retreat of sea ice. They were equipped to observe the surface oceanic and atmospheric variables required to estimate air-sea fluxes of heat, momentum and carbon dioxide. Some of these variables were made available to weather forecast centers in real time. Our objective here is to analyze the effectiveness of existing remote ice navigation products and highlight the challenges and opportunities for improving remote ice navigation strategies with USVs. We examine the sources of navigational sea-ice distribution information based on post-mission tabulation of the sea-ice conditions encountered by the vehicles. The satellite-based ice-concentration analyses consulted during the mission exhibited large disagreements when the sea ice was retreating fastest (e.g., the 10% concentration contours differed between analyses by up to ∼175 km). Attempts to use saildrone observations to detect the ice edge revealed that in situ temperature and salinity measurements varied sufficiently in ice bands and open water that it is difficult to use these variables alone as a reliable ice-edge indicator. Devising robust strategies for remote ice zone navigation may depend on developing the capability to recognize sea ice and initiate navigational maneuvers with cameras and processing capability onboard the vehicles.

The Essentials of Marine Biotechnology - Ana Rotter; Michéle Barbier; Francesco Bertoni; Atle M. Bones; M. Leonor Cancela; Jens Carlsson; Maria F. Carvalho; Marta Cegłowska; Jerónimo Chirivella-Martorell; Meltem Conk Dalay; Mercedes Cueto; Thanos Dailianis; et al. (Frontiers in Marine Science, 2021)
Coastal countries have traditionally relied on the existing marine resources (e.g., fishing, food, transport, recreation, and tourism) as well as tried to support new economic endeavors (ocean energy, desalination for water supply, and seabed mining). Modern societies and lifestyle resulted in an increased demand for dietary diversity, better health and well-being, new biomedicines, natural cosmeceuticals, environmental conservation, and sustainable energy sources. These societal needs stimulated the interest of researchers on the diverse and underexplored marine environments as promising and sustainable sources of biomolecules and biomass, and they are addressed by the emerging field of marine (blue) biotechnology. Blue biotechnology provides opportunities for a wide range of initiatives of commercial interest for the pharmaceutical, biomedical, cosmetic, nutraceutical, food, feed, agricultural, and related industries. This article synthesizes the essence, opportunities, responsibilities, and challenges encountered in marine biotechnology and outlines the attainment and valorization of directly derived or bio-inspired products from marine organisms. First, the concept of bioeconomy is introduced. Then, the diversity of marine bioresources including an overview of the most prominent marine organisms and their potential for biotechnological uses are described. This is followed by introducing methodologies for exploration of these resources and the main use case scenarios in energy, food and feed, agronomy, bioremediation and climate change, cosmeceuticals, bio-inspired materials, healthcare, and well-being sectors. The key aspects in the fields of legislation and funding are provided, with the emphasis on the importance of communication and stakeholder engagement at all levels of biotechnology development. Finally, vital overarching concepts, such as the quadruple helix and Responsible Research and Innovation principle are highlighted as important to follow within the marine biotechnology field. The authors of this review are collaborating under the European Commission-funded Cooperation in Science and Technology (COST) Action Ocean4Biotech – European transdisciplinary networking platform for marine biotechnology and focus the study on the European state of affairs.

Post-Stroke Working Memory Dysfunction: A Meta-Analysis and Systematic Review - Selma Lugtmeijer; Nikki A. Lammers; Edward H. F. de Haan; Frank-Erik de Leeuw; Roy P. C. Kessels (Neuropsychology Review, 2021)
This review investigates the severity and nature of post-stroke working memory deficits with reference to the multi-component model of working memory. We conducted a systematic search in PubMed up to March 2019 with search terms for stroke and memory. Studies on adult stroke patients, that included a control group, and assessed working memory function, were selected. Effect sizes (Hedges’ g ) were extracted from 50 studies (in total 3,084 stroke patients) based on the sample size, mean and standard deviation of patients and controls. Performance of stroke patients was compared to healthy controls on low-load (i.e. capacity) and high-load (executively demanding) working memory tasks, grouped by modality (verbal, non-verbal). A separate analysis compared patients in the sub-acute and the chronic stage. Longitudinal studies and effects of lesion location were systematically reviewed. Stroke patients demonstrated significant deficits in working memory with a moderate effect size for both low-load (Hedges’ g = -.58 [-.82 to -.43]) and high-load (Hedges’ g = -.59 [-.73 to -.45]) tasks. The effect sizes were comparable for verbal and non-verbal material. Systematically reviewing the literature showed that working memory deficits remain prominent in the chronic stage of stroke. Lesions in a widespread fronto-parietal network are associated with working memory deficits. Stroke patients show decrements of moderate magnitude in all subsystems of working memory. This review clearly demonstrates the global nature of the impairment in working memory post-stroke.

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

Lower soil moisture and deep soil temperatures in thermokarst features increase old soil carbon loss after 10 years of experimental permafrost warming - Elaine F. Pegoraro; Marguerite E. Mauritz; Kiona Ogle; Christopher H. Ebert; Edward A. G. Schuur (Global Change Biology, 2021)
Almost half of the global terrestrial soil carbon (C) is stored in the northern circumpolar permafrost region, where air temperatures are increasing two times faster than the global average. As climate warms, permafrost thaws and soil organic matter becomes vulnerable to greater microbial decomposition. Long‐term soil warming of ice‐rich permafrost can result in thermokarst formation that creates variability in environmental conditions. Consequently, plant and microbial proportional contributions to ecosystem respiration may change in response to long‐term soil warming. Natural abundance δ 13 C and Δ 14 C of aboveground and belowground plant material, and of young and old soil respiration were used to inform a mixing model to partition the contribution of each source to ecosystem respiration fluxes. We employed a hierarchical Bayesian approach that incorporated gross primary productivity and environmental drivers to constrain source contributions. We found that long‐term experimental permafrost warming introduced a soil hydrology component that interacted with temperature to affect old soil C respiration. Old soil C loss was suppressed in plots with warmer deep soil temperatures because they tended to be wetter. When soil volumetric water content significantly decreased in 2018 relative to 2016 and 2017, the dominant respiration sources shifted from plant aboveground and young soil respiration to old soil respiration. The proportion of ecosystem respiration from old soil C accounted for up to 39% of ecosystem respiration and represented a 30‐fold increase compared to the wet‐year average. Our findings show that thermokarst formation may act to moderate microbial decomposition of old soil C when soil is highly saturated. However, when soil moisture decreases, a higher proportion of old soil C is vulnerable to decomposition and can become a large flux to the atmosphere. As permafrost systems continue to change with climate, we must understand the thresholds that may propel these systems from a C sink to a source.

Genome‐enabled exploration of microbial ecology and evolution in the sea: a rising tide lifts all boats - Edward F. DeLong (Environmental Microbiology, 2021)
Summary As a young bacteriologist just launching my career during the early days of the ‘microbial revolution’ in the 1980s, I was fortunate to participate in some early discoveries, and collaborate in the development of cross‐disciplinary methods now commonly referred to as "metagenomics". My early scientific career focused on applying phylogenetic and genomic approaches to characterize ‘wild’ bacteria, archaea and viruses in their natural habitats, with an emphasis on marine systems. These central interests have not changed very much for me over the past three decades, but knowledge, methodological advances and new theoretical perspectives about the microbial world certainly have. In this invited ‘How we did it’ perspective, I trace some of the trajectories of my lab's collective efforts over the years, including phylogenetic surveys of microbial assemblages in marine plankton and sediments, development of microbial community gene‐ and genome‐enabled surveys, and application of genome‐guided, cultivation‐independent functional characterization of novel enzymes, pathways and their relationships to in situ biogeochemistry. Throughout this short review, I attempt to acknowledge, all the mentors, students, postdocs and collaborators who enabled this research. Inevitably, a brief autobiographical review like this cannot be fully comprehensive, so sincere apologies to any of my great colleagues who are not explicitly mentioned herein. I salute you all as well!

Are bacterial symbionts associated with gall induction in insects? - Tobin J. Hammer; Rosemarie De Clerck-Floate; John F. Tooker; Peter W. Price; Donald G. Miller; Edward F. Connor (Arthropod-Plant Interactions, 2021)

Multi-stressor Effects of Ultraviolet Light, Temperature, and Salinity on Louisiana Sweet Crude Oil Toxicity in Larval Estuarine Organisms - Marie E. DeLorenzo; Peter B. Key; Katy W. Chung; Kaitlin Aaby; Deanna Hausman; Cheldina Jean; Paul L. Pennington; Emily C. Pisarski; Edward F. Wirth (Archives of Environmental Contamination and Toxicology, 2021)

Pantropical variability in tree crown allometry - Grace Jopaul Loubota Panzou; Adeline Fayolle; Tommaso Jucker; Oliver L. Phillips; Stephanie Bohlman; Lindsay F. Banin; Simon L. Lewis; Kofi Affum‐Baffoe; Luciana F. Alves; Cécile Antin; Eric Arets; Luzmila Arroyo; et al. (Global Ecology and Biogeography, 2021)
Aim Tree crowns determine light interception, carbon and water exchange. Thus, understanding the factors causing tree crown allometry to vary at the tree and stand level matters greatly for the development of future vegetation modelling and for the calibration of remote sensing products. Nevertheless, we know little about large‐scale variation and determinants in tropical tree crown allometry. In this study, we explored the continental variation in scaling exponents of site‐specific crown allometry and assessed their relationships with environmental and stand‐level variables in the tropics. Location Global tropics. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 87,737 trees distributed among 245 forest and savanna sites across the tropics, we fitted site‐specific allometric relationships between crown dimensions (crown depth, diameter and volume) and stem diameter using power‐law models. Stand‐level and environmental drivers of crown allometric relationships were assessed at pantropical and continental scales. Results The scaling exponents of allometric relationships between stem diameter and crown dimensions were higher in savannas than in forests. We identified that continental crown models were better than pantropical crown models and that continental differences in crown allometric relationships were driven by both stand‐level (wood density) and environmental (precipitation, cation exchange capacity and soil texture) variables for both tropical biomes. For a given diameter, forest trees from Asia and savanna trees from Australia had smaller crown dimensions than trees in Africa and America, with crown volumes for some Asian forest trees being smaller than those of trees in African forests. Main conclusions Our results provide new insight into geographical variability, with large continental differences in tropical tree crown allometry that were driven by stand‐level and environmental variables. They have implications for the assessment of ecosystem function and for the monitoring of woody biomass by remote sensing techniques in the global tropics.

Making sense of virus size and the tradeoffs shaping viral fitness - Kyle F. Edwards; Grieg F. Steward; Christopher R. Schvarcz (Ecology Letters, 2021)
Viruses span an impressive size range, with genome length varying a thousandfold and virion volume nearly a millionfold. For cellular organisms the scaling of traits with size is a pervasive influence on ecological processes, but whether size plays a central role in viral ecology is unknown. Here, we focus on viruses of aquatic unicellular organisms, which exhibit the greatest known range of virus size. We outline hypotheses within a quantitative framework, and analyse data where available, to consider how size affects the primary components of viral fitness. We argue that larger viruses have fewer offspring per infection and slower contact rates with host cells, but a larger genome tends to increase infection efficiency, broaden host range, and potentially increase attachment success and decrease decay rate. These countervailing selective pressures may explain why a breadth of sizes exist and even coexist when infecting the same host populations. Oligotrophic ecosystems may be enriched in “giant” viruses, because environments with resource‐limited phagotrophs at low concentrations may select for broader host range, better control of host metabolism, lower decay rate and a physical size that mimics bacterial prey. Finally, we describe where further research is needed to understand the ecology and evolution of viral size diversity.

Accuracy assessment of global internal-tide models using satellite altimetry - Loren Carrere; Brian K. Arbic; Brian Dushaw; Gary Egbert; Svetlana Erofeeva; Florent Lyard; Richard D. Ray; Clément Ubelmann; Edward Zaron; Zhongxiang Zhao; Jay F. Shriver; Maarten Cornelis Buijsman; et al. (Ocean Science, 2021)
Altimeter measurements are corrected for several geophysical parameters in order to access ocean signals of interest, like mesoscale or sub-mesoscale variability. The ocean tide is one of the most critical corrections due to the amplitude of the tidal elevations and to the aliasing phenomena of high-frequency signals into the lower-frequency band, but the internal-tide signatures at the ocean surface are not yet corrected globally. Internal tides can have a signature of several centimeters at the surface with wavelengths of about 50–250 km for the first mode and even smaller scales for higher-order modes. The goals of the upcoming Surface Water Ocean Topography (SWOT) mission and other high-resolution ocean measurements make the correction of these small-scale signals a challenge, as the correction of all tidal variability becomes mandatory to access accurate measurements of other oceanic signals. In this context, several scientific teams are working on the development of new internal-tide models, taking advantage of the very long altimeter time series now available, which represent an unprecedented and valuable global ocean database. The internal-tide models presented here focus on the coherent internal-tide signal and they are of three types: empirical models based upon analysis of existing altimeter missions, an assimilative model and a three-dimensional hydrodynamic model. A detailed comparison and validation of these internal-tide models is proposed using existing satellite altimeter databases. The analysis focuses on the four main tidal constituents: M2, K1, O1 and S2. The validation process is based on a statistical analysis of multi-mission altimetry including Jason-2 and Cryosphere Satellite-2 data. The results show a significant altimeter variance reduction when using internal-tide corrections in all ocean regions where internal tides are generating or propagating. A complementary spectral analysis also gives some estimation of the performance of each model as a function of wavelength and some insight into the residual non-stationary part of internal tides in the different regions of interest. This work led to the implementation of a new internal-tide correction (ZARON'one) in the next geophysical data records version-F (GDR-F) standards.

Differences in joint power distribution in high and low lactate threshold cyclists - Brian K. Leary; Heath M. Burton; Emre Vardarli; Anthony S. Wolfe; Charles K. Crawford; John D. Akins; Edward F. Coyle (European Journal of Applied Physiology, 2021)

Physical activity for cancer patients during COVID-19 pandemic: a call to action - Leandro F. M. Rezende; Dong Hoon Lee; Gerson Ferrari; José Eluf-Neto; Edward L. Giovannucci (Cancer Causes & Control, 2021)

Plasticity in the grazing ecophysiology of Florenciella (Dichtyochophyceae), a mixotrophic nanoflagellate that consumes Prochlorococcus and other bacteria - Qian Li; Kyle F. Edwards; Christopher R. Schvarcz; Karen E. Selph; Grieg F. Steward (Limnology and Oceanography, 2021)
Mixotrophic nanoflagellates can account for more than half of the bacterivory in the sunlit ocean, yet very little is known about their ecophysiology. Here, we characterize the grazing ecology of an open‐ocean mixotroph in the genus Florenciella (class Dictyochophyceae). Members of this class were indirectly implicated as major consumers of Prochlorococcus and Synechococcus in the oligotrophic North Pacific Subtropical Gyre, but their phagotrophic capabilities have never been investigated. Our studies showed that Florenciella readily consumed Prochlorococcus , Synechococcus , and heterotrophic bacteria, and that the ingested prey relieved nutrient limitations on growth. Florenciella grew faster (3 d −1 ) in nitrogen‐deplete medium given sufficient live Synechococcus , than in nitrogen‐replete K medium (2 d −1 ), but it did not grow in continuous darkness. Grazing rates were substantially higher under nutrient limitation and showed a hint of diel variability, with rates tending to be highest near the end of the light period. An apparent trade‐off between the maximum clearance rate (5 nL Florenciella −1 h −1 ) and the maximum ingestion rate (up to ∼ 10 prey cells Florenciella −1 h −1 ) across experiments suggests that grazing behavior may also vary in response to prey concentration. If the observed grazing rates are representative of other open‐ocean mixotrophs, their collective activity could account for a significant fraction of the daily cyanobacterial mortality. This study provides essential parameters for understanding the grazing ecology of a common marine mixotroph and the first characterization of mixotrophic nanoflagellate functional responses when feeding on unicellular cyanobacteria, the dominant marine primary producers in the oligotrophic ocean.

Trevor Alleyne Thorpe: His academic life and scientific legacy - Prakash P. Kumar; Stephen F. Chandler; Indra S. Harry; Chin-yi Lu; Claudio Stasolla; Edward C. Yeung (In Vitro Cellular & Developmental Biology - Plant, 2020)

Trait‐based ecology at large scales: Assessing functional trait correlations, phylogenetic constraints and spatial variability using open data - Martin A. Wilkes; François Edwards; J. Iwan Jones; John F. Murphy; Judy England; Nikolai Friberg; Daniel Hering; N. LeRoy Poff; Philippe Usseglio‐Polatera; Wilco C. E. P. Verberk; Jon Webb; Lee E. Brown (Global Change Biology, 2020)
The growing use of functional traits in ecological research has brought new insights into biodiversity responses to global environmental change. However, further progress depends on overcoming three major challenges involving (a) statistical correlations between traits, (b) phylogenetic constraints on the combination of traits possessed by any single species, and (c) spatial effects on trait structure and trait–environment relationships. Here, we introduce a new framework for quantifying trait correlations, phylogenetic constraints and spatial variability at large scales by combining openly available species’ trait, occurrence and phylogenetic data with gridded, high‐resolution environmental layers and computational modelling. Our approach is suitable for use among a wide range of taxonomic groups inhabiting terrestrial, marine and freshwater habitats. We demonstrate its application using freshwater macroinvertebrate data from 35 countries in Europe. We identified a subset of available macroinvertebrate traits, corresponding to a life‐history model with axes of resistance, resilience and resource use, as relatively unaffected by correlations and phylogenetic constraints. Trait structure responded more consistently to environmental variation than taxonomic structure, regardless of location. A re‐analysis of existing data on macroinvertebrate communities of European alpine streams supported this conclusion, and demonstrated that occurrence‐based functional diversity indices are highly sensitive to the traits included in their calculation. Overall, our findings suggest that the search for quantitative trait–environment relationships using single traits or simple combinations of multiple traits is unlikely to be productive. Instead, there is a need to embrace the value of conceptual frameworks linking community responses to environmental change via traits which correspond to the axes of life‐history models. Through a novel integration of tools and databases, our flexible framework can address this need.

Evolution of the African slippery frogs (Anura: Conraua ), including the world’s largest living frog - David C. Blackburn; Stuart V. Nielsen; Michael F. Barej; Joseph Doumbia; Mareike Hirschfeld; N’Goran G. Kouamé; Dwight Lawson; Simon Loader; Caleb Ofori‐Boateng; Edward L. Stanley; Mark‐Oliver Rödel (Zoologica Scripta, 2020)
Although Conraua goliath is well known as the largest living frog species, the diversity and evolution of the genus Conraua across sub‐Saharan Africa remain poorly understood. We present multilocus phylogenetic analyses of the six currently recognized species that provide insights into divergence times, biogeography, body size evolution and undescribed species. An analysis of divergence times demonstrates that crown‐group Conraua arose some time during the latest Oligocene to mid‐Miocene followed by divergence into major lineages in the mid‐Miocene that may reflect the fragmentation of widespread tropical forests in Africa that began at this time. We find three pairs of sister species, C. crassipes + C. beccarii , C. alleni + C. derooi and C. goliath + C. robusta , each of which diverged during the Miocene. These relationships reject phylogenetic hypotheses based solely on biogeography as the geographically peripheral C. beccarii from north‐eastern Africa is nested within western African species and the Central African species do not form a clade. Our species delimitation analyses provide support for undescribed species in C. alleni , C. beccarii and C. derooi , and possibly C. crassipes , suggesting that the current taxonomy substantially underestimates species diversity. There is no clear directional trend of either increasing or decreasing body size in Conraua and the three largest species do not form a clade. With a robust phylogenetic hypothesis in hand, further field‐based studies are needed to understand the evolution of morphology and life history in this charismatic African anuran clade.

Evidence for the Pleistocene Arc Hypothesis from genome‐wide SNPs in a Neotropical dry forest specialist, the Rufous‐fronted Thornbird (Furnariidae: Phacellodomus rufifrons ) - Eamon C. Corbett; Gustavo A. Bravo; Fabio Schunck; Luciano N. Naka; Luís F. Silveira; Scott V. Edwards (Molecular Ecology, 2020)
South American dry forests have a complex and poorly understood biogeographic history. Based on the fragmented distribution of many Neotropical dry forest species, it has been suggested that this biome was more widely distributed and contiguous under drier climate conditions in the Pleistocene. To test this scenario, known as the Pleistocene Arc Hypothesis, we studied the phylogeography of the Rufous‐fronted Thornbird ( Phacellodomus rufifrons ), a widespread dry forest bird with a disjunct distribution closely matching that of the biome itself. We sequenced mtDNA and used ddRADseq to sample 7,167 genome‐wide single‐nucleotide polymorphisms from 74 P. rufifrons individuals across its range. We found low genetic differentiation over two prominent geographic breaks — particularly across a 1,000 km gap between populations in Bolivia and Northern Peru. Using demographic analyses of the joint site frequency spectrum, we found evidence of recent divergence without subsequent gene flow across those breaks. By contrast, parapatric morphologically distinct populations in northeastern Brazil show high genetic divergence with evidence of recent gene flow. These results, in combination with our paleoclimate species distribution modelling, support the idea that currently disjunct patches of dry forest were more connected in the recent past, probably during the Middle and Late Pleistocene. This notion fits the major predictions of the Pleistocene Arc Hypothesis and illustrates the importance of comprehensive genomic and geographic sampling for examining biogeographic and evolutionary questions in complex ecosystems like Neotropical dry forests.

The Role and Promise of Artificial Intelligence in Medical Toxicology - Michael A. Chary; Alex F. Manini; Edward W. Boyer; Michele Burns (Journal of Medical Toxicology, 2020)

Assessing the efficacy of nourishment of a Mediterranean beach using bimodal fluvial sediments and a specific placement design - Matteo Vacchi; Giorgio Berriolo; Chiara F. Schiaffino; Alessio Rovere; Edward A. Anthony; Nicola Corradi; Marco Firpo; Marco Ferrari (Geo-Marine Letters, 2020)

Intercomparison of Large-Eddy Simulations of the Antarctic Boundary Layer for Very Stable Stratification - Fleur Couvreux; Eric Bazile; Quentin Rodier; Björn Maronga; Georgios Matheou; Maria J. Chinita; John Edwards; Bart J. H. van Stratum; Chiel C. van Heerwaarden; Jing Huang; Arnold F. Moene; Anning Cheng; et al. (Boundary-Layer Meteorology, 2020)

Phylogenetic placement of Spermospora avenae, causal agent of red leather leaf disease of oats - A. Zaveri; R. C. Mann; J. K. Kaur; F. J. Henry; H. Wallwork; C. C. Linde; Jacqueline Edwards (Australasian Plant Pathology, 2020)

Cascading effects of termite mounds in African savannas - Justice Muvengwi; Edward T. F. Witkowski (New Zealand Journal of Botany, 2020)
African termites are classified into five distinct families, Termitidae, Rhinotermitidae, Hodotermitidae, Termopsidae and Kalotermitidae. Termites are undoubtedly one of the key ecosystem engineers. Because they harbour more nutritive plants, herbivory by large herbivores is biased towards mounds. Their engineering role is visible through construction of conspicuous termite mounds, which often harbour some unique species compared with the expansive ecosystem in which they occur. To understand the cascading effects of termite mounds on ecosystem functioning, we present a review on how termites create ecosystem heterogeneity, and how this heterogeneity in terms of soil physical and chemical characteristics, particularly nutrients, further influences vegetation production, diversity and palatability to large herbivores. Here we review literature mainly focusing on: (i) Phylogeny (evolutionary history) of African termites, (ii) mound construction, (iii) mound spatial distribution, (iv) termite foraging (v) termite nutrient cycling, (vi) termite influence on hydrology, (vii) termite mound influence on plant species diversity and (viii) termite mound influence on large herbivores. Our review showed that African termites are diverse, with the potential to influence ecosystems heterogeneity through soil nutrients enrichment, which in turn influences forage abundance (thicket clumps), diversity and quality. High forage quality occurring on termite mounds influences herbivory patterns in the savanna ecosystem. Herbivory is reported to be higher on termite mounds compared to the expansive savanna landscape. The most common plant family occurring on termite mounds is Capparaceae. We suggest that future studies focus more on: (1) the influence of termite mounds on plant functional traits, (2) the importance of termite mounds in dryland savanna cropping/rangeland systems, and (3) on ways to support establishment of mound building termite species.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Fitness, independent of physical activity is associated with cerebral blood flow in adults at risk for Alzheimer’s disease - Ryan J. Dougherty; Elizabeth A. Boots; Jacob B. Lindheimer; Aaron J. Stegner; Stephanie Van Riper; Dorothy F. Edwards; Catherine L. Gallagher; Cynthia M. Carlsson; Howard A. Rowley; Barbara B. Bendlin; Sanjay Asthana; Bruce P. Hermann; et al. (Brain Imaging and Behavior, 2020)

Impairments in Emotion Recognition and Risk-Taking Behavior After Isolated, Cerebellar Stroke - Nils S. van den Berg; Rients B. Huitema; Jacoba M. Spikman; Gert-Jan Luijckx; Edward H. F. de Haan (The Cerebellum, 2020)
An increasing amount of research has shown a cerebellar involvement in higher order cognitive functions, including emotional processing and decision-making. However, it has not been investigated whether impairments in facial emotion recognition, which could be a marker of impaired emotional experiences, are related to risky decision-making in these patients. Therefore, we aimed to investigate facial emotion recognition and risky decision-making in these patients as well as to investigate a relationship between these constructs. Thirteen patients with a discrete, isolated, cerebellar lesion as a consequence of a stroke were included in the study. Emotion recognition was assessed with the Facial Expressions of Emotions—Stimuli and Test (FEEST). Risk-taking behavior was assessed with the Action Selection Test (AST). Furthermore, 106 matched healthy controls performed the FEEST and 20 matched healthy controls performed the AST. Compared with healthy controls, patients were significantly worse in the recognition of emotional expressions and they took significantly more risks. In addition, a worse ability to recognize fearful facial expressions was strongly related to an increase in risky decisions in the AST. Therefore, we suggest that tests of emotion recognition should be incorporated into the neuropsychological assessment after cerebellar stroke to boost detection and treatment of these impairments in these patients.

Split-Brain: What We Know Now and Why This is Important for Understanding Consciousness - Edward H. F. de Haan; Paul M. Corballis; Steven A. Hillyard; Carlo A. Marzi; Anil Seth; Victor A. F. Lamme; Lukas Volz; Mara Fabri; Elizabeth Schechter; Tim Bayne; Michael Corballis; Yair Pinto (Neuropsychology Review, 2020)
Recently, the discussion regarding the consequences of cutting the corpus callosum (“split-brain”) has regained momentum (Corballis, Corballis, Berlucchi, & Marzi, Brain , 141 (6), e46, 2018; Pinto et al., Brain, 140 (5), 1231–1237, 2017a; Pinto, Lamme, & de Haan, Brain, 140 (11), e68, 2017; Volz & Gazzaniga, Brain , 140 (7), 2051–2060, 2017; Volz, Hillyard, Miller, & Gazzaniga, Brain , 141 (3), e15, 2018). This collective review paper aims to summarize the empirical common ground, to delineate the different interpretations, and to identify the remaining questions. In short, callosotomy leads to a broad breakdown of functional integration ranging from perception to attention. However, the breakdown is not absolute as several processes, such as action control, seem to remain unified. Disagreement exists about the responsible mechanisms for this remaining unity. The main issue concerns the first-person perspective of a split-brain patient. Does a split-brain harbor a split consciousness or is consciousness unified? The current consensus is that the body of evidence is insufficient to answer this question, and different suggestions are made with respect to how future studies might address this paucity. In addition, it is suggested that the answers might not be a simple yes or no but that intermediate conceptualizations need to be considered.

Direct Observation of Low Strain, High Rate Deformation of Cultured Brain Tissue During Primary Blast - Edward W. Vogel; Matthew B. Panzer; Fatima N. Morales; Nevin Varghese; Cameron R. Bass; David F. Meaney; Barclay Morrison (Annals of Biomedical Engineering, 2020)

Not a melting pot: Plant species aggregate in their non‐native range - Gisela C. Stotz; James F. Cahill; Jonathan A. Bennett; Cameron N. Carlyle; Edward W. Bork; Diana Askarizadeh; Sandor Bartha; Carl Beierkuhnlein; Bazartseren Boldgiv; Leslie Brown; Marcelo Cabido; Giandiego Campetella; et al. (Global Ecology and Biogeography, 2020)
Aim Plant species continue to be moved outside of their native range by human activities. Here, we aim to determine whether, once introduced, plants assimilate into native communities or whether they aggregate, thus forming mosaics of native‐ and alien‐rich communities. Alien species might aggregate in their non‐native range owing to shared habitat preferences, such as their tendency to establish in high‐biomass, species‐poor areas. Location Twenty‐two herbaceous grasslands in 14 countries, mainly in the temperate zone. Time period 2012–2016. Major taxa studied Plants. Methods We used a globally coordinated survey. Within this survey, we found 46 plant species, predominantly from Eurasia, for which we had co‐occurrence data in their native and non‐native ranges. We tested for differences in co‐occurrence patterns of 46 species between their native (home) and non‐native (away) range. We also tested whether species had similar habitat preferences, by testing for differences in total biomass and species richness of the patches that species occupy in their native and non‐native ranges. Results We found the same species to show different patterns of association depending on whether they were in their native or non‐native range. Alien species were negatively associated with native species; instead, they aggregated with other alien species in species‐poor, high‐biomass communities in their non‐native range compared with their native range. Main conclusions The strong differences between the native (home) and non‐native (away) range in species co‐occurrence patterns are evidence that the way in which species associate with resident communities in their non‐native range is not species dependent, but is instead a property of being away from their native range. These results thus highlight that species might undergo important ecological changes when introduced away from their native range. Overall, we show origin‐dependent associations that result in novel communities, in which alien‐rich patches exist within a mosaic of native‐dominated communities.

Secondary forest fragments offer important carbon and biodiversity cobenefits - Fabio A. R. Matos; Luiz F. S. Magnago; Carlos Aquila Chan Miranda; Luis F. T. de Menezes; Markus Gastauer; Nathália V. H. Safar; Carlos E. G. R. Schaefer; Mônica P. da Silva; Marcelo Simonelli; Felicity A. Edwards; Sebastião V. Martins; João A. A. Meira‐Neto; et al. (Global Change Biology, 2020)
Tropical forests store large amounts of carbon and high biodiversity, but are being degraded at alarming rates. The emerging global Forest and Landscape Restoration (FLR) agenda seeks to limit global climate change by removing carbon dioxide from the atmosphere through the growth of trees. In doing so, it may also protect biodiversity as a free cobenefit, which is vital given the massive shortfall in funding for biodiversity conservation. We investigated whether natural forest regeneration on abandoned pastureland offers such cobenefits, focusing for the first time on the recovery of taxonomic diversity (TD), phylogenetic diversity (PD) and functional diversity (FD) of trees, including the recovery of threatened and endemic species richness, within isolated secondary forest (SF) fragments. We focused on the globally threatened Brazilian Atlantic Forest, where commitments have been made to restore 1 million hectares under FLR. Three decades after land abandonment, regenerating forests had recovered ~20% (72 Mg/ha) of the above‐ground carbon stocks of a primary forest (PF), with cattle pasture containing just 3% of stocks relative to PFs. Over this period, SF recovered ~76% of TD, 84% of PD and 96% of FD found within PFs. In addition, SFs had on average recovered 65% of threatened and ~30% of endemic species richness of primary Atlantic forest. Finally, we find positive relationships between carbon stock and tree diversity recovery. Our results emphasize that SF fragments offer cobenefits under FLR and other carbon‐based payments for ecosystem service schemes (e.g. carbon enhancements under REDD+). They also indicate that even isolated patches of SF could help to mitigate climate change and the biodiversity extinction crisis by recovering species of high conservation concern and improving landscape connectivity.

Characteristics of free air carbon dioxide enrichment of a northern temperate mature forest - Kris M. Hart; Giulio Curioni; Phillip Blaen; Nicholas J. Harper; Peter Miles; Keith F. Lewin; John Nagy; Edward J. Bannister; Xiaoming M. Cai; Rick M. Thomas; Stefan Krause; Michael Tausz; et al. (Global Change Biology, 2020)
In 2017, the Birmingham Institute of Forest Research (BIFoR) began to conduct Free Air Carbon Dioxide Enrichment (FACE) within a mature broadleaf deciduous forest situated in the United Kingdom. BIFoR FACE employs large‐scale infrastructure, in the form of lattice towers, forming ‘arrays’ which encircle a forest plot of ~30 m diameter. BIFoR FACE consists of three treatment arrays to elevate local CO 2 concentrations (e[CO 2 ]) by +150 µmol/mol. In practice, acceptable operational enrichment (ambient [CO 2 ] + e[CO 2 ]) is ±20% of the set point 1‐min average target. There are a further three arrays that replicate the infrastructure and deliver ambient air as paired controls for the treatment arrays. For the first growing season with e[CO 2 ] (April to November 2017), [CO 2 ] measurements in treatment and control arrays show that the target concentration was successfully delivered, that is: +147 ± 21 µmol/mol (mean ± SD ) or 98 ± 14% of set point enrichment target. e[CO 2 ] treatment was accomplished for 97.7% of the scheduled operation time, with the remaining time lost due to engineering faults (0.6% of the time), CO 2 supply issues (0.6%) or adverse weather conditions (1.1%). CO 2 demand in the facility was driven predominantly by wind speed and the formation of the deciduous canopy. Deviations greater than 10% from the ambient baseline CO 2 occurred 80 µmol/mol (i.e. >53% of the treatment increment) into control arrays accounted for 2 ] values in reconstructed three‐dimensional [CO 2 ] fields show enrichment somewhat lower than the target but still well above ambient. The data presented here provide confidence in the facility setup and can be used to guide future next‐generation forest FACE facilities built into tall and complex forest stands.

Frag SAD : A database of diversity and species abundance distributions from habitat fragments - Jonathan M. Chase; Mario Liebergesell; Alban Sagouis; Felix May; Shane A. Blowes; Åke Berg; Enrico Bernard; Berry J. Brosi; Marc W. Cadotte; Luis Cayuela; Adriano G. Chiarello; Jean‐Francois Cosson; et al. (Ecology, 2019)
Habitat destruction is the single greatest anthropogenic threat to biodiversity. Decades of research on this issue have led to the accumulation of hundreds of data sets comparing species assemblages in larger, intact, habitats to smaller, more fragmented, habitats. Despite this, little synthesis or consensus has been achieved, primarily because of non‐standardized sampling methodology and analyses of notoriously scale‐dependent response variables (i.e., species richness). To be able to compare and contrast the results of habitat fragmentation on species’ assemblages, it is necessary to have the underlying data on species abundances and sampling intensity, so that standardization can be achieved. To accomplish this, we systematically searched the literature for studies where abundances of species in assemblages (of any taxa) were sampled from many habitat patches that varied in size. From these, we extracted data from several studies, and contacted authors of studies where appropriate data were collected but not published, giving us 117 studies that compared species assemblages among habitat fragments that varied in area. Less than one‐half (41) of studies came from tropical forests of Central and South America, but there were many studies from temperate forests and grasslands from all continents except Antarctica. Fifty‐four of the studies were on invertebrates (mostly insects), but there were several studies on plants (15), birds (16), mammals (19), and reptiles and amphibians (13). We also collected qualitative information on the length of time since fragmentation. With data on total and relative abundances (and identities) of species, sampling effort, and affiliated meta‐data about the study sites, these data can be used to more definitively test hypotheses about the role of habitat fragmentation in altering patterns of biodiversity. There are no copyright restrictions. Please cite this data paper and the associated Dryad data set if the data are used in publications.

Flood Exposure Affects Long-Term Tree Survival in Compensatory Mitigation Wetlands - Jeffrey W. Matthews; Geoffrey E. Pociask; Edward P. F. Price; Adrianna E. Krzywicka (Wetlands, 2019)

An approach to forecast grain crop yield using multi-layered, multi-farm data sets and machine learning - Patrick Filippi; Edward J. Jones; Niranjan S. Wimalathunge; Pallegedara D. S. N. Somarathna; Liana E. Pozza; Sabastine U. Ugbaje; Thomas G. Jephcott; Stacey E. Paterson; Brett M. Whelan; Thomas F. A. Bishop (Precision Agriculture, 2019)

Integrated Risk Assessment for the Blue Economy - Emma E. Hodgson; Timothy E. Essington; Jameal F. Samhouri; Edward H. Allison; Nathan J. Bennett; Ann Bostrom; Alison C. Cullen; Stephen Kasperski; Phillip S. Levin; Melissa R. Poe (Frontiers in Marine Science, 2019)

Characterisation of the effect of day length, and associated differences in dietary intake, on the gut microbiota of Soay sheep - Nadine A. Thomas; Andrea M. Olvera-Ramírez; Leticia Abecia; Clare L. Adam; Joan E. Edwards; Georgina F. Cox; Patricia A. Findlay; Elodie Destables; Tracy A. Wood; Neil R. McEwan (Archives of Microbiology, 2019)

Epidemiological Investigation of Toxoplasma gondii Infections in Commercial Sheep Flock in an Endemic Area for Ocular Toxoplasmosis in Southern Brazil - Angélica Consalter; Edwards Frazão-Teixeira; Jitender P. Dubey; Eraldo L. Zanella; Andressa F. da Silva; Guilherme N. de Souza; Ana M. R. Ferreira (Acta Parasitologica, 2019)

Public–Private Partnerships to Advance Regional Ocean-Observing Capabilities: A Saildrone and NOAA-PMEL Case Study and Future Considerations to Expand to Global Scale Observing - Christian Meinig; Eugene F. Burger; Nora Cohen; Edward D. Cokelet; Meghan F. Cronin; Jessica N. Cross; Sebastien de Halleux; Richard Jenkins; Andrew T. Jessup; Calvin W. Mordy; Noah Lawrence-Slavas; Adrienne J. Sutton; et al. (Frontiers in Marine Science, 2019)

Effect of rhizomania on red table-beet biomass production and molecular characterization of an isolate of Beet necrotic yellow vein virus from Brazil - Viviana M. Camelo-García; Juan P. Edwards Molina; Tatsuya Nagata; Jorge A. M. Rezende; João M. F. Silva (European Journal of Plant Pathology, 2019)

Recombinant human lactoferrin induces apoptosis, disruption of F-actin structure and cell cycle arrest with selective cytotoxicity on human triple negative breast cancer cells - Blanca F. Iglesias-Figueroa; Tania S. Siqueiros-Cendón; Denisse A. Gutierrez; Renato J. Aguilera; Edward A. Espinoza-Sánchez; Sigifredo Arévalo-Gallegos; Armando Varela-Ramirez; Quintín Rascón-Cruz (Apoptosis, 2019)

Lessons from seabird conservation in Alaskan longline fisheries - Edward F. Melvin; Kimberly S. Dietrich; Robert M. Suryan; Shannon M. Fitzgerald (Conservation Biology, 2019)
Although bycatch of seabirds and other long‐lived species is a critical conservation issue in world fisheries, case studies documenting significant reductions in the mortality of these low‐productivity species in a fishery are rare. We studied progress toward seabird conservation in the Alaskan longline fisheries, one of the largest and most diverse demersal fisheries. We generated annual seabird bycatch rates in 4 target fisheries and all fisheries combined from 23 years of fisheries observer data. We used 0‐inflated negative binomial models to evaluate variables influencing seabird bycatch per unit effort (BPUE) in 2 target fisheries. Following adoption of streamer lines, at first voluntarily and then mandatorily, seabird BPUE was reduced by 77–90%, preventing mortality of thousands of birds per year. Despite this, BPUE increased significantly in 2 of 4 target fisheries since streamer lines were adopted. Although night setting yielded significant reductions (74–97%) in seabird BPUE and significant increases (7–11%) in fish catch per unit effort over daytime setting, nighttime setting increased the BPUE of Northern Fulmar ( Fulmarus glacialis ) by 40% and nontarget fish species by 5–17%. Thus, best practices to prevent seabird mortalities in longline fisheries varied by species assemblage and fishery. Our results inform global efforts toward fisheries bycatch reduction by illustrating that successful conservation requires fishery‐specific solutions, strong industry support, constant vigilance in analysis and reporting observer data, and ongoing outreach to fleets, especially to vessels with anomalously high BPUE.

Microbiological safety of popular recreation swimming sites in Central California - Xunde Li; Jennifer A. Chase; Ronald F. Bond; Panachon Lor; Kristine Fernandez; Trân H. Nguyen; Melissa L. Partyka; Anyarat Thiptara; Edward R. Atwill (Environmental Monitoring and Assessment, 2019)

Phosphate‐limited ocean regions select for bacterial populations enriched in the carbon–phosphorus lyase pathway for phosphonate degradation - Oscar A. Sosa; Daniel J. Repeta; Edward F. DeLong; Mohammad D. Ashkezari; David M. Karl (Environmental Microbiology, 2019)
Summary In tropical and subtropical oceanic surface waters phosphate scarcity can limit microbial productivity. However, these environments also have bioavailable forms of phosphorus incorporated into dissolved organic matter (DOM) that microbes with the necessary transport and hydrolysis metabolic pathways can access to supplement their phosphorus requirements. In this study we evaluated how the environment shapes the abundance and taxonomic distribution of the bacterial carbon–phosphorus (C–P) lyase pathway, an enzyme complex evolved to extract phosphate from phosphonates. Phosphonates are organophosphorus compounds characterized by a highly stable C–P bond and are enriched in marine DOM. Similar to other known bacterial adaptions to low phosphate environments, C–P lyase was found to become more prevalent as phosphate concentrations decreased. C–P lyase was particularly enriched in the Mediterranean Sea and North Atlantic Ocean, two regions that feature sustained periods of phosphate depletion. In these regions, C–P lyase was prevalent in several lineages of Alphaproteobacteria ( Pelagibacter , SAR116, Roseobacter and Rhodospirillales ), Gammaproteobacteria, and Actinobacteria . The global scope of this analysis supports previous studies that infer phosphonate catabolism via C–P lyase is an important adaptive strategy implemented by bacteria to alleviate phosphate limitation and expands the known geographic extent and taxonomic affiliation of this metabolic pathway in the ocean.

Ten tips for developing interdisciplinary socio-ecological researchers - Rachel Kelly; Mary Mackay; Kirsty L. Nash; Christopher Cvitanovic; Edward H. Allison; Derek Armitage; Aletta Bonn; Steven J. Cooke; Stewart Frusher; Elizabeth A. Fulton; Benjamin S. Halpern; Priscila F. M. Lopes; et al. (Socio-Ecological Practice Research, 2019)

Effects of recombinant salmon type II growth hormone and bovine growth hormone on growth of coho salmon (Oncorhynchus kisutch) - Annette F. Muttray; Edward M. Donaldson; Robert H. Devlin (Fish Physiology and Biochemistry, 2019)

Late Quaternary sea‐level change and evolution of Belfast Lough, Northern Ireland: new offshore evidence and implications for sea‐level reconstruction - Ruth M. K. Plets; S. Louise Callard; J. Andrew G. Cooper; Joseph T. Kelley; Daniel F. Belknap; Robin J. Edwards; Antony J. Long; Rory J. Quinn; Derek W. T. Jackson (Journal of Quaternary Science, 2019)
The interplay of eustatic and isostatic factors causes complex relative sea‐level (RSL) histories, particularly in paraglacial settings. In this context the past record of RSL is important in understanding ice‐sheet history, earth rheology and resulting glacio‐isostatic adjustment. Field data to develop sea‐level reconstructions are often limited to shallow depths and uncertainty exists as to the veracity of modelled sea‐level curves. We use seismic stratigraphy, 39 vibrocores and 26 radiocarbon dates to investigate the deglacial history of Belfast Lough, Northern Ireland, and reconstruct past RSL. A typical sequence of till, glacimarine and Holocene sediments is preserved. Two sea‐level lowstands (both max. −40 m) are recorded at c. 13.5 and 11.5k cal a bp . Each is followed by a rapid transgression and subsequent periods of RSL stability. The first transgression coincides temporally with a late stage of Meltwater Pulse 1a and the RSL stability occurred between c. 13.0 and c. 12.2k cal a bp (Younger Dryas). The second still/slowstand occurred between c. 10.3 and c. 11.5k cal a bp . Our data provide constraints on the direction and timing of RSL change during deglaciation. Application of the Depth of Closure concept adds an error term to sea‐level reconstructions based on seismic stratigraphic reconstructions.

Advancing Research for the Management of Long-Lived Species: A Case Study on the Greenland Shark - Jena E. Edwards; Elizabeth Hiltz; Franziska Broell; Peter G. Bushnell; Steven E. Campana; Jørgen S. Christiansen; Brynn M. Devine; Jeffrey J. Gallant; Kevin J. Hedges; M. Aaron MacNeil; Bailey C. McMeans; Julius Nielsen; et al. (Frontiers in Marine Science, 2019)

The U.S. Climate Resilience Toolkit: evidence of progress - Edward P. Gardiner; David D. Herring; James F. Fox (Climatic Change, 2019)

Future Directions in Conservation Research on Petrels and Shearwaters - Airam Rodríguez; José M. Arcos; Vincent Bretagnolle; Maria P. Dias; Nick D. Holmes; Maite Louzao; Jennifer Provencher; André F. Raine; Francisco Ramírez; Beneharo Rodríguez; Robert A. Ronconi; Rebecca S. Taylor; et al. (Frontiers in Marine Science, 2019)

Antibiotic misuse in respiratory tract infections in children and adults—a prospective, multicentre study (TAILORED Treatment) - Chantal B. van Houten; Asi Cohen; Dan Engelhard; John P. Hays; Roger Karlsson; Edward Moore; David Fernández; Racheli Kreisberg; Laurence V. Collins; Wouter de Waal; Karin M. de Winter-de Groot; Tom F. W. Wolfs; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Understanding the evolving phenotype of vascular complications in telomere biology disorders - Cecilia Higgs; Yanick J. Crow; Denise M. Adams; Emmanuel Chang; Don Hayes; Utz Herbig; James N. Huang; Ryan Himes; Kunal Jajoo; F. Brad Johnson; Susan D. Reynolds; Yoshihiro Yonekawa; et al. (Angiogenesis, 2019)

A Computational Cardiac Model for the Adaptation to Pulmonary Arterial Hypertension in the Rat - Reza Avazmohammadi; Emilio A. Mendiola; João S. Soares; David S. Li; Zhiqiang Chen; Samer Merchant; Edward W. Hsu; Peter Vanderslice; Richard A. F. Dixon; Michael S. Sacks (Annals of Biomedical Engineering, 2019)

Evolutionarily stable communities: a framework for understanding the role of trait evolution in the maintenance of diversity - Kyle F. Edwards; Colin T. Kremer; Elizabeth T. Miller; Matthew M. Osmond; Elena Litchman; Christopher A. Klausmeier (Ecology Letters, 2018)
Biological diversity depends on the interplay between evolutionary diversification and ecological mechanisms allowing species to coexist. Current research increasingly integrates ecology and evolution over a range of timescales, but our common conceptual framework for understanding species coexistence requires better incorporation of evolutionary processes. Here, we focus on the idea of evolutionarily stable communities ( ESC s), which are theoretical endpoints of evolution in a community context. We use ESC s as a unifying framework to highlight some important but under‐appreciated theoretical results, and we review empirical research relevant to these theoretical predictions. We explain how, in addition to generating diversity, evolution can also limit diversity by reducing the effectiveness of coexistence mechanisms. The coevolving traits of competing species may either diverge or converge, depending on whether the number of species in the community is low (undersaturated) or high (oversaturated) relative to the ESC . Competition in oversaturated communities can lead to extinction or neutrally coexisting, ecologically equivalent species. It is critical to consider trait evolution when investigating fundamental ecological questions like the strength of different coexistence mechanisms, the feasibility of ecologically equivalent species, and the interpretation of different patterns of trait dispersion.

Pragmatic criteria to define chronic pseudomonas aeruginosa infection among adults with cystic fibrosis - Zhe Hui Hoo; Elizabeth Coates; Chin Maguire; Hannah Cantrill; Nadia Shafi; Edward F. Nash; Angela McGowan; Stephen J. Bourke; William G. Flight; Thomas V. Daniels; Julia A. Nightingale; Mark I. Allenby; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Variation in coral-associated cryptofaunal communities across spatial scales and environmental gradients - Chelsie W. W. Counsell; Megan J. Donahue; Kyle F. Edwards; Erik C. Franklin; Mark A. Hixon (Coral Reefs, 2018)

Cross‐scale controls on carbon emissions from boreal forest megafires - Xanthe J. Walker; Brendan M. Rogers; Jennifer L. Baltzer; Steven G. Cumming; Nicola J. Day; Scott J. Goetz; Jill F. Johnstone; Edward A. G. Schuur; Merritt R. Turetsky; Michelle C. Mack (Global Change Biology, 2018)
Climate warming and drying is associated with increased wildfire disturbance and the emergence of megafires in North American boreal forests. Changes to the fire regime are expected to strongly increase combustion emissions of carbon (C) which could alter regional C balance and positively feedback to climate warming. In order to accurately estimate C emissions and thereby better predict future climate feedbacks, there is a need to understand the major sources of heterogeneity that impact C emissions at different scales. Here, we examined 211 field plots in boreal forests dominated by black spruce ( Picea mariana ) or jack pine ( Pinus banksiana ) of the Northwest Territories ( NWT ), Canada after an unprecedentedly large area burned in 2014. We assessed both aboveground and soil organic layer ( SOL ) combustion, with the goal of determining the major drivers in total C emissions, as well as to develop a high spatial resolution model to scale emissions in a relatively understudied region of the boreal forest. On average, 3.35 kg C m −2 was combusted and almost 90% of this was from SOL combustion. Our results indicate that black spruce stands located at landscape positions with intermediate drainage contribute the most to C emissions. Indices associated with fire weather and date of burn did not impact emissions, which we attribute to the extreme fire weather over a short period of time. Using these results, we estimated a total of 94.3 Tg C emitted from 2.85 Mha of burned area across the entire 2014 NWT fire complex, which offsets almost 50% of mean annual net ecosystem production in terrestrial ecosystems of Canada. Our study also highlights the need for fine‐scale estimates of burned area that represent small water bodies and regionally specific calibrations of combustion that account for spatial heterogeneity in order to accurately model emissions at the continental scale.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Towards a microbial universal theory of all (nearly) totality: MUTANT - Edward F. DeLong (Environmental Microbiology, 2018)

Thank You Ken, Joan and Dave, for 20 years of Environmental Microbiology! - Edward F. DeLong (Environmental Microbiology, 2018)

Regional forcing explains local species diversity and turnover on tropical islands - Thomas Ibanez; Gunnar Keppel; Cláudia Baider; Chris Birkinshaw; Heike Culmsee; Susan Cordell; F. B. Vincent Florens; Janet Franklin; Christian P. Giardina; Thomas W. Gillespie; Melinda Laidlaw; Creighton M. Litton; et al. (Global Ecology and Biogeography, 2018)
Aim To determine the role of regional forcing on plot‐level species diversity and composition, and to quantify the relative importance of biogeographical and climatic factors in explaining woody plant diversity and composition at the local‐, island‐ and archipelago‐scale. Location Forty‐one tropical islands of the Indo‐Pacific region from Madagascar to Hawai‘i Island. Methods We analysed the diversity and composition of tropical woody plant communities located across 113 plots, 41 islands and 19 archipelagos. We used generalized linear mixed‐effects models and generalized dissimilarity models to determine the role of regional forcing at the island and archipelago scale and to assess the relative importance of biogeographical (area and isolation of islands or archipelagos, geographical distance between plots) and climatic factors in explaining differences in local diversity and composition (species turnover). Analyses were conducted at different geographical scales (local, island and archipelago) and taxonomic levels (species, genus and family). Results Variation in local (plot‐level) diversity (as species density, the number of species per 100 woody plants) was primarily explained by island and archipelago identity. Maximum species density was positively correlated with the area of an island (or archipelago) and negatively correlated with the isolation of an archipelago. Local climatic variability was also a significant predictor of species density, but less important than regional forcing. Climate variables explained Main conclusions Regional forcing was the key driver of local diversity and composition on islands. Island area and archipelago isolation are likely driving local diversity through their effects on the pool of island species. Geographical distance between plots is the main factor explaining species turnover, while at higher taxonomic levels, climatic factors and niche conservatism are the main drivers.

Occupational exposure to perfluoroalkyl substances and serum levels of perfluorooctanesulfonic acid (PFOS) and perfluorooctanoic acid (PFOA) in an aging population from upstate New York: a retrospective cohort study - Eva M. Tanner; Michael S. Bloom; Qian Wu; Kurunthachalam Kannan; Recai M. Yucel; Srishti Shrestha; Edward F. Fitzgerald (International Archives of Occupational and Environmental Health, 2018)

Ecosystem state shifts during long‐term development of an Amazonian peatland - Graeme T. Swindles; Paul J. Morris; Bronwen Whitney; Jennifer M. Galloway; Mariusz Gałka; Angela Gallego‐Sala; Andrew L. Macumber; Donal Mullan; Mark W. Smith; Matthew J. Amesbury; Thomas P. Roland; Hamed Sanei; et al. (Global Change Biology, 2018)
The most carbon (C)‐dense ecosystems of Amazonia are areas characterized by the presence of peatlands. However, Amazonian peatland ecosystems are poorly understood and are threatened by human activities. Here, we present an investigation into long‐term ecohydrological controls on C accumulation in an Amazonian peat dome. This site is the oldest peatland yet discovered in Amazonia (peat initiation ca. 8.9 ka BP ), and developed in three stages: (i) peat initiated in an abandoned river channel with open water and aquatic plants; (ii) inundated forest swamp; and (iii) raised peat dome (since ca. 3.9 ka BP ). Local burning occurred at least three times in the past 4,500 years. Two phases of particularly rapid C accumulation (ca. 6.6–6.1 and ca. 4.9–3.9 ka BP ), potentially resulting from increased net primary productivity, were seemingly driven by drier conditions associated with widespread drought events. The association of drought phases with major ecosystem state shifts (open water wetland–forest swamp–peat dome) suggests a potential climatic control on the developmental trajectory of this tropical peatland. A third drought phase centred on ca. 1.8–1.1 ka BP led to markedly reduced C accumulation and potentially a hiatus during the peat dome stage. Our results suggest that future droughts may lead to phases of rapid C accumulation in some inundated tropical peat swamps, although this can lead ultimately to a shift to ombrotrophy and a subsequent return to slower C accumulation. Conversely, in ombrotrophic peat domes, droughts may lead to reduced C accumulation or even net loss of peat. Increased surface wetness at our site in recent decades may reflect a shift towards a wetter climate in western Amazonia. Amazonian peatlands represent important carbon stores and habitats, and are important archives of past climatic and ecological information. They should form key foci for conservation efforts.

The Differential Absorption of a Series of P-Glycoprotein Substrates in Isolated Perfused Lungs from Mdr1a/1b Genetic Knockout Mice can be Attributed to Distinct Physico-Chemical Properties: an Insight into Predicting Transporter-Mediated, Pulmonary Specific Disposition - Daniel F. Price; Chris N. Luscombe; Peter J. Eddershaw; Chris D. Edwards; Mark Gumbleton (Pharmaceutical Research, 2017)

Keeping it in the family: strong fine-scale genetic structure and inbreeding in Lodoicea maldivica, the largest-seeded plant in the world - E. J. Morgan; C. N. Kaiser-Bunbury; P. J. Edwards; F. Fleischer-Dogley; C. J. Kettle (Conservation Genetics, 2017)

Asynchrony among local communities stabilises ecosystem function of metacommunities - Kevin R. Wilcox; Andrew T. Tredennick; Sally E. Koerner; Emily Grman; Lauren M. Hallett; Meghan L. Avolio; Kimberly J. La Pierre; Gregory R. Houseman; Forest Isbell; David Samuel Johnson; Juha M. Alatalo; Andrew H. Baldwin; et al. (Ecology Letters, 2017)
Temporal stability of ecosystem functioning increases the predictability and reliability of ecosystem services, and understanding the drivers of stability across spatial scales is important for land management and policy decisions. We used species‐level abundance data from 62 plant communities across five continents to assess mechanisms of temporal stability across spatial scales. We assessed how asynchrony (i.e. different units responding dissimilarly through time) of species and local communities stabilised metacommunity ecosystem function. Asynchrony of species increased stability of local communities, and asynchrony among local communities enhanced metacommunity stability by a wide range of magnitudes (1–315%); this range was positively correlated with the size of the metacommunity. Additionally, asynchronous responses among local communities were linked with species’ populations fluctuating asynchronously across space, perhaps stemming from physical and/or competitive differences among local communities. Accordingly, we suggest spatial heterogeneity should be a major focus for maintaining the stability of ecosystem services at larger spatial scales.

Political transition and emergent forest‐conservation issues in Myanmar - Graham W. Prescott; William J. Sutherland; Daniel Aguirre; Matthew Baird; Vicky Bowman; Jake Brunner; Grant M. Connette; Martin Cosier; David Dapice; Jose Don T. De Alban; Alex Diment; Julia Fogerite; et al. (Conservation Biology, 2017)
Political and economic transitions have had substantial impacts on forest conservation. Where transitions are underway or anticipated, historical precedent and methods for systematically assessing future trends should be used to anticipate likely threats to forest conservation and design appropriate and prescient policy measures to counteract them. Myanmar is transitioning from an authoritarian, centralized state with a highly regulated economy to a more decentralized and economically liberal democracy and is working to end a long‐running civil war. With these transitions in mind, we used a horizon‐scanning approach to assess the 40 emerging issues most affecting Myanmar's forests, including internal conflict, land‐tenure insecurity, large‐scale agricultural development, demise of state timber enterprises, shortfalls in government revenue and capacity, and opening of new deforestation frontiers with new roads, mines, and hydroelectric dams. Averting these threats will require, for example, overhauling governance models, building capacity, improving infrastructure‐ and energy‐project planning, and reforming land‐tenure and environmental‐protection laws. Although challenges to conservation in Myanmar are daunting, the political transition offers an opportunity for conservationists and researchers to help shape a future that enhances Myanmar's social, economic, and environmental potential while learning and applying lessons from other countries. Our approach and results are relevant to other countries undergoing similar transitions.

Erratum to: A multi-stage genome-wide association study of uterine fibroids in African Americans - Jacklyn N. Hellwege; Janina M. Jeff; Lauren A. Wise; C. Scott Gallagher; Melissa Wellons; Katherine E. Hartmann; Sarah F. Jones; Eric S. Torstenson; Scott Dickinson; Edward A. Ruiz-Narváez; Nadin Rohland; Alexander Allen; et al. (Human Genetics, 2017)

Haldane and Fisher – scientific interactions - A. W. F. Edwards (Journal of Genetics, 2017)

Wastewater influences nitrogen dynamics in a coastal catchment during a prolonged drought - Denise A. Bruesewitz; Timothy J. Hoellein; Rae F. Mooney; Wayne S. Gardner; Edward J. Buskey (Limnology and Oceanography, 2017)
Ecosystem function measurements can enhance our understanding of nitrogen (N) delivery in coastal catchments across river and estuary ecosystems. Here, we contrast patterns of N cycling and export in two rivers, one heavily influenced by wastewater treatment plants (WWTP), in a coastal catchment of south Texas. We measured N export from both rivers to the estuary over 2 yr that encompass a severe drought, along with detailed mechanisms of N cycling in river, tidal river, and two estuary sites during prolonged drought. WWTP nutrient inputs stimulated uptake of N, but denitrification resulting in permanent N removal accounted for only a small proportion of total uptake. During drought periods, WWTP N was the primary source of exported N to the estuary, minimizing the influence of episodic storm‐derived nutrients from the WWTP‐influenced river to the estuary. In the site without WWTP influence, the river exported very little N during drought, so storm‐derived nutrient pulses were important for delivering N loads to the estuary. Overall, N is processed from river to estuary, but sustained WWTP‐N loads and periodic floods alter the timing of N delivery and N processing. Research that incorporates empirical measurements of N fluxes from river to estuary can inform management needs in the face of multiple anthropogenic stressors such as demand for freshwater and eutrophication.

A multi-stage genome-wide association study of uterine fibroids in African Americans - Jacklyn N. Hellwege; Janina M. Jeff; Lauren A. Wise; C. Scott Gallagher; Melissa Wellons; Katherine E. Hartmann; Sarah F. Jones; Eric S. Torstenson; Scott Dickinson; Edward A. Ruiz-Narváez; Nadin Rohland; Alexander Allen; et al. (Human Genetics, 2017)
Uterine fibroids are benign tumors of the uterus affecting up to 77% of women by menopause. They are the leading indication for hysterectomy, and account for $34 billion annually in the United States. Race/ethnicity and age are the strongest known risk factors. African American (AA) women have higher prevalence, earlier onset, and larger and more numerous fibroids than European American women. We conducted a multi-stage genome-wide association study (GWAS) of fibroid risk among AA women followed by in silico genetically predicted gene expression profiling of top hits. In Stage 1, cases and controls were confirmed by pelvic imaging, genotyped and imputed to 1000 Genomes. Stage 2 used self-reported fibroid and GWAS data from 23andMe, Inc. and the Black Women’s Health Study. Associations with fibroid risk were modeled using logistic regression adjusted for principal components, followed by meta-analysis of results. We observed a significant association among 3399 AA cases and 4764 AA controls at rs739187 (risk-allele frequency = 0.27) in CYTH4 (OR (95% confidence interval) = 1.23 (1.16–1.30), p value = 7.82 × 10 −9 ). Evaluation of the genetic association results with MetaXcan identified lower predicted gene expression of CYTH4 in thyroid tissue as significantly associated with fibroid risk ( p value = 5.86 × 10 −8 ). In this first multi-stage GWAS for fibroids among AA women, we identified a novel risk locus for fibroids within CYTH4 that impacts gene expression in thyroid and has potential biological relevance for fibroids.

Phylogeography and population genetics of introduced Silver Carp (Hypophthalmichthys molitrix) and Bighead Carp (H. nobilis) in North America - Heather L. Farrington; Christine E. Edwards; Meredith Bartron; Richard F. Lance (Biological Invasions, 2017)

Qualitative and quantitative factors affecting the relationship between Canola leaf spot epidemic and stem base canker (Leptosphaeria maculans) in Argentina - J. P. Edwards Molina; A. Escande; G. Cendoya; F. Quiroz (Australasian Plant Pathology, 2017)

The landscape of genetic diseases in Saudi Arabia based on the first 1000 diagnostic panels and exomes - Dorota Monies; Mohamed Abouelhoda; Moeenaldeen AlSayed; Zuhair Alhassnan; Maha Alotaibi; Husam Kayyali; Mohammed Al-Owain; Ayaz Shah; Zuhair Rahbeeni; Mohammad A. Al-Muhaizea; Hamad I. Alzaidan; Edward Cupler; et al. (Human Genetics, 2017)

Differences in meristems between monocots and dicots and susceptibility to attack by gall-inducing insects - Megan S. Silvia; Edward F. Connor (Arthropod-Plant Interactions, 2017)

Greater temperature sensitivity of plant phenology at colder sites: implications for convergence across northern latitudes - Janet Prevéy; Mark Vellend; Nadja Rüger; Robert D. Hollister; Anne D. Bjorkman; Isla H. Myers‐Smith; Sarah C. Elmendorf; Karin Clark; Elisabeth J. Cooper; Bo Elberling; Anna M. Fosaa; Gregory H. R. Henry; et al. (Global Change Biology, 2017)
Warmer temperatures are accelerating the phenology of organisms around the world. Temperature sensitivity of phenology might be greater in colder, higher latitude sites than in warmer regions, in part because small changes in temperature constitute greater relative changes in thermal balance at colder sites. To test this hypothesis, we examined up to 20 years of phenology data for 47 tundra plant species at 18 high‐latitude sites along a climatic gradient. Across all species, the timing of leaf emergence and flowering was more sensitive to a given increase in summer temperature at colder than warmer high‐latitude locations. A similar pattern was seen over time for the flowering phenology of a widespread species, Cassiope tetragona . These are among the first results highlighting differential phenological responses of plants across a climatic gradient and suggest the possibility of convergence in flowering times and therefore an increase in gene flow across latitudes as the climate warms.

Initial biochar effects on plant productivity derive from N fertilization - Simon Jeffery; Ilse Memelink; Edward Hodgson; Sian Jones; Tess F. J. van de Voorde; T. Martijn Bezemer; Liesje Mommer; Jan Willem van Groenigen (Plant and Soil, 2017)

Effect of tempol and tempol plus catalase on intra-renal haemodynamics in spontaneously hypertensive stroke-prone (SHSP) and Wistar rats - Ahmad F Ahmeda; Mark G. Rae; Mohammed F. Al Otaibi; Lamyia M Anweigi; Edward J Johns (Journal of Physiology and Biochemistry, 2017)

History of hypertension, heart disease, and diabetes and ovarian cancer patient survival: evidence from the ovarian cancer association consortium - Albina N. Minlikeeva; Jo L. Freudenheim; Rikki A. Cannioto; J. Brian Szender; Kevin H. Eng; Francesmary Modugno; Roberta B. Ness; Michael J. LaMonte; Grace Friel; Brahm H. Segal; Kunle Odunsi; Paul Mayor; et al. (Cancer Causes & Control, 2017)

NAD-preferring malic enzyme: localization, regulation and its potential role in herring (Clupea harengus) sperm cells - Natalia Niedźwiecka; Jadwiga Gronczewska; Edward F. Skorkowski (Fish Physiology and Biochemistry, 2017)

Plant growth in amended molybdenum mine waste rock - Owen T. Burney; Edward F. Redente; Charles E. Lambert (Environmental Science and Pollution Research, 2017)

Continued feeding on Diporeia by deepwater sculpin in Lake Huron - Patricia A. Thompson; Edward F. Roseman; Kevin M. Keeler; Timothy P. O’Brien; Dustin A. Bowser (Environmental Biology of Fishes, 2017)

High-Speed Laser Image Analysis of Plume Angles for Pressurised Metered Dose Inhalers: The Effect of Nozzle Geometry - Yang Chen; Paul M. Young; Seamus Murphy; David F. Fletcher; Edward Long; David Lewis; Tanya Church; Daniela Traini (AAPS PharmSciTech, 2017)

Litter decay controlled by temperature, not soil properties, affecting future soil carbon - Edward G. Gregorich; Henry Janzen; Benjamin H. Ellert; Bobbi L. Helgason; Budong Qian; Bernie J. Zebarth; Denis A. Angers; Ronald P. Beyaert; Craig F. Drury; Scott D. Duguid; William E. May; Brian G. McConkey; et al. (Global Change Biology, 2017)
Widespread global changes, including rising atmospheric CO 2 concentrations, climate warming and loss of biodiversity, are predicted for this century; all of these will affect terrestrial ecosystem processes like plant litter decomposition. Conversely, increased plant litter decomposition can have potential carbon‐cycle feedbacks on atmospheric CO 2 levels, climate warming and biodiversity. But predicting litter decomposition is difficult because of many interacting factors related to the chemical, physical and biological properties of soil, as well as to climate and agricultural management practices. We applied 13 C‐labelled plant litter to soil at ten sites spanning a 3500‐km transect across the agricultural regions of Canada and measured its decomposition over five years. Despite large differences in soil type and climatic conditions, we found that the kinetics of litter decomposition were similar once the effect of temperature had been removed, indicating no measurable effect of soil properties. A two‐pool exponential decay model expressing undecomposed carbon simply as a function of thermal time accurately described kinetics of decomposition. ( R 2 = 0.94; RMSE = 0.0508). Soil properties such as texture, cation exchange capacity, pH and moisture, although very different among sites, had minimal discernible influence on decomposition kinetics. Using this kinetic model under different climate change scenarios, we projected that the time required to decompose 50% of the litter (i.e. the labile fractions) would be reduced by 1–4 months, whereas time required to decompose 90% of the litter (including recalcitrant fractions) would be reduced by 1 year in cooler sites to as much as 2 years in warmer sites. These findings confirm quantitatively the sensitivity of litter decomposition to temperature increases and demonstrate how climate change may constrain future soil carbon storage, an effect apparently not influenced by soil properties.

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Specification of a Coupled Geological and Wellbore Fluid Dynamics Model for Uncertainty Analysis and Risk-Based Design on a Subsea Oil Project - Christopher J. Jablonowski; Arash Haghshenas; Edward E. Shumilak; Kenneth F. Tyler (Natural Resources Research, 2017)

Losing Legacies, Ecological Release, and Transient Responses: Key Challenges for the Future of Northern Ecosystem Science - Merritt R. Turetsky; Jennifer L. Baltzer; Jill F. Johnstone; Michelle C. Mack; Kevin McCann; Edward A. G. Schuur (Ecosystems, 2017)

Raman spectroscopic analysis of the effect of the lichenicolous fungus Xanthoriicola physciae on its lichen host - Howell G.M. Edwards; Mark R.D. Seaward; Tom F. Preece; Susana E. Jorge-Villar; David L. Hawksworth (Symbiosis, 2017)

Analysis of mating system and genetic structure in the endangered, amphicarpic plant, Lewton’s polygala (Polygala lewtonii) - Joel F. Swift; Stacy A. Smith; Eric S. Menges; Burgund Bassüner; Christine E. Edwards (Conservation Genetics, 2016)

Community trait structure in phytoplankton: seasonal dynamics from a method for sparse trait data - Kyle F. Edwards (Ecology, 2016)
The distribution of functional traits in communities, and how trait distributions shift over time and space, is critical information for understanding community structure, the maintenance of diversity, and community effects on ecosystem function. It is often the case that traits tightly linked to ecological performance, such as physiological capacities, are laborious to measure and largely unknown for speciose communities; however, these traits are particularly important for unraveling the mechanistic basis of community structure. Here I develop a method combining sparse trait data with a statistical niche model to infer trait distributions for phytoplankton communities and how they vary over 10 yr in the western English Channel. I find that community‐average nitrate affinity, light‐limited growth rate, and maximum growth rate all show major seasonal patterns, reflecting alternate limitation by light vs. nitrogen. Trait diversity exhibits a variety of patterns distinct from community trait means, which suggests complex regulation of functional diversity. Patterns such as these are important for predicting how ocean ecosystems will respond to global change, and for developing trait‐based models of emergent community structure. The statistical approach used here could be applied to any kind of organism, if it exhibits strong relationships between traits and statistical niche estimates.

Chest wall motion analysis in healthy volunteers and adults with cystic fibrosis using a novel Kinect-based motion tracking system - James M. Harte; Christopher K. Golby; Johanna Acosta; Edward F. Nash; Ercihan Kiraci; Mark A. Williams; Theodoros N. Arvanitis; Babu Naidu (Medical & Biological Engineering & Computing, 2016)

Novel Method for Recruiting Representative At-Risk Individuals into Cancer Prevention Trials: Online Health Risk Assessment in Employee Wellness Programs - Siu-kuen Azor Hui; Suzanne M. Miller; Leah Hazuda; Kimberly Engelman; Edward F. Ellerbeck (Journal of Cancer Education, 2016)

Measuring Nutrition Literacy in Breast Cancer Patients: Development of a Novel Instrument - Heather D. Gibbs; Edward F. Ellerbeck; Christie Befort; Byron Gajewski; Amy R. Kennett; Qing Yu; Danielle Christifano; Debra K. Sullivan (Journal of Cancer Education, 2016)

Sub-canopy Evapotranspiration from Floating Vegetation and Open Water in a Swamp Forest - Scott T. Allen; Brandon L. Edwards; Michele L. Reba; Richard F. Keim (Wetlands, 2016)

Mapping adipose and muscle tissue expression quantitative trait loci in African Americans to identify genes for type 2 diabetes and obesity - Satria P. Sajuthi; Neeraj K. Sharma; Jeff W. Chou; Nicholette D. Palmer; David R. McWilliams; John Beal; Mary E. Comeau; Lijun Ma; Jorge Calles-Escandon; Jamehl Demons; Samantha Rogers; Kristina Cherry; et al. (Human Genetics, 2016)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Phytoplankton growth and the interaction of light and temperature: A synthesis at the species and community level - Kyle F. Edwards; Mridul K. Thomas; Christopher A. Klausmeier; Elena Litchman (Limnology and Oceanography, 2016)
Temperature strongly affects phytoplankton growth rates, but its effect on communities and ecosystem processes is debated. Because phytoplankton are often limited by light, temperature should change community structure if it affects the traits that determine competition for light. Furthermore, the aggregate response of phytoplankton communities to temperature will depend on how changes in community structure scale up to bulk rates. Here, we synthesize experiments on 57 phytoplankton species to analyze how the growth‐irradiance relationship changes with temperature. We find that light‐limited growth, light‐saturated growth, and the optimal irradiance for growth are all highly sensitive to temperature. Within a species, these traits are co‐adapted to similar temperature optima, but light‐limitation reduces a species' temperature optimum by ∼5°C, which may be an adaptation to how light and temperature covary with depth or reflect underlying physiological correlations. Importantly, the maximum achievable growth rate increases with temperature under light saturation, but not under strong light limitation. This implies that light limitation diminishes the temperature sensitivity of bulk phytoplankton growth, even though community structure will be temperature‐sensitive. Using a database of primary production incubations, we show that this prediction is consistent with estimates of bulk phytoplankton growth across gradients of temperature and irradiance in the ocean. These results indicate that interactions between temperature and resource limitation will be fundamental for explaining how phytoplankton communities and biogeochemical processes vary across temperature gradients and respond to global change.

Phytoplankton dynamics in a subtropical lake dominated by cyanobacteria: cyanobacteria ‘Like it Hot’ and sometimes dry - Akeapot Srifa; Edward J. Phlips; Mary F. Cichra; John C. Hendrickson (Aquatic Ecology, 2016)

Shrubline but not treeline advance matches climate velocity in montane ecosystems of south‐central Alaska - Roman J. Dial; T. Scott Smeltz; Patrick F. Sullivan; Christina L. Rinas; Katriina Timm; Jason E. Geck; S. Carl Tobin; Trevor S. Golden; Edward C. Berg (Global Change Biology, 2016)
Tall shrubs and trees are advancing into many tundra and wetland ecosystems but at a rate that often falls short of that predicted due to climate change. For forest, tall shrub, and tundra ecosystems in two pristine mountain ranges of Alaska, we apply a Bayesian, error‐propagated calculation of expected elevational rise (climate velocity), observed rise (biotic velocity), and their difference (biotic inertia). We show a sensitive dependence of climate velocity on lapse rate and derive biotic velocity as a rigid elevational shift. Ecosystem presence identified from recent and historic orthophotos ~50 years apart was regressed on elevation. Biotic velocity was estimated as the difference between critical point elevations of recent and historic logistic fits divided by time between imagery. For both mountain ranges, the 95% highest posterior density of climate velocity enclosed the posterior distributions of all biotic velocities. In the Kenai Mountains, mean tall shrub and climate velocities were both 2.8 m y −1 . In the better sampled Chugach Mountains, mean tundra retreat was 1.2 m y −1 and climate velocity 1.3 m y −1 . In each mountain range, the posterior mode of tall woody vegetation velocity (the complement of tundra) matched climate velocity better than either forest or tall shrub alone, suggesting competitive compensation can be important. Forest velocity was consistently low at 0.1–1.1 m y −1 , indicating treeline is advancing slowly. We hypothesize that the high biotic inertia of forest ecosystems in south‐central Alaska may be due to competition with tall shrubs and/or more complex climate controls on the elevational limits of trees than tall shrubs. Among tall shrubs, those that disperse farthest had lowest inertia. Finally, the rapid upward advance of woody vegetation may be contributing to regional declines in Dall's sheep (Ovis dalli), a poorly dispersing alpine specialist herbivore with substantial biotic inertia due to dispersal reluctance.

The harlequin ladybird, Harmonia axyridis: global perspectives on invasion history and ecology - Helen E. Roy; Peter M. J. Brown; Tim Adriaens; Nick Berkvens; Isabel Borges; Susana Clusella-Trullas; Richard F. Comont; Patrick De Clercq; Rene Eschen; Arnaud Estoup; Edward W. Evans; Benoit Facon; et al. (Biological Invasions, 2016)

A study of common scorpionfly (Mecoptera: Panorpidae) visual systems reveals the expression of a single opsin - Katie F. Manwaring; Michael F. Whiting; Edward Wilcox; Seth M. Bybee (Organisms Diversity & Evolution, 2016)

The invertebrate ecology of the Chalk aquifer in England (UK) - L. Maurice; A. R. Robertson; D. White; L. Knight; T. Johns; F. Edwards; M. Arietti; J. P. R. Sorensen; D. Weitowitz; B. P. Marchant; J. P. Bloomfield (Hydrogeology Journal, 2016)

Differences in Ecosystem Carbon Distribution and Nutrient Cycling Linked to Forest Tree Species Composition in a Mid-Successional Boreal Forest - April M. Melvin; Michelle C. Mack; Jill F. Johnstone; A. David McGuire; Helene Genet; Edward A. G. Schuur (Ecosystems, 2015)

Speciation with gene flow in whiptail lizards from a Neotropical xeric biome - Eliana F. Oliveira; Marcelo Gehara; Vinícius A. São‐Pedro; Xin Chen; Edward A. Myers; Frank T. Burbrink; Daniel O. Mesquita; Adrian A. Garda; Guarino R. Colli; Miguel T. Rodrigues; Federico J. Arias; Hussam Zaher; et al. (Molecular Ecology, 2015)
Two main hypotheses have been proposed to explain the diversification of the Caatinga biota. The riverine barrier hypothesis ( RBH ) claims that the São Francisco River ( SFR ) is a major biogeographic barrier to gene flow. The Pleistocene climatic fluctuation hypothesis ( PCH ) states that gene flow, geographic genetic structure and demographic signatures on endemic Caatinga taxa were influenced by Quaternary climate fluctuation cycles. Herein, we analyse genetic diversity and structure, phylogeographic history, and diversification of a widespread Caatinga lizard ( Cnemidophorus ocellifer ) based on large geographical sampling for multiple loci to test the predictions derived from the RBH and PCH . We inferred two well‐delimited lineages (Northeast and Southwest) that have diverged along the Cerrado–Caatinga border during the Mid‐Late Miocene (6–14 Ma) despite the presence of gene flow. We reject both major hypotheses proposed to explain diversification in the Caatinga. Surprisingly, our results revealed a striking complex diversification pattern where the Northeast lineage originated as a founder effect from a few individuals located along the edge of the Southwest lineage that eventually expanded throughout the Caatinga. The Southwest lineage is more diverse, older and associated with the Cerrado–Caatinga boundaries. Finally, we suggest that C. ocellifer from the Caatinga is composed of two distinct species. Our data support speciation in the presence of gene flow and highlight the role of environmental gradients in the diversification process.

Retrospective stable isotope analysis reveals ecosystem responses to river regulation over the last century - Thomas F. Turner; Trevor J. Krabbenhoft; Michael L. Collyer; Corey A. Krabbenhoft; Melanie S. Edwards; Zachary D. Sharp (Ecology, 2015)
Disruption of natural flow regimes, nutrient pollution, and other consequences of human population growth and development have impacted most major rivers of the world. Alarming losses of aquatic biodiversity coincide with human‐caused river alteration, but effects of biotic homogenization on aquatic ecosystem processes are not as well documented. This is because unaltered systems for comparison are scarce, and some ecosystem‐wide effects may take decades to manifest. We evaluated aquatic ecosystem responses to extensive river‐floodplain engineering and nutrient addition in the Rio Grande of southwestern North America as revealed by changes in trophic structure of, and resource availability to, the fish community. Stable Isotope Analysis (SIA) was conducted on museum‐preserved fishes collected over a 70‐year period of intensive river management and exponential human population growth. Trophic complexity and resource heterogeneity for fish consumers (measured as “isotopic niche breadth”) decreased following sediment deprivation and channelization, and these effects persist into the present. Increased nutrient inputs led to δ 15 N enrichment in the entire fish community at all affected sites, and a shift to autochthonous sources of carbon at the most proximal site downstream of wastewater release, probably via bottom‐up transfer. Overall, retrospective SIA of apex consumers suggests radical change and functional impairment of a floodplain river ecosystem already marked by significant biodiversity loss.

The checkered history of checkerboard distributions: reply - Edward F. Connor; Michael D. Collins; Daniel Simberloff (Ecology, 2015)

Aquatic vegetation mediates the relationship between hydrologic connectivity and water quality in a managed floodplain - Michael D. Kaller; Richard F. Keim; Brandon L. Edwards; A. Raynie Harlan; Tiffany E. Pasco; William E. Kelso; D. Allen Rutherford (Hydrobiologia, 2015)

The Effect of Active Pharmaceutical Ingredients on Aerosol Electrostatic Charges from Pressurized Metered Dose Inhalers - Yang Chen; Paul M. Young; David F. Fletcher; Hak Kim Chan; Edward Long; David Lewis; Tanya Church; Daniela Traini (Pharmaceutical Research, 2015)

Evidence of the St. Clair-Detroit River System as a dispersal corridor and nursery habitat for transient larval burbot - Darrin E. McCullough; Edward F. Roseman; Kevin M. Keeler; Robin L. DeBruyne; Jeremy J. Pritt; Patricia A. Thompson; Stacey Ireland; Jason E. Ross; Dustin Bowser; Robert D. Hunter; Dana Castle; Jason L. Fischer; et al. (Hydrobiologia, 2015)

Would protecting tropical forest fragments provide carbon and biodiversity cobenefits under REDD +? - Luiz Fernando S. Magnago; Ainhoa Magrach; William F. Laurance; Sebastião V. Martins; João Augusto A. Meira‐Neto; Marcelo Simonelli; David P. Edwards (Global Change Biology, 2015)
Tropical forests store vast amounts of carbon and are the most biodiverse terrestrial habitats, yet they are being converted and degraded at alarming rates. Given global shortfalls in the budgets required to prevent carbon and biodiversity loss, we need to seek solutions that simultaneously address both issues. Of particular interest are carbon‐based payments under the Reducing Emissions from Deforestation and Forest Degradation ( REDD +) mechanism to also conserve biodiversity at no additional cost. One potential is for REDD + to protect forest fragments, especially within biomes where contiguous forest cover has diminished dramatically, but we require empirical tests of the strength of any carbon and biodiversity cobenefits in such fragmented systems. Using the globally threatened Atlantic Forest landscape, we measured above‐ground carbon stocks within forest fragments spanning 13 to 23 442 ha in area and with different degrees of isolation. We related these stocks to tree community structure and to the richness and abundance of endemic and IUCN Red‐listed species. We found that increasing fragment size has a positive relationship with above‐ground carbon stock and with abundance of IUCN Red‐listed species and tree community structure. We also found negative relationships between distance from large forest block and tree community structure, endemic species richness and abundance, and IUCN Red‐listed species abundance. These resulted in positive congruence between carbon stocks and Red‐listed species, and the abundance and richness of endemic species, demonstrating vital cobenefits. As such, protecting forest fragments in hotspots of biodiversity, particularly larger fragments and those closest to sources, offers important carbon and biodiversity cobenefits. More generally, our results suggest that macroscale models of cobenefits under REDD + have likely overlooked key benefits at small scales, indicating the necessity to apply models that include finer‐grained assessments in fragmented landscapes rather than using averaged coarse‐grained cells.

Seasonal Water Column NH4 + Cycling Along a Semi-arid Sub-tropical River–Estuary Continuum: Responses to Episodic Events and Drought Conditions - Denise A. Bruesewitz; Wayne S. Gardner; Rae F. Mooney; Edward J. Buskey (Ecosystems, 2015)

Nutrient utilization traits of phytoplankton - Kyle F. Edwards; Christopher A. Klausmeier; Elena Litchman (Ecology, 2015)
This paper presents a compilation of nutrient utilization traits of marine and freshwater phytoplankton. The literature was comprehensively searched for culture experiments using nitrate, ammonium, or phosphate as the limiting nutrient. The following traits were extracted: the response of growth to nutrient supply (maximum growth rate under unlimited nutrient supply and the nutrient concentration at which growth is half‐saturated); the response of internal nutrient content to nutrient supply (the minimum subsistence quota at which growth ceases and the maximum nutrient quota under unlimited nutrient supply); and nutrient uptake kinetics for nutrient‐limited cells (maximum uptake rate and the nutrient concentration at which uptake is half‐saturated). The resulting data set includes 1319 measurements on 129 species from 138 publications. Potential uses of these data include studies of community structure and trait evolution, parameterization of ecosystem models, and biofuel development.

Coinfection with multiple strains of bovine papular stomatitis virus - Tao Huang; Edan R. Tulman; Diego G. Diel; Sushil Khatiwada; Will Sims; John F. Edwards; Xintian Wen; Gerald F. Kutish; Daniel L. Rock; Gustavo Delhon (Archives of Virology, 2015)

Neck muscle afferents influence oromotor and cardiorespiratory brainstem neural circuits - I. J. Edwards; V. K. Lall; J. F. Paton; Y. Yanagawa; G. Szabo; S. A. Deuchars; J. Deuchars (Brain Structure and Function, 2015)

Females Exceed Males in Mercury Concentrations of Burbot Lota lota - Charles P. Madenjian; Martin A. Stapanian; Peter A. Cott; David P. Krabbenhoft; William H. Edwards; Lynn M. Ogilvie; Justin G. Mychek-Londer; John F. DeWild (Archives of Environmental Contamination and Toxicology, 2015)

The Effect of Actuator Nozzle Designs on the Electrostatic Charge Generated in Pressurised Metered Dose Inhaler Aerosols - Yang Chen; Paul M. Young; David F. Fletcher; Hak Kim Chan; Edward Long; David Lewis; Tanya Church; Daniela Traini (Pharmaceutical Research, 2015)

Microbial taxonomy in the post-genomic era: Rebuilding from scratch? - Cristiane C. Thompson; Gilda R. Amaral; Mariana Campeão; Robert A. Edwards; Martin F. Polz; Bas E. Dutilh; David W. Ussery; Tomoo Sawabe; Jean Swings; Fabiano L. Thompson (Archives of Microbiology, 2015)

Evidence‐based conservation: reply to Tepedino et al. - Gretchen Lebuhn; Sam Droege; Edward F. Connor; Barbara Gemmill‐Herren; Simon G. Potts; Robert L. Minckley; Robert P. Jean; Emanuel Kula; David W. Roubik; Karen W. Wright; Gordon Frankie; Frank Parker (Conservation Biology, 2015)

Operationalizing resilience for adaptive coral reef management under global environmental change - Kenneth R.N. Anthony; Paul A. Marshall; Ameer Abdulla; Roger Beeden; Chris Bergh; Ryan Black; C. Mark Eakin; Edward T. Game; Margaret Gooch; Nicholas A.J. Graham; Alison Green; Scott F. Heron; et al. (Global Change Biology, 2015)
Cumulative pressures from global climate and ocean change combined with multiple regional and local‐scale stressors pose fundamental challenges to coral reef managers worldwide. Understanding how cumulative stressors affect coral reef vulnerability is critical for successful reef conservation now and in the future. In this review, we present the case that strategically managing for increased ecological resilience (capacity for stress resistance and recovery) can reduce coral reef vulnerability (risk of net decline) up to a point. Specifically, we propose an operational framework for identifying effective management levers to enhance resilience and support management decisions that reduce reef vulnerability. Building on a system understanding of biological and ecological processes that drive resilience of coral reefs in different environmental and socio‐economic settings, we present an Adaptive Resilience‐Based management ( ARBM ) framework and suggest a set of guidelines for how and where resilience can be enhanced via management interventions. We argue that press‐type stressors (pollution, sedimentation, overfishing, ocean warming and acidification) are key threats to coral reef resilience by affecting processes underpinning resistance and recovery, while pulse‐type (acute) stressors (e.g. storms, bleaching events, crown‐of‐thorns starfish outbreaks) increase the demand for resilience. We apply the framework to a set of example problems for Caribbean and Indo‐Pacific reefs. A combined strategy of active risk reduction and resilience support is needed, informed by key management objectives, knowledge of reef ecosystem processes and consideration of environmental and social drivers. As climate change and ocean acidification erode the resilience and increase the vulnerability of coral reefs globally, successful adaptive management of coral reefs will become increasingly difficult. Given limited resources, on‐the‐ground solutions are likely to focus increasingly on actions that support resilience at finer spatial scales, and that are tightly linked to ecosystem goods and services.

Do Defensive Chemicals Facilitate Intraguild Predation and Influence Invasion Success in Ladybird Beetles? - Yukie Kajita; John J. Obrycki; John J. Sloggett; Edward W. Evans; Kenneth F. Haynes (Journal of Chemical Ecology, 2014)

Mixed Trophic State Production Process for Microalgal Biomass with High Lipid Content for Generating Biodiesel and Biogas - Pavlo Bohutskyi; Thomas Kula; Ben A. Kessler; Yongseok Hong; Edward J. Bouwer; Michael J. Betenbaugh; F. C. Thomas Allnutt (BioEnergy Research, 2014)

Conserving the World's Finest Grassland Amidst Ambitious National Development - NYAMSUREN BATSAIKHAN; BAYARBAATAR BUUVEIBAATAR; BAZAAR CHIMED; OIDOV ENKHTUYA; DAVAA GALBRAKH; OYUNSAIKHAN GANBAATAR; BADAMJAV LKHAGVASUREN; DEJID NANDINTSETSEG; JOEL BERGER; JUSTIN M. CALABRESE; ANN E. EDWARDS; WILLIAM F. FAGAN; et al. (Conservation Biology, 2014)

Apparent environmental synergism drives the dynamics of Amazonian forest fragments - William F. Laurance; Ana S. Andrade; Ainhoa Magrach; José L. C. Camargo; Mason Campbell; Philip M. Fearnside; Will Edwards; Jefferson J. Valsko; Thomas E. Lovejoy; Susan G. Laurance (Ecology, 2014)
Many contemporary ecosystems are likely to be affected by multiple environmental drivers, complicating efforts to predict future changes in those ecosystems. We studied long‐term changes (1980–2012) in forest dynamics and liana (woody vine) abundance and biomass in fragmented and intact forests of the central Amazon. We did so by contrasting trends in 33 permanent 1‐ha plots near forest edges (plot center 2 or regional climate drivers that influence forest dynamics. Hence, the dynamics of Amazonian forest fragments cannot be understood simply as a consequence of forest fragmentation. Rather, the changes we observed appear to arise from an interaction of fragmentation with one or more global‐ or regional‐scale drivers affecting forest dynamics. Both sets of phenomena are evidently increasing forest dynamics and liana abundances in fragmented forests, changes that could reduce carbon storage and alter many aspects of forest ecology.

Direct and indirect drivers of plant diversity responses to climate and clipping across northern temperate grassland - Shannon R. White; Edward W. Bork; James F. Cahill (Ecology, 2014)
It is well known that climate can influence plant community assembly via a multitude of indirect and direct pathways. However, interpretations of plant diversity responses to simulated climate change experiments, and subsequent predictions of plant communities under future climate scenarios, rarely address the importance of indirect effects. Networks of direct and indirect effects are also critical in understanding linkages between climate and grazing, a common land use of grasslands, and implications for plant diversity. We characterized the roles of indirect vs. direct effects in determining plant diversity responses to climate and grazing using data from three northern temperate grasslands in which we conducted factorial experiments manipulating precipitation, air temperature, and clipping intensity. Utilizing a structural equation modeling framework to address the multivariate networks, we found warming operated directly, causing species loss at all sites. We identified shoot biomass as the key indirect driver of diversity loss in response to both precipitation and clipping, regardless of site. However, site‐specific contingencies in the network of interactions were important for understanding varied precipitation effects. At the driest site only, shoot biomass was resistant to reduced precipitation, and diversity was consequently unaltered. Similarly, disconnect between primary drivers and responses explained relatively idiosyncratic responses of evenness compared to richness. Importantly, the finding of widespread, directly controlled plant diversity loss with warming aligns with concerns about declining biodiversity under climate change. However, using a framework of network interactions also allowed us to pinpoint the source of variability in response across systems. Looking forward, we can use the identification of this key indirect pathway to guide an understanding of community assembly under factors likely to control shoot biomass. Viewing a multifactorial, multisite experimental approach through a framework of network interactions allowed us to both identify generalized responses and distill the complexity of contingent responses. This, along with the practical need to identify diversity responses to climate change and grazing, underscores the importance of understanding both indirect and direct drivers of ecosystem responses to global change factors.

Salt accumulation and depletion in the root-zone of the halophyte Atriplex nummularia Lindl.: influence of salinity, leaf area and plant water use - Hesham F. Alharby; Timothy D. Colmer; Edward G. Barrett-Lennard (Plant and Soil, 2014)

Towards a phylogenetic classification of reef corals: the I ndo‐ P acific genera M erulina , G oniastrea and S capophyllia ( S cleractinia, M erulinidae) - Danwei Huang; Francesca Benzoni; Roberto Arrigoni; Andrew H. Baird; Michael L. Berumen; Jessica Bouwmeester; Loke Ming Chou; Hironobu Fukami; Wilfredo Y. Licuanan; Edward R. Lovell; Rudolf Meier; Peter A. Todd; et al. (Zoologica Scripta, 2014)
Recent advances in scleractinian systematics and taxonomy have been achieved through the integration of molecular and morphological data, as well as rigorous analysis using phylogenetic methods. In this study, we continue in our pursuit of a phylogenetic classification by examining the evolutionary relationships between the closely related reef coral genera M erulina , G oniastrea , P araclavarina and S capophyllia (Merulinidae). In particular, we address the extreme polyphyly of F avites and G oniastrea that was discovered a decade ago. We sampled 145 specimens belonging to 16 species from a wide geographic range in the I ndo‐ P acific, focusing especially on type localities, including the Red Sea, western Indian Ocean and central Pacific. Tree reconstructions based on both nuclear and mitochondrial markers reveal a novel lineage composed of three species previously placed in F avites and G oniastrea . Morphological analyses indicate that this clade, P aragoniastrea H uang, B enzoni & B udd, gen. n., has a unique combination of corallite and subcorallite features observable with scanning electron microscopy and thin sections. Molecular and morphological evidence furthermore indicates that the monotypic genus Paraclavarina is nested within Merulina , and the former is therefore synonymised.

An improved approach for remotely sensing water stress impacts on forest C uptake - Daniel A. Sims; Edward R. Brzostek; Abdullah F. Rahman; Danilo Dragoni; Richard P. Phillips (Global Change Biology, 2014)
Given that forests represent the primary terrestrial sink for atmospheric CO 2 , projections of future carbon (C) storage hinge on forest responses to climate variation. Models of gross primary production ( GPP ) responses to water stress are commonly based on remotely sensed changes in canopy ‘greenness’ (e.g., normalized difference vegetation index; NDVI ). However, many forests have low spectral sensitivity to water stress ( SSWS ) – defined here as drought‐induced decline in GPP without a change in greenness. Current satellite‐derived estimates of GPP use a vapor pressure deficit ( VPD ) scalar to account for the low SWSS of forests, but fail to capture their responses to water stress. Our objectives were to characterize differences in SSWS among forested and nonforested ecosystems, and to develop an improved framework for predicting the impacts of water stress on GPP in forests with low SSWS . First, we paired two independent drought indices with NDVI data for the conterminous US from 2000 to 2011, and examined the relationship between water stress and NDVI . We found that forests had lower SSWS than nonforests regardless of drought index or duration. We then compared satellite‐derived estimates of GPP with eddy‐covariance observations of GPP in two deciduous broadleaf forests with low SSWS : the Missouri Ozark ( MO ) and Morgan Monroe State Forest ( MMSF ) AmeriFlux sites. Model estimates of GPP that used VPD scalars were poorly correlated with observations of GPP at MO ( r 2 = 0.09) and MMSF ( r 2 = 0.38). When we included the NDVI responses to water stress of adjacent ecosystems with high SSWS into a model based solely on temperature and greenness, we substantially improved predictions of GPP at MO ( r 2 = 0.83) and for a severe drought year at the MMSF ( r 2 = 0.82). Collectively, our results suggest that large‐scale estimates of GPP that capture variation in SSWS among ecosystems could improve predictions of C uptake by forests under drought.

Distinct dissolved organic matter sources induce rapid transcriptional responses in coexisting populations of P rochlorococcus , P elagibacter and the OM60 clade - Adrian K. Sharma; Jamie W. Becker; Elizabeth A. Ottesen; Jessica A. Bryant; Solange Duhamel; David M. Karl; Otto X. Cordero; Daniel J. Repeta; Edward F. DeLong (Environmental Microbiology, 2014)
Summary A considerable fraction of the E arth's organic carbon exists in dissolved form in seawater. To investigate the roles of planktonic marine microbes in the biogeochemical cycling of this dissolved organic matter ( DOM ), we performed controlled seawater incubation experiments and followed the responses of an oligotrophic surface water microbial assemblage to perturbations with DOM derived from an axenic culture of P rochlorococcus , or high‐molecular weight DOM concentrated from nearby surface waters. The rapid transcriptional responses of both P rochlorococcus and P elagibacter populations suggested the utilization of organic nitrogen compounds common to both DOM treatments. Along with these responses, both populations demonstrated decreases in gene transcripts associated with nitrogen stress, including those involved in ammonium acquisition. In contrast, responses from low abundance organisms of the NOR5/OM60 gammaproteobacteria were observed later in the experiment, and included elevated levels of gene transcripts associated with polysaccharide uptake and oxidation. In total, these results suggest that numerically dominant oligotrophic microbes rapidly acquire nitrogen from commonly available organic sources, and also point to an important role for carbohydrates found within the DOM pool for sustaining the less abundant microorganisms in these oligotrophic systems.

The Third GABLS Intercomparison Case for Evaluation Studies of Boundary-Layer Models. Part B: Results and Process Understanding - Fred C. Bosveld; Peter Baas; Gert-Jan Steeneveld; Albert A. M. Holtslag; Wayne M. Angevine; Eric Bazile; Evert I. F. de Bruijn; Daniel Deacu; John M. Edwards; Michael Ek; Vincent E. Larson; Jonathan E. Pleim; et al. (Boundary-Layer Meteorology, 2014)

The Impact of Radiation on the GABLS3 Large-Eddy Simulation through the Night and during the Morning Transition - J. M. Edwards; S. Basu; F. C. Bosveld; A. A. M. Holtslag (Boundary-Layer Meteorology, 2014)

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

Chronic water stress reduces tree growth and the carbon sink of deciduous hardwood forests - Edward R. Brzostek; Danilo Dragoni; Hans Peter Schmid; Abdullah F. Rahman; Daniel Sims; Craig A. Wayson; Daniel J. Johnson; Richard P. Phillips (Global Change Biology, 2014)
Predicted decreases in water availability across the temperate forest biome have the potential to offset gains in carbon (C) uptake from phenology trends, rising atmospheric CO 2 , and nitrogen deposition. While it is well established that severe droughts reduce the C sink of forests by inducing tree mortality, the impacts of mild but chronic water stress on forest phenology and physiology are largely unknown. We quantified the C consequences of chronic water stress using a 13‐year record of tree growth ( n = 200 trees), soil moisture, and ecosystem C balance at the Morgan–Monroe State Forest ( MMSF ) in Indiana, and a regional 11‐year record of tree growth ( n > 300 000 trees) and water availability for the 20 most dominant deciduous broadleaf tree species across the eastern and midwestern USA . We show that despite ~26 more days of C assimilation by trees at the MMSF , increasing water stress decreased the number of days of wood production by ~42 days over the same period, reducing the annual accrual of C in woody biomass by 41%. Across the deciduous forest region, water stress induced similar declines in tree growth, particularly for water‐demanding ‘mesophytic’ tree species. Given the current replacement of water‐stress adapted ‘xerophytic’ tree species by mesophytic tree species, we estimate that chronic water stress has the potential to decrease the C sink of deciduous forests by up to 17% (0.04 Pg C yr −1 ) in the coming decades. This reduction in the C sink due to mesophication and chronic water stress is equivalent to an additional 1–3 days of global C emissions from fossil fuel burning each year. Collectively, our results indicate that regional declines in water availability may offset the growth‐enhancing effects of other global changes and reduce the extent to which forests ameliorate climate warming.

Enhanced metabolic versatility of planktonic sulfur-oxidizing Î³-proteobacteria in an oxygen-deficient coastal ecosystem - Alejandro A. Murillo; Salvador RamÃrez-Flandes; Edward F. DeLong; Osvaldo Ulloa (Frontiers in Marine Science, 2014)

Exogenous phytohormones and the induction of plant galls by insects - Linnea Bartlett; Edward F. Connor (Arthropod-Plant Interactions, 2014)

Long‐term changes in liana abundance and forest dynamics in undisturbed Amazonian forests - William F. Laurance; Ana S. Andrade; Ainhoa Magrach; José L. C. Camargo; Jefferson J. Valsko; Mason Campbell; Philip M. Fearnside; Will Edwards; Thomas E. Lovejoy; Susan G. Laurance (Ecology, 2014)
Lianas (climbing woody vines) are important structural parasites of tropical trees and may be increasing in abundance in response to global‐change drivers. We assessed long‐term (∼14‐year) changes in liana abundance and forest dynamics within 36 1‐ha permanent plots spanning ∼600 km 2 of undisturbed rainforest in central Amazonia. Within each plot, we counted each liana stem (≥2 cm diameter) and measured its diameter at 1.3 m height, and then used these data to estimate liana aboveground biomass. An initial liana survey was completed in 1997–1999 and then repeated in 2012, using identical methods. Liana abundance in the plots increased by an average of 1.00% ± 0.88% per year, leading to a highly significant ( t = 6.58, df = 35, P t = 1.46, df = 35, P = 0.15; paired t tests). Liana size distributions shifted significantly (χ 2 = 191, df = 8, P We used long‐term data on rainfall and forest dynamics from our study site to test hypotheses about potential drivers of change in liana communities. Lianas generally increase with rainfall seasonality, but we found no significant trends over time (1997–2012) in five rainfall parameters (total annual rainfall, dry‐season rainfall, wet‐season rainfall, number of very dry months, CV of monthly rainfall). However, rates of tree mortality and recruitment have increased significantly over time in our plots, and general linear mixed‐effect models suggested that lianas were more abundant at sites with higher tree mortality and flatter topography. Rising concentrations of atmospheric CO 2 , which may stimulate liana growth, might also have promoted liana increases. Our findings clearly support the view that lianas are increasing in abundance in old‐growth tropical forests, possibly in response to accelerating forest dynamics and rising CO 2 concentrations. The aboveground biomass of trees was lowest in plots with abundant lianas, suggesting that lianas could reduce forest carbon storage and potentially alter forest dynamics if they continue to proliferate.

The Influence of Actuator Materials and Nozzle Designs on Electrostatic Charge of Pressurised Metered Dose Inhaler (pMDI) Formulations - Yang Chen; Paul M. Young; David F. Fletcher; Hak Kim Chan; Edward Long; David Lewis; Tanya Church; Daniela Traini (Pharmaceutical Research, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Interactions of time of day and sleep with between-session habituation and extinction memory in young adult males - Edward F. Pace-Schott; Lauren E. Tracy; Zoe Rubin; Adrian G. Mollica; Jeffrey M. Ellenbogen; Matt T. Bianchi; Mohammed R. Milad; Roger K. Pitman; Scott P. Orr (Experimental Brain Research, 2014)

Patterns of genetic diversity in the rare Erigeron lemmoni and comparison with its more widespread congener, Erigeron arisolius (Asteraceae) - Christine E. Edwards; Denise L. Lindsay; Pamela Bailey; Richard F. Lance (Conservation Genetics, 2014)

Normal eyeblink classical conditioning in patients with fixed dystonia - Sabine Janssen; Lidwien C. Veugen; Britt S. Hoffland; Panagiotis Kassavetis; Diana E. van Rooijen; Dick F. Stegeman; Mark J. Edwards; Jacobus J. van Hilten; Bart P. van de Warrenburg (Experimental Brain Research, 2014)

Phosgene Exposure: A Case of Accidental Industrial Exposure - Lewis S. Hardison; Edward Wright; Anthony F. Pizon (Journal of Medical Toxicology, 2014)

Spring-summer temperatures since AD 1780 reconstructed from stable oxygen isotope ratios in white spruce tree-rings from the Mackenzie Delta, northwestern Canada - Trevor J. Porter; Michael F. J. Pisaric; Robert D. Field; Steven V. Kokelj; Thomas W. D. Edwards; Peter deMontigny; Richard Healy; Allegra N. LeGrande (Climate Dynamics, 2014)

Longitudinal decline of lower extremity muscle power in healthy and mobility-limited older adults: influence of muscle mass, strength, composition, neuromuscular activation and single fiber contractile properties - Kieran F. Reid; Evan Pasha; Gheorghe Doros; David J. Clark; Carolynn Patten; Edward M. Phillips; Walter R. Frontera; Roger A. Fielding (European Journal of Applied Physiology, 2014)

Trophic dynamics of U, Ni, Hg and other contaminants of potential concern on the Department of Energy’s Savannah River Site - Paul G. Edwards; Karen F. Gaines; A. Lawrence Bryan; James M. Novak; Susan A. Blas (Environmental Monitoring and Assessment, 2014)

Land‐sharing versus land‐sparing logging: reconciling timber extraction with biodiversity conservation - David P. Edwards; James J. Gilroy; Paul Woodcock; Felicity A. Edwards; Trond H. Larsen; David J. R. Andrews; Mia A. Derhé; Teegan D. S. Docherty; Wayne W. Hsu; Simon L. Mitchell; Takahiro Ota; Leah J. Williams; et al. (Global Change Biology, 2014)
Selective logging is a major driver of rainforest degradation across the tropics. Two competing logging strategies are proposed to meet timber demands with the least impact on biodiversity: land sharing, which combines timber extraction with biodiversity protection across the concession; and land sparing, in which higher intensity logging is combined with the protection of intact primary forest reserves. We evaluate these strategies by comparing the abundances and species richness of birds, dung beetles and ants in Borneo, using a protocol that allows us to control for both timber yield and net profit across strategies. Within each taxonomic group, more species had higher abundances with land‐sparing than land‐sharing logging, and this translated into significantly higher species richness within land‐sparing concessions. Our results are similar when focusing only on species found in primary forest and restricted in range to Sundaland, and they are independent of the scale of sampling. For each taxonomic group, land‐sparing logging was the most promising strategy for maximizing the biological value of logging operations.

Volatile communication between plants that affects herbivory: a meta‐analysis - Richard Karban; Louie H. Yang; Kyle F. Edwards (Ecology Letters, 2014)
Volatile communication between plants causing enhanced defence has been controversial. Early studies were not replicated, and influential reviews questioned the validity of the phenomenon. We collected 48 well‐replicated studies and found overall support for the hypothesis that resistance increased for individuals with damaged neighbours. Laboratory or greenhouse studies and those conducted on agricultural crops showed stronger induced resistance than field studies on undomesticated species, presumably because other variation had been reduced. A cumulative analysis revealed that early, non‐replicated studies were more variable and showed less evidence for communication. Effects of habitat and plant growth form were undetectable. In most cases, the mechanisms of resistance and alternative hypotheses were not considered. There was no indication that some response variables were more likely to produce large effects. These results indicate that plants of diverse taxonomic affinities and ecological conditions become more resistant to herbivores when exposed to volatiles from damaged neighbours.

Classification of Forested Wetland Degradation Using Ordination of Multitemporal Reflectance - Richard F. Keim; Jason A. Zoller; DeWitt H. Braud; Brandon L. Edwards (Wetlands, 2013)

Brain responses to erotic and other emotional stimuli in breast cancer survivors with and without distress about low sexual desire: a preliminary fMRI study - Francesco Versace; Jeffrey M. Engelmann; Edward F. Jackson; Aurelija Slapin; Kristin M. Cortese; Therese B. Bevers; Leslie R. Schover (Brain Imaging and Behavior, 2013)

Discordant results between biochemical and molecular transthyretin assays: lessons learned from a unique testing algorithm at the Mayo Clinic - HONEY V. REDDI; BRITTANY C. THOMAS; KURT S. WILLKOMM; MATTHEW J. FERBER; KANDELARIA M. RUMILLA; KIMIYO M. RAYMOND; JOHN F. O’BRIEN; W. EDWARD HIGHSMITH (Journal of Genetics, 2013)

Erratum to: The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; H. John B. Birks; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; et al. (Vegetation History and Archaeobotany, 2013)

The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; Barbara A. Brayshay; et al. (Vegetation History and Archaeobotany, 2013)

Disentangling herbivore impacts on Populus tremuloides: a comparison of native ungulates and cattle in Canada’s Aspen Parkland - Edward W. Bork; Cameron N. Carlyle; James F. Cahill; Rae E. Haddow; Robert J. Hudson (Oecologia, 2013)

Parkinson disease loci in the mid-western Amish - M. F. Davis; A. C. Cummings; L. N. D’Aoust; L. Jiang; D. R. Velez Edwards; R. Laux; L. Reinhart-Mercer; D. Fuzzell; W. K. Scott; M. A. Pericak-Vance; S. L. Lee; J. L. Haines (Human Genetics, 2013)

Estuarine ecosystem function response to flood and drought in a shallow, semiarid estuary: Nitrogen cycling and ecosystem metabolism - Denise A. Bruesewitz; Wayne S. Gardner; Rae F. Mooney; Lindsey Pollard; Edward J. Buskey (Limnology and Oceanography, 2013)
We quantified sediment‐water interface and water column nitrogen (N) transformation rates seasonally over the course of a year that incorporated a major storm event and a period of prolonged riverine base flow in Copano Bay, Texas, a shallow, productive estuary in the western Gulf of Mexico. We calculated daily rates of gross primary production (GPP), community respiration (CR), and net ecosystem production (NEP) in Copano Bay to examine carbon (C) cycling over the course of the year. These metrics of estuarine ecosystem function indicated that the estuary switched from a net sink for N during floods to a net source of N during droughts while sustaining high rates of primary production throughout the year. The estuary became a net sink for N as a result of increased denitrification rates following a storm event. Both GPP and CR increased immediately following a flood event, and the system was driven to net heterotrophy. Copano Bay became a net source of N during periods of prolonged base flow via increased N fixation rates. Internal N cycling became increasingly important during periods of base flow, including increased rates of dissimilatory nitrate reduction to ammonium. This internal N cycling sustained production during periods of drought, when GPP ≈ CR. Both CR and NEP were linked to nutrient export from the inflowing rivers. N and C cycles were tightly linked but became decoupled briefly as a result of inputs of nutrients and organic matter during the period after a major storm event.

The checkered history of checkerboard distributions - Edward F. Connor; Michael D. Collins; Daniel Simberloff (Ecology, 2013)
To address the idea that the process of interspecific competition can be inferred from data on geographical distribution alone and that evidence from geographical distribution implies an important role for interspecific competition in shaping ecological communities, we reexamine the occurrence of “true checkerboard” distributions among the land and freshwater birds in three Melanesian archipelagoes: Vanuatu, the Bismarck Archipelago, and the Solomon Islands. We use the most recently published distributional records and explicitly include the geography of the distributions of species within each archipelago. We use the overlap of convex hulls to estimate the overlap in the geographic range for each pair of species in each of these archipelagoes. We define a “true checkerboard” to consist of a pair of species with exclusive island‐by‐island distributions, but that have overlapping geographical ranges. To avoid the “dilution effect,” we follow Diamond and Gilpin in focusing only on congeneric and within‐guild species pairs as potential competitors. Few, if any, “true checkerboards” exist in these archipelagoes that could possibly have been influenced by competitive interactions, and even “true checkerboards” can arise for reasons other than interspecific competition. The similarity between related species pairs (congeneric and within‐guild pairs) and unrelated species pairs in their deviation from expectation of the number of islands shared and the overlap of their geographic ranges indicates that these are not distinct statistical populations, but rather a single population of species pairs. Our result, which is based on an examination of the distributional data alone, is consistent with the interpretation that, in these avifaunas, the distributions of congeneric, within‐guild, and unrelated species pairs are shaped by a common set of biological and physical environmental processes.

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

2-epi-5-epi-Valiolone synthase activity is essential for maintaining phycobilisome composition in the cyanobacterium Anabaena variabilis ATCC 29413 when grown in the presence of a carbon source - Edward Spence; Samantha J. Bryan; Mohamed Lisfi; John Cullum; Walter C. Dunlap; J. Malcolm Shick; Conrad W. Mullineaux; Paul F. Long (Photosynthesis Research, 2013)

The Race for Space: Tracking Land-Cover Transformation in a Socio-ecological Landscape, South Africa - Kaera L. Coetzer; Barend F. N. Erasmus; Edward T. F. Witkowski; Belinda Reyers (Environmental Management, 2013)

Functional traits explain phytoplankton responses to environmental gradients across lakes of the United States - Kyle F. Edwards; Elena Litchman; Christopher A. Klausmeier (Ecology, 2013)
Ecological communities exhibit regular shifts in structure along environmental gradients, but it has proved difficult to dissect the mechanisms by which environmental conditions determine the relative success of species. Functional traits may provide a link between environmental drivers and mechanisms of community membership, but this has not been well tested for phytoplankton, which dominate primary production in many aquatic ecosystems. Here we test whether functional traits of phytoplankton can explain how species respond to gradients of light and phosphorus across U.S. lakes. We find that traits related to light utilization and maximum growth rate can predict species' differential responses to the relative availability of these resources. These results show that laboratory‐measured traits are predictive of species' performance under natural conditions, that functional traits provide a mechanistic foundation for community ecology, and that variation in community structure is predictable in spite of the complexity of ecological communities.

No evidence for cumulative effects in a Dnmt3b hypomorph across multiple generations - Neil A. Youngson; Trevor Epp; Amity R. Roberts; Lucia Daxinger; Alyson Ashe; Edward Huang; Krystal L. Lester; Sarah K. Harten; Graham F. Kay; Timothy Cox; Jacqueline M. Matthews; Suyinn Chong; et al. (Mammalian Genome, 2013)

Cigarette smoking and risk of ovarian cancer: a pooled analysis of 21 case–control studies - Mette T. Faber; Susanne K. Kjær; Christian Dehlendorff; Jenny Chang-Claude; Klaus K. Andersen; Estrid Høgdall; Penelope M. Webb; Susan J. Jordan; Mary Anne Rossing; Jennifer A. Doherty; Galina Lurie; Pamela J. Thompson; et al. (Cancer Causes & Control, 2013)

The biogeography of marine plankton traits - Andrew D. Barton; Andrew J. Pershing; Elena Litchman; Nicholas R. Record; Kyle F. Edwards; Zoe V. Finkel; Thomas Kiørboe; Ben A. Ward (Ecology Letters, 2013)
Changes in marine plankton communities driven by environmental variability impact the marine food web and global biogeochemical cycles of carbon and other elements. To predict and assess these community shifts and their consequences, ecologists are increasingly investigating how the functional traits of plankton determine their relative fitness along environmental and biological gradients. Laboratory, field and modelling studies are adopting this trait‐based approach to map the biogeography of plankton traits that underlies variations in plankton communities. Here, we review progress towards understanding the regulatory roles of several key plankton functional traits, including cell size, N 2 ‐fixation and mixotrophy among phytoplankton, and body size, ontogeny and feeding behaviour for zooplankton. The trait biogeographical approach sheds light on what structures plankton communities in the current ocean, as well as under climate change scenarios, and also allows for finer resolution of community function because community trait composition determines the rates of significant processes, including carbon export. Although understanding of trait biogeography is growing, uncertainties remain that stem, in part, from the paucity of observations describing plankton functional traits. Thus, in addition to recommending widespread adoption of the trait‐based approach, we advocate for enhanced collection, standardisation and dissemination of plankton functional trait data.

Development and Pilot Evaluation of Native CREST—a Cancer Research Experience and Student Training Program for Navajo Undergraduate Students - Christine A. Hughes; Mark C. Bauer; Bruce F. Horazdovsky; Edward R. Garrison; Christi A. Patten; Wesley O. Petersen; Clarissa N. Bowman; Robert A. Vierkant (Journal of Cancer Education, 2013)

Serum 25-hydroxyvitamin D and breast cancer in the military: a case–control study utilizing pre-diagnostic serum - Sharif B. Mohr; Edward D. Gorham; John E. Alcaraz; Christopher I. Kane; Caroline A. Macera; J. Kellogg Parsons; Deborah L. Wingard; Ronald Horst; Cedric F. Garland (Cancer Causes & Control, 2013)

Noninvasive diffusive optical imaging of the auditory response to birdsong in the zebra finch - James V. Lee; Edward L. Maclin; Kathy A. Low; Gabriele Gratton; Monica Fabiani; David F. Clayton (Journal of Comparative Physiology A, 2013)

Detecting Insect Pollinator Declines on Regional and Global Scales - Gretchen Lebuhn; Sam Droege; Edward F. Connor; Barbara Gemmill‐Herren; Simon G. Potts; Robert L. Minckley; Terry Griswold; Robert Jean; Emanuel Kula; David W. Roubik; Jim Cane; Karen W. Wright; et al. (Conservation Biology, 2013)
Recently there has been considerable concern about declines in bee communities in agricultural and natural habitats. The value of pollination to agriculture, provided primarily by bees, is >$200 billion/year worldwide, and in natural ecosystems it is thought to be even greater. However, no monitoring program exists to accurately detect declines in abundance of insect pollinators; thus, it is difficult to quantify the status of bee communities or estimate the extent of declines. We used data from 11 multiyear studies of bee communities to devise a program to monitor pollinators at regional, national, or international scales. In these studies, 7 different methods for sampling bees were used and bees were sampled on 3 different continents. We estimated that a monitoring program with 200–250 sampling locations each sampled twice over 5 years would provide sufficient power to detect small (2–5%) annual declines in the number of species and in total abundance and would cost U.S.$2,000,000. To detect declines as small as 1% annually over the same period would require >300 sampling locations. Given the role of pollinators in food security and ecosystem function, we recommend establishment of integrated regional and international monitoring programs to detect changes in pollinator communities. Detección de Declinaciones de Insectos Polinizadores a Escalas Regional y Global

A genome-wide association study of breast cancer in women of African ancestry - Fang Chen; Gary K. Chen; Daniel O. Stram; Robert C. Millikan; Christine B. Ambrosone; Esther M. John; Leslie Bernstein; Wei Zheng; Julie R. Palmer; Jennifer J. Hu; Tim R. Rebbeck; Regina G. Ziegler; et al. (Human Genetics, 2013)

Prospective study of effect modification by Toll-like receptor 4 variation on the association between Trichomonas vaginalis serostatus and prostate cancer - Yen Ching Chen; Yi Ling Huang; Elizabeth A. Platz; John F. Alderete; Lu Zheng; Jennifer R. Rider; Peter Kraft; Edward Giovannucci; Siobhan Sutcliffe (Cancer Causes & Control, 2013)

Trait-dependent declines of species following conversion of rain forest to oil palm plantations - Michael J. M. Senior; Keith C. Hamer; Simon Bottrell; David P. Edwards; Tom M. Fayle; Jennifer M. Lucey; Peter J. Mayhew; Robert Newton; Kelvin S.-H. Peh; Frederick H. Sheldon; Christopher Stewart; Alison R. Styring; et al. (Biodiversity and Conservation, 2013)

Functional traits explain phytoplankton community structure and seasonal dynamics in a marine ecosystem - Kyle F. Edwards; Elena Litchman; Christopher A. Klausmeier (Ecology Letters, 2013)
A fundamental yet elusive goal of ecology is to predict the structure of communities from the environmental conditions they experience. Trait‐based approaches to terrestrial plant communities have shown that functional traits can help reveal the mechanisms underlying community assembly, but such approaches have not been tested on the microbes that dominate ecosystem processes in the ocean. Here, we test whether functional traits can explain community responses to seasonal environmental fluctuation, using a time series of the phytoplankton of the English Channel. We show that interspecific variation in response to major limiting resources, light and nitrate, can be well‐predicted by lab‐measured traits characterising light utilisation, nitrate utilisation and maximum growth rate. As these relationships were predicted a priori , using independently measured traits, our results show that functional traits provide a strong mechanistic foundation for understanding the structure and dynamics of ecological communities.

Microstructure characteristics during hydrate formation and dissociation revealed by X-ray tomographic microscopy - Stephan A. Klapp; Frieder Enzmann; Peter Walz; Thomas Huthwelker; Jürgen Tuckermann; J.-Oliver Schwarz; Thomas Pape; Edward T. Peltzer; Rajmund Mokso; David Wangner; Federica Marone; Michael Kersten; et al. (Geo-Marine Letters, 2012)

Isolation and characterization of microsatellite loci for a hyper-rare cliff endemic, Erigeron lemmonii, and a more widespread congener, Erigeron arisolius (Asteraceae) - Denise L. Lindsay; Pamela Bailey; Joseph L. Anderson; Michael G. Jung; Christine E. Edwards; Richard F. Lance (Conservation Genetics Resources, 2012)

The mechanism of gall induction makes galls red - Edward F. Connor; Linnea Bartlett; Sean O’Toole; Steven Byrd; Kevin Biskar; Jessica Orozco (Arthropod-Plant Interactions, 2012)

Integrating Climate and Ocean Change Vulnerability into Conservation Planning - Elizabeth McLeod; Alison Green; Edward Game; Kenneth Anthony; Joshua Cinner; Scott F. Heron; Joanie Kleypas; Catherine E. Lovelock; John M. Pandolfi; Robert L. Pressey; Rodney Salm; Steve Schill; et al. (Coastal Management, 2012)

Oxygen minimum zones harbour novel viral communities with low diversity - Noriko Cassman; Alejandra Prieto‐Davó; Kevin Walsh; Genivaldo G. Z. Silva; Florent Angly; Sajia Akhter; Katie Barott; Julia Busch; Tracey McDole; J. Matthew Haggerty; Dana Willner; Gadiel Alarcón; et al. (Environmental Microbiology, 2012)
Summary Oxygen minimum zones ( OMZs ) are oceanographic features that affect ocean productivity and biodiversity, and contribute to ocean nitrogen loss and greenhouse gas emissions. Here we describe the viral communities associated with the E astern T ropical S outh P acific ( ETSP ) OMZ off I quique, C hile for the first time through abundance estimates and viral metagenomic analysis. The viral‐to‐microbial ratio ( VMR ) in the ETSP OMZ fluctuated in the oxycline and declined in the anoxic core to below one on several occasions. The number of viral genotypes (unique genomes as defined by sequence assembly) ranged from 2040 at the surface to 98 in the oxycline, which is the lowest viral diversity recorded to date in the ocean. Within the ETSP OMZ viromes, only 4.95% of genotypes were shared between surface and anoxic core viromes using reciprocal BLASTn sequence comparison. ETSP virome comparison with surface marine viromes ( S argasso S ea, G ulf of M exico, K ingman R eef, C hesapeake B ay) revealed a dissimilarity of ETSP OMZ viruses to those from other oceanic regions. From the 1.4 million non‐redundant DNA sequences sampled within the altered oxygen conditions of the ETSP OMZ , more than 97.8% were novel. Of the average 3.2% of sequences that showed similarity to the SEED non‐redundant database, phage sequences dominated the surface viromes, eukaryotic virus sequences dominated the oxycline viromes, and phage sequences dominated the anoxic core viromes. The viral community of the ETSP OMZ was characterized by fluctuations in abundance, taxa and diversity across the oxygen gradient. The ecological significance of these changes was difficult to predict; however, it appears that the reduction in oxygen coincides with an increased shedding of eukaryotic viruses in the oxycline, and a shift to unique viral genotypes in the anoxic core.

DNA from soil mirrors plant taxonomic and growth form diversity - N. G. YOCCOZ; K. A. BRÅTHEN; L. GIELLY; J. HAILE; M. E. EDWARDS; T. GOSLAR; H. Von STEDINGK; A. K. BRYSTING; E. COISSAC; F. POMPANON; J. H. SØNSTEBØ; C. MIQUEL; et al. (Molecular Ecology, 2012)
Ecosystems across the globe are threatened by climate change and human activities. New rapid survey approaches for monitoring biodiversity would greatly advance assessment and understanding of these threats. Taking advantage of next‐generation DNA sequencing, we tested an approach we call metabarcoding: high‐throughput and simultaneous taxa identification based on a very short (usually

Simplifying the savanna: the trajectory of fire‐sensitive vegetation mosaics in northern Australia - Jeremy Russell‐Smith; Andrew C. Edwards; Owen F. Price (Journal of Biogeography, 2012)
Aim Fire is a key agent in savanna systems, yet the capacity to predict fine‐grained population phenomena under variable fire regime conditions at landscape scales is a daunting challenge. Given mounting evidence for significant impacts of fire on vulnerable biodiversity elements in north Australian savannas over recent decades, we assess: (1) the trajectory of fire‐sensitive vegetation elements within a particularly biodiverse savanna mosaic based on long‐term monitoring and spatial modelling; (2) the broader implications for northern Australia; and (3) the applicability of the methodological approach to other fire‐prone settings. Location Arnhem Plateau, northern Australia. Methods We apply data from long‐term vegetation monitoring plots included within Kakadu National Park to derive statistical models describing the responses of structure and floristic attributes to 15 years of ambient (non‐experimental) fire regime treatments. For a broader 28,000 km 2 region, we apply significant models to spatial assessment of the effects of modern fire regimes (1995–2009) on diagnostic closed forest, savanna and shrubland heath attributes. Results Significant models included the effects of severe fires on large stems of the closed forest dominant Allosyncarpia ternata , stem densities of the widespread savanna coniferous obligate seeder Callitris intratropica , and fire frequency and related fire interval parameters on numbers of obligate seeder taxa characteristic of shrubland heaths. No significant relationships were observed between fire regime and eucalypt and non‐eucalypt adult tree components of savanna. Spatial application of significant models illustrates that more than half of the regional closed forest perimeters, savanna and shrubland habitats experienced deleterious fire regimes over the study period, except in very dissected terrain. Main conclusions While north Australia’s relatively unmodified mesic savannas may appear structurally intact and healthy, this study provides compelling evidence that fire‐sensitive vegetation elements embedded within the savanna mosaic are in decline under present‐day fire regimes. These observations have broader implications for analogous savanna mosaics across northern Australia, and support complementary findings of the contributory role of fire regimes in the demise of small mammal fauna. The methodological approach has application in other fire‐prone settings, but is reliant on significant long‐term infrastructure resourcing.

Microbial community phylogenetic and trait diversity declines with depth in a marine oxygen minimum zone - Jessica A. Bryant; Frank J. Stewart; John M. Eppley; Edward F. DeLong (Ecology, 2012)
Oxygen minimum zones (OMZs) are natural physical features of the world's oceans. They create steep physiochemical gradients in the water column, which most notably include a dramatic draw down in oxygen concentrations over small vertical distances (

Muscle power failure in mobility-limited older adults: preserved single fiber function despite lower whole muscle size, quality and rate of neuromuscular activation - Kieran F. Reid; Gheorghe Doros; David J. Clark; Carolynn Patten; Robert J. Carabello; Gregory J. Cloutier; Edward M. Phillips; Lisa S. Krivickas; Walter R. Frontera; Roger A. Fielding (European Journal of Applied Physiology, 2012)

Phosphite utilization by the marine picocyanobacterium Prochlorococcus MIT9301 - Asunción Martínez; Marcia S. Osburne; Adrian K. Sharma; Edward F. DeLong; Sallie W. Chisholm (Environmental Microbiology, 2012)
Summary Primary productivity in the ocean's oligotrophic regions is often limited by phosphorus (P) availability. In low phosphate environments, the prevalence of many genes involved in P acquisition is elevated, suggesting that the ability to effectively access diverse P sources is advantageous for organisms inhabiting these regions. Prochlorococcus, the numerically dominant primary producer in the oligotrophic ocean, encodes high‐affinity P transporters, P regulatory proteins and enzymes for organic phosphate utilization, but its ability to use reduced P compounds has not been previously demonstrated. Because Prochlorococcus strain MIT9301 encodes genes similar to phnY and phnZ , which constitute a novel marine bacterial 2‐aminoethylphosphonate (2‐AEPn) utilization pathway, it has been suggested that this organism might use 2‐AEPn as an alternative P source. We show here that although MIT9301 was unable to use 2‐AEPn as a sole P source under standard culture conditions, it was able to use phosphite. Phosphite utilization by MIT9301 appears to be mediated by an NAD‐dependent phosphite dehydrogenase encoded by ptxD . We show that phosphite utilization genes are present in diverse marine microbes and that their abundance is higher in low‐P waters. These results strongly suggest that phosphite represents a previously unrecognized component of the marine P cycle.

Examining the effects of former cannabis use on cerebellum-dependent eyeblink conditioning in humans - Adam B. Steinmetz; Chad R. Edwards; Jennifer M. Vollmer; Molly A. Erickson; Brian F. O’Donnell; William P. Hetrick; Patrick D. Skosnik (Psychopharmacology, 2012)

Breeding success of four male life history types of spring Chinook Salmon spawning in an artificial stream - Steve L. Schroder; Curtis M. Knudsen; Todd N. Pearsons; Todd W. Kassler; Edward P. Beall; Sewall F. Young; David E. Fast (Environmental Biology of Fishes, 2012)

Allometric scaling and taxonomic variation in nutrient utilization traits and maximum growth rate of phytoplankton - Kyle F. Edwards; Mridul K. Thomas; Christopher A. Klausmeier; Elena Litchman (Limnology and Oceanography, 2012)
Nutrient utilization traits can be used to link the ecophysiology of phytoplankton to population dynamic models and the structure of communities across environmental gradients. Here we analyze a comprehensive literature compilation of four traits: maximum nutrient uptake rate; the half‐saturation constant for nutrient uptake; the minimum subsistence quota, measured for nitrate and phosphate; and maximum growth rate. We also use these traits to analyze two composite traits, uptake affinity and scaled uptake affinity. All traits tend to increase with cell volume, except for scaled uptake affinity and maximum growth rate, which tend to decline with cell volume. Most scaling relationships are the same for freshwater and marine species, although important differences exist. Most traits differ on average between major taxa, but between‐taxon variation is nearly always due to between‐taxon variation in volume. There is some evidence for between‐trait correlations that could constrain trait evolution, but these correlations are difficult to disentangle from correlation driven by cell volume. These results should enhance the parameterization of models that use size or taxonomic group to structure physiological variation in phytoplankton communities.

Drug-induced sleep: theoretical and practical considerations - Jeffrey M. Ellenbogen; Edward F. Pace-Schott (Pflügers Archiv - European Journal of Physiology, 2012)

Effects of biotic disturbances on forest carbon cycling in the U nited S tates and C anada - Jeffrey A. Hicke; Craig D. Allen; Ankur R. Desai; Michael C. Dietze; Ronald J. Hall; Edward H. (Ted) Hogg; Daniel M. Kashian; David Moore; Kenneth F. Raffa; Rona N. Sturrock; James Vogelmann (Global Change Biology, 2012)
Forest insects and pathogens are major disturbance agents that have affected millions of hectares in N orth A merica in recent decades, implying significant impacts to the carbon ( C ) cycle. Here, we review and synthesize published studies of the effects of biotic disturbances on forest C cycling in the U nited S tates and C anada. Primary productivity in stands was reduced, sometimes considerably, immediately following insect or pathogen attack. After repeated growth reductions caused by some insects or pathogens or a single infestation by some bark beetle species, tree mortality occurred, altering productivity and decomposition. In the years following disturbance, primary productivity in some cases increased rapidly as a result of enhanced growth by surviving vegetation, and in other cases increased slowly because of lower forest regrowth. In the decades following tree mortality, decomposition increased as a result of the large amount of dead organic matter. Net ecosystem productivity decreased immediately following attack, with some studies reporting a switch to a C source to the atmosphere, and increased afterward as the forest regrew and dead organic matter decomposed. Large variability in C cycle responses arose from several factors, including type of insect or pathogen, time since disturbance, number of trees affected, and capacity of remaining vegetation to increase growth rates following outbreak. We identified significant knowledge gaps, including limited understanding of carbon cycle impacts among different biotic disturbance types (particularly pathogens), their impacts at landscape and regional scales, and limited capacity to predict disturbance events and their consequences for carbon cycling. We conclude that biotic disturbances can have major impacts on forest C stocks and fluxes and can be large enough to affect regional C cycling. However, additional research is needed to reduce the uncertainties associated with quantifying biotic disturbance effects on the N orth A merican C budget.

Transcriptional responses of surface water marine microbial assemblages to deep‐sea water amendment - Yanmei Shi; Jay McCarren; Edward F. DeLong (Environmental Microbiology, 2012)
Summary Deep‐water nutrient injection in the North Pacific Subtropical Gyre provides an aperiodic yet significant source of inorganic nutrients to the nutrient‐limiting surface waters, and has been implicated in phytoplankton bloom formation. Here we examined short‐term transcriptional responses of surface water picoplankton assemblages in a deep‐sea water (DSW) mixing experiment. Both flow cytometric and transcriptomic analysis indicated stimulation of an Alteromonas ‐like population in the DSW‐amended treatment after 12 h, relative to the control. Among the highly expressed alteromonad transcripts in DSW‐treated samples, those encoding genes associated with chemotaxis, cell motility and carbon metabolism were most highly represented, relative to the control. Similarly, Prochlorococcus showed significantly higher levels of transcripts associated with carbon fixation and photosynthesis, as well as slightly increased cell density, relative to the control. Although other microbial taxa did not exhibit enhanced growth, DSW‐stimulated changes in their genome‐wide transcriptional profiles were still readily detectable. Cell‐associated cyanophage DNA and cDNA profiles suggested DSW stimulation of phage‐mediated cell lysis, in previously infected cells. Comparison of the DSW‐responsive Alteromonas populations, to previously reported dissolved organic matter (DOM)‐responding alteromonads (), revealed differential transcript abundances, predominantly among genes encoding mobile elements and phage‐related genes. Transcript representation in other metabolic pathways differed significantly between Alteromonas populations in the two different treatments, suggesting perturbation‐specific metabolic responses to DSW and DOM. In total, the results provide new insight into short‐term responses of picoplankton to DSW mixing, which occur prior to the more well‐studied, longer‐term growth responses of larger phytoplankton species.

Microbial metatranscriptomics in a permanent marine oxygen minimum zone - Frank J. Stewart; Osvaldo Ulloa; Edward F. DeLong (Environmental Microbiology, 2012)
Summary Simultaneous characterization of taxonomic composition, metabolic gene content and gene expression in marine oxygen minimum zones (OMZs) has potential to broaden perspectives on the microbial and biogeochemical dynamics in these environments. Here, we present a metatranscriptomic survey of microbial community metabolism in the Eastern Tropical South Pacific OMZ off northern Chile. Community RNA was sampled in late austral autumn from four depths (50, 85, 110, 200 m) extending across the oxycline and into the upper OMZ. Shotgun pyrosequencing of cDNA yielded 180 000 to 550 000 transcript sequences per depth. Based on functional gene representation, transcriptome samples clustered apart from corresponding metagenome samples from the same depth, highlighting the discrepancies between metabolic potential and actual transcription. BLAST‐based characterizations of non‐ribosomal RNA sequences revealed a dominance of genes involved with both oxidative (nitrification) and reductive (anammox, denitrification) components of the marine nitrogen cycle. Using annotations of protein‐coding genes as proxies for taxonomic affiliation, we observed depth‐specific changes in gene expression by key functional taxonomic groups. Notably, transcripts most closely matching the genome of the ammonia‐oxidizing archaeon Nitrosopumilus maritimus dominated the transcriptome in the upper three depths, representing one in five protein‐coding transcripts at 85 m. In contrast, transcripts matching the anammox bacterium Kuenenia stuttgartiensis dominated at the core of the OMZ (200 m; 1 in 12 protein‐coding transcripts). The distribution of N. maritimus ‐like transcripts paralleled that of transcripts matching ammonia monooxygenase genes, which, despite being represented by both bacterial and archaeal sequences in the community DNA, were dominated (> 99%) by archaeal sequences in the RNA, suggesting a substantial role for archaeal nitrification in the upper OMZ. These data, as well as those describing other key OMZ metabolic processes (e.g. sulfur oxidation), highlight gene‐specific expression patterns in the context of the entire community transcriptome, as well as identify key functional groups for taxon‐specific genomic profiling.

Characteristics of Norway spruce trees (Picea abies) surviving a spruce bark beetle (Ips typographus L.) outbreak - R. Jakuš; M. Edwards-Jonášová; P. Cudlín; M. Blaženec; M. Ježík; F. Havlíček; Ivo Moravec (Trees, 2011)

Monitoring the mission blue butterfly using immature stages - Summer Lindzey; Edward F. Connor (Journal of Insect Conservation, 2011)

BMP4 loss-of-function mutations in developmental eye disorders including SHORT syndrome - Linda M. Reis; Rebecca C. Tyler; Kala F. Schilter; Omar Abdul-Rahman; Jeffrey W. Innis; Beth A. Kozel; Adele S. Schneider; Tanya M. Bardakjian; Edward J. Lose; Donna M. Martin; Ulrich Broeckel; Elena V. Semina (Human Genetics, 2011)

Indoor Air Polychlorinated Biphenyl Concentrations in Three Communities Along the Upper Hudson River, New York - Lloyd R. Wilson; Patrick M. Palmer; Erin E. Belanger; Michael R. Cayo; Lorie A. Durocher; Syni-An A. Hwang; Edward F. Fitzgerald (Archives of Environmental Contamination and Toxicology, 2011)

Influence of ley duration on the yield and quality of the subsequent cereal crop (spring oats) in an organically managed long-term crop rotation experiment - C. A. Watson; J. A. Baddeley; A. C. Edwards; R. M. Rees; R. L. Walker; C. F. E. Topp (Organic Agriculture, 2011)

Alien arthropod predators and parasitoids: interactions with the environment - Edward W. Evans; Richard F. Comont; Wolfgang Rabitsch (BioControl, 2011)

Large herbivores may alter vegetation structure of semi-arid savannas through soil nutrient mediation - Cornelis van der Waal; Ada Kool; Seline S. Meijer; Edward Kohi; Ignas M. A. Heitkönig; Willem F. de Boer; Frank van Langevelde; Rina C. Grant; Mike J. S. Peel; Rob Slotow; Henrik J. de Knegt; Herbert H. T. Prins; et al. (Oecologia, 2011)

The transcriptomic responses of the eastern oyster, Crassostrea virginica , to environmental conditions - ROBERT W. CHAPMAN; ANNALAURA MANCIA; MARION BEAL; ARTUR VELOSO; CHARLES RATHBURN; ANNE BLAIR; A. F. HOLLAND; G. W. WARR; GUY DIDINATO; INNA M. SOKOLOVA; EDWARD F. WIRTH; EDWARD DUFFY; et al. (Molecular Ecology, 2011)
Understanding the mechanisms by which organisms adapt to environmental conditions is a fundamental question for ecology and evolution. In this study, we evaluate changes in gene expression of a marine mollusc, the eastern oyster Crassostrea virginica , associated with the physico‐chemical conditions and the levels of metals and other contaminants in their environment. The results indicate that transcript signatures can effectively disentangle the complex interactive gene expression responses to the environment and are also capable of disentangling the complex dynamic effects of environmental factors on gene expression. In this context, the mapping of environment to gene and gene to environment is reciprocal and mutually reinforcing. In general, the response of transcripts to the environment is driven by major factors known to affect oyster physiology such as temperature, pH, salinity, and dissolved oxygen, with pollutant levels playing a relatively small role, at least within the range of concentrations found in the studied oyster habitats. Further, the two environmental factors that dominate these effects (temperature and pH) interact in a dynamic and nonlinear fashion to impact gene expression. Transcriptomic data obtained in our study provide insights into the mechanisms of physiological responses to temperature and pH in oysters that are consistent with the known effects of these factors on physiological functions of ectotherms and indicate important linkages between transcriptomics and physiological outcomes. Should these linkages hold in further studies and in other organisms, they may provide a novel integrated approach for assessing the impacts of climate change, ocean acidification and anthropogenic contaminants on aquatic organisms via relatively inexpensive microarray platforms.

Mathematizing Darwin - A. W. F. Edwards (Behavioral Ecology and Sociobiology, 2011)

Reducing seabird strikes with trawl cables in the pollock catcher-processor fleet in the eastern Bering Sea - Edward F. Melvin; Kimberly S. Dietrich; Shannon Fitzgerald; Tamre Cardoso (Polar Biology, 2011)

Salinity and Chlorophyll a as Performance Measures to Rehabilitate a Mangrove-Dominated Deltaic Coastal Region: the Ciénaga Grande de Santa Marta–Pajarales Lagoon Complex, Colombia - Victor H. Rivera-Monroy; Robert R. Twilley; J. Ernesto Mancera-Pineda; Christopher J. Madden; Ariel Alcantara-Eguren; E. Barry Moser; Bror F. Jonsson; Edward Castañeda-Moya; Oscar Casas-Monroy; Paola Reyes-Forero; Jorge Restrepo (Estuaries and Coasts, 2011)

Time‐series analyses of Monterey Bay coastal microbial picoplankton using a ‘genome proxy’ microarray - Virginia I. Rich; Vinh D. Pham; John Eppley; Yanmei Shi; Edward F. DeLong (Environmental Microbiology, 2011)
Summary To investigate the temporal, spatial and phylogenetic resolution of marine microbial community structure and variability, we designed and expanded a genome proxy array (an oligonucleotide microarray targeting marine microbial genome fragments and genomes), evaluated it against metagenomic sequencing, and applied it to time‐series samples from the Monterey Bay. The expanded array targeted 268 microbial genotypes across much of the known diversity of cultured and uncultured marine microbes. The target abundances measured by the array were highly correlated to pyrosequence‐based abundances (linear regression R 2 = 0.85–0.91, P

Fine mapping QMi-C11 a major QTL controlling root-knot nematodes resistance in Upland cotton - Xinlian Shen; Yajun He; Edward L. Lubbers; Richard F. Davis; Robert L. Nichols; Peng W. Chee (Theoretical and Applied Genetics, 2010)

Intakes of vitamins A, C, and E and use of multiple vitamin supplements and risk of colon cancer: a pooled analysis of prospective cohort studies - Yikyung Park; Donna Spiegelman; David J. Hunter; Demetrius Albanes; Leif Bergkvist; Julie E. Buring; Jo L. Freudenheim; Edward Giovannucci; R. Alexandra Goldbohm; Lisa Harnack; Ikuko Kato; Vittorio Krogh; et al. (Cancer Causes & Control, 2010)

Multivariate trade‐offs, succession, and phenological differentiation in a guild of colonial invertebrates - Kyle F. Edwards; John J. Stachowicz (Ecology, 2010)
For competing species limited by one or few resources, diversity is thought to be maintained by trade‐offs that allow niche differentiation without resource partitioning. However, few studies have quantified multiple key traits for each species in a guild and shown that trade‐offs among these traits apply across the guild. Here we document strong bivariate and multivariate relationships among growth rate, fecundity, longevity, and overgrowth ability for six co‐occurring colonial invertebrates. We find that all four of these traits are constrained to a single “fast–slow” niche axis that mechanistically relates life history variation to a colonization–competition trade‐off. The location of species on this axis strongly predicts the timing of their peak abundance during succession. We also find that species closer to each other on the fast–slow axis are more likely to differ in reproductive phenology, suggesting a secondary dimension of niche differentiation for otherwise similar species.

Alcohol intake and pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium (PanScan) - Dominique S. Michaud; Alina Vrieling; Li Jiao; Julie B. Mendelsohn; Emily Steplowski; Shannon M. Lynch; Jean Wactawski-Wende; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Charles S. Fuchs; Myron Gross; Kathy Helzlsouer; et al. (Cancer Causes & Control, 2010)

The contribution of N 2 O to the greenhouse gas balance of first‐generation biofuels - EDWARD M.W. SMEETS; LEX F. BOUWMAN; ELKE STEHFEST; DETLEF P. VAN VUUREN; ADAM POSTHUMA (Global Change Biology, 2010)

Symbiosis research, technology, and education: Proceedings of the 6th International Symbiosis Society Congress held in Madison Wisconsin, USA, August 2009 - Heidi Goodrich-Blair; Jean-Michel Ané; James D. Bever; Seth R. Bordenstein; Monika Bright; John M. Chaston; Keith Clay; Cameron R. Currie; Angela E. Douglas; Nicole Gerardo; Maria J. Harrison; Ruth E. Ley; et al. (Symbiosis, 2010)

Rice fields to prawn farms: a blue revolution in southwest Bangladesh? - Nesar Ahmed; Edward H. Allison; James F. Muir (Aquaculture International, 2010)

Immobilizing nitrogen to control plant invasion - Laura G. Perry; Dana M. Blumenthal; Thomas A. Monaco; Mark W. Paschke; Edward F. Redente (Oecologia, 2010)

Effects of the Purkinje System and Cardiac Geometry on Biventricular Pacing: A Model Study - Daniel Romero; Rafael Sebastian; Bart H. Bijnens; Viviana Zimmerman; Patrick M. Boyle; Edward J. Vigmond; Alejandro F. Frangi (Annals of Biomedical Engineering, 2010)

Population synchrony of a native fish across three Laurentian Great Lakes: evaluating the effects of dispersal and climate - David B. Bunnell; Jean V. Adams; Owen T. Gorman; Charles P. Madenjian; Stephen C. Riley; Edward F. Roseman; Jeffrey S. Schaeffer (Oecologia, 2010)

Conserved synteny at the protein family level reveals genes underlying Shewanella species’ cold tolerance and predicts their novel phenotypes - Tatiana V. Karpinets; Anna Y. Obraztsova; Yanbing Wang; Denise D. Schmoyer; Guruprasad H. Kora; Byung H. Park; Margrethe H. Serres; Margaret F. Romine; Miriam L. Land; Terence B. Kothe; Jim K. Fredrickson; Kenneth H. Nealson; et al. (Functional & Integrative Genomics, 2010)

Abundances of crenarchaeal amoA genes and transcripts in the Pacific Ocean - Matthew J. Church; Brenner Wai; David M. Karl; Edward F. DeLong (Environmental Microbiology, 2010)
Summary Planktonic Crenarchaea are thought to play a key role in chemolithotrophic ammonia oxidation, a critical step of the marine nitrogen (N) cycle. In this study, we examined the spatial distributions of ammonia‐oxidizing Crenarchaea across a large (∼5200 km) region of the central Pacific Ocean. Examination of crenarchaeal 16S rRNA, ammonia monooxygenase subunit A ( amoA ) genes, and amoA transcript abundances provided insight into their spatial distributions and activities. Crenarchaeal gene abundances increased three to four orders of magnitude with depth between the upper ocean waters and dimly lit waters of the mesopelagic zone. The resulting median value of the crenarchaeal amoA : 16S rRNA gene ratio was 1.3, suggesting the majority of Crenarchaea in the epi‐ and mesopelagic regions of the Pacific Ocean have the metabolic machinery for ammonia oxidation. Crenarchaeal amoA transcript abundances typically increased one to two orders of magnitude in the transitional zone separating the epipelagic waters from the mesopelagic (100–200 m), before decreasing into the interior of the mesopelagic zone. The resulting gene copy normalized transcript abundances revealed elevated amoA expression in the upper ocean waters (0–100 m) where crenarchaeal abundances were low, with transcripts decreasing into the mesopelagic zone as crenarchaeal gene abundances increased. These results suggest ammonia‐oxidizing Crenarchaea are active contributors to the N cycle throughout the epi‐ and mesopelagic waters of the Pacific Ocean.

Assessing the productivity of indigenous chickens in an extensive management system in southern Nyanza, Kenya - Portas Odula Olwande; William O. Ogara; Samwel O. Okuthe; Gerald Muchemi; Edward Okoth; Maurice O. Odindo; Rubin F. Adhiambo (Tropical Animal Health and Production, 2010)

A near‐annual palaeohydrological study based on testate amoebae from a sub‐alpine mire: surface wetness and the role of climate during the instrumental period - Mariusz Lamentowicz; Willem Van Der Knaap; Łukasz Lamentowicz; Jacqueline F. N. Van Leeuwen; Edward A. D. Mitchell; Tomasz Goslar; Christian Kamenik (Journal of Quaternary Science, 2010)
We present the first testate amoeba‐based palaeohydrological reconstruction from the Swiss Alps, and the first depth to the water table (DWT) calibration dataset for this region. Compared to existing models, our new calibration dataset performs well (RMSEP = 4.88), despite the length of the water table gradient covered (53 cm). The present‐day topography and vegetation of the study mire Mauntschas suggest that it is partly ombrotrophic (large Sphagnum fuscum hummocks, one of which was the coring site) but mostly under the minerotrophic influence of springs in the mire and runoff from the surrounding area. Ombrotrophic Sphagnum fuscum hummocks developed at the sampling site only during the last 50 years, when testate amoebae indicate a shift towards dry and/or acid conditions. Prior to AD 1950 the water table was much higher, suggesting that the influence of the mineral‐rich water prevented the development of ombrotrophic hummocks. The reconstructed DWT correlated with Pinus cembra pollen accumulation rates, suggesting that testate amoebae living on the mire and P. cembra growing outside of it partly respond to the same factor(s). Finally, temperature trends from the nearby meteorological station paralleled trends in reconstructed DWT. However, contrary to other studies made on raised bogs of northwestern Europe, the highest correlation was observed for winter temperature, despite the fact that testate amoebae would more logically respond to moisture conditions during the growing season. The observed correlation with winter temperature might reflect a control of winter severity on surface moisture during at least the first part of the growing season, through snow melt and soil frost phenomena influencing run‐off. More ecohydrological work on sub‐alpine mires is needed to understand the relationships between climate, testate amoebae and peatland development. Copyright © 2009 John Wiley & Sons, Ltd.

Prey diversity is associated with weaker consumer effects in a meta‐analysis of benthic marine experiments - Kyle F. Edwards; Kristin M. Aquilino; Rebecca J. Best; Kirsten L. Sellheim; John J. Stachowicz (Ecology Letters, 2010)
Ecology Letters (2010) 13: 194–201 Abstract A rapidly accumulating body of research has shown that species diversity consistently affects the functioning of ecosystems. The incorporation of trophic complexity and the extension of this research to larger scales and natural ranges in species diversity remain as important challenges for understanding the true magnitude of these effects in natural systems. Here, we test whether the diversity of prey communities affects the magnitude of aggregate consumer effects. We conducted a meta‐analysis of 57 consumer removal field experiments from a range of intertidal and subtidal hard substrate marine communities. We found that the richness of the prey community was the strongest predictor of the magnitude of consumer effects while controlling for habitat type, taxonomic composition, and other variables. Consumer removal increased aggregate prey abundance on average by 1200% at the lower limit of prey diversity (two species), but only 200% at the upper limit of 37 species. Importantly, compositional change was substantial at both high and low prey diversity, suggesting predation intensity did not vary with prey richness. Rather diverse prey communities appear to be more capable of maintaining abundance via compensatory responses, by containing prey species that are resistant to (or tolerant of) predators. These results suggest that the effects of species diversity on trophic interactions may scale consistently from small‐scale manipulations to cross‐community comparisons.

Ecosystem Services as a Common Language for Coastal Ecosystem‐Based Management - ELISE F. GRANEK; STEPHEN POLASKY; CARRIE V. KAPPEL; DENISE J. REED; DAVID M. STOMS; EVAMARIA W. KOCH; CHRIS J. KENNEDY; LORI A. CRAMER; SALLY D. HACKER; EDWARD B. BARBIER; SHANKAR ASWANI; MARY RUCKELSHAUS; et al. (Conservation Biology, 2010)
Ecosystem‐based management is logistically and politically challenging because ecosystems are inherently complex and management decisions affect a multitude of groups. Coastal ecosystems, which lie at the interface between marine and terrestrial ecosystems and provide an array of ecosystem services to different groups, aptly illustrate these challenges. Successful ecosystem‐based management of coastal ecosystems requires incorporating scientific information and the knowledge and views of interested parties into the decision‐making process. Estimating the provision of ecosystem services under alternative management schemes offers a systematic way to incorporate biogeophysical and socioeconomic information and the views of individuals and groups in the policy and management process. Employing ecosystem services as a common language to improve the process of ecosystem‐based management presents both benefits and difficulties. Benefits include a transparent method for assessing trade‐offs associated with management alternatives, a common set of facts and common currency on which to base negotiations, and improved communication among groups with competing interests or differing worldviews. Yet challenges to this approach remain, including predicting how human interventions will affect ecosystems, how such changes will affect the provision of ecosystem services, and how changes in service provision will affect the welfare of different groups in society. In a case study from Puget Sound, Washington, we illustrate the potential of applying ecosystem services as a common language for ecosystem‐based management.

Widespread known and novel phosphonate utilization pathways in marine bacteria revealed by functional screening and metagenomic analyses - Asuncion Martinez; Gene W. Tyson; Edward F. DeLong (Environmental Microbiology, 2010)
Summary Phosphonates (Pn), compounds with a direct C–P bond instead of the more common C–O–P ester bond, constitute a significant fraction of marine dissolved organic phosphorus and recent evidence suggests that they may be an alternative source of P for marine microorganisms. To further characterize the microorganisms and pathways involved in Pn utilization, we screened bacterioplankton genomic libraries for their ability to complement an Escherichia coli strain unable to use Pns as a P source. Using this approach we identified a phosphonatase pathway as well as a novel pair of genes that allowed utilization of 2‐aminoethylphosphonate (2‐AEPn) as the sole P source. These pathways are present in diverse bacteria common in marine plankton including representatives of Proteobacteria , Planctomycetes and Cyanobacteria . Analysis of metagenomic databases for Pn utilization genes revealed that they are widespread and abundant among marine bacteria, suggesting that Pn metabolism is likely to play an important role in P‐depleted surface waters, as well as in the more P‐rich deep‐water column.

Genetic map construction and QTL mapping of resistance to blackleg (Leptosphaeria maculans) disease in Australian canola (Brassica napus L.) cultivars - S. Kaur; N. O. I. Cogan; G. Ye; R. C. Baillie; M. L. Hand; A. E. Ling; A. K. Mcgearey; J. Kaur; C. J. Hopkins; M. Todorovic; H. Mountford; D. Edwards; et al. (Theoretical and Applied Genetics, 2009)

New record of fungus Mycoleptodiscus terrestris from New Zealand - Deborah E. Hofstra; Tracey Edwards; John S. Clayton; Judy F. Shearer (New Zealand Journal of Botany, 2009)
During a survey of submersed aquatic macrophytes and their associated fungi from lakes and waterways in New Zealand's North Island, an isolate of Mycoleptodiscus terrestris (Gerd.) Ostaz. was confirmed on the basis of colony characteristics, sporodochia, and conidial morphology. This is a new record of M. terrestris in New Zealand and a new host species, the introduced aquatic macrophyte, Ceratophyllum demersum L.

Distribution of Dissolved Trace Metals Around the Sacrificos Coral Reef Island, in the Southwestern Gulf of Mexico - L. Rosales-Hoz; A. Carranza-Edwards; L. Sanvicente-Añorve; M. A. Alatorre-Mendieta; F. Rivera-Ramirez (Bulletin of Environmental Contamination and Toxicology, 2009)

Impacts of Nonnative Invasive Species on US Forests and Recommendations for Policy and Management - W. Keith Moser; Edward L. Barnard; Ronald F. Billings; Susan J. Crocker; Mary Ellen Dix; Andrew N. Gray; George G. Ice; Mee-Sook Kim; Richard Reid; Sue U. Rodman; William H. McWilliams (Journal of Forestry, 2009)
The introduction of nonnative invasive species (NNIS) into the United States has had tremendous impacts on the nation's commercial and urban forest resources. Of principal concern are the effects of NNIS on forest composition, structure, function, productivity, and patterns of carbon sequestration. In 2006, the Society of American Foresters commissioned an ad hoc team to prepare a white paper on the effect of NNIS on America's forests. The paper was the genesis of this article, which provides an overview of the impacts of NNIS within the United States and includes recommendations for NNIS policy and management.

Measurement and calculation of OH reactivity at a United Kingdom coastal site - James D. Lee; Jennifer C. Young; Katie A. Read; Jacqueline F. Hamilton; James R. Hopkins; Alastair C. Lewis; Brian J. Bandy; James Davey; Peter Edwards; Trevor Ingham; Daniel E. Self; Shona C. Smith; et al. (Journal of Atmospheric Chemistry, 2009)

Positron emission tomographic measure of brain dopamine dependence to nicotine as a model of drugs of abuse - Edward F. Domino; Hideo Tsukada; Norihiro Harada (Psychopharmacology, 2009)

Effect of stocking on juvenile wood stiffness for three Eucalyptus species - Edward Warren; R. Geoff B. Smith; Luis Alejandro Apiolaza; John C. F. Walker (New Forests, 2009)

Combined feedforward and feedback control of a redundant, nonlinear, dynamic musculoskeletal system - Dimitra Blana; Robert F. Kirsch; Edward K. Chadwick (Medical & Biological Engineering & Computing, 2009)

Impact of socioeconomic status on cancer incidence and stage at diagnosis: selected findings from the surveillance, epidemiology, and end results: National Longitudinal Mortality Study - Limin X. Clegg; Marsha E. Reichman; Barry A. Miller; Benjamin F. Hankey; Gopal K. Singh; Yi Dan Lin; Marc T. Goodman; Charles F. Lynch; Stephen M. Schwartz; Vivien W. Chen; Leslie Bernstein; Scarlett L. Gomez; et al. (Cancer Causes & Control, 2009)

Near real‐time, autonomous detection of marine bacterioplankton on a coastal mooring in Monterey Bay, California, using rRNA‐targeted DNA probes - Christina M. Preston; Roman Marin; Scott D. Jensen; Jason Feldman; James M. Birch; Eugene I. Massion; Edward F. DeLong; Marcelino Suzuki; Kevin Wheeler; Christopher A. Scholin (Environmental Microbiology, 2009)
Summary A sandwich hybridization assay (SHA) was developed to detect 16S rRNAs indicative of phylogenetically distinct groups of marine bacterioplankton in a 96‐well plate format as well as low‐density arrays printed on a membrane support. The arrays were used in a field‐deployable instrument, the Environmental Sample Processor (ESP). The SHA employs a chaotropic buffer for both cell homogenization and hybridization, thus target sequences are captured directly from crude homogenates. Capture probes for seven of nine different bacterioplankton clades examined reacted specifically when challenged with target and non‐target 16S rRNAs derived from in vitro transcribed 16S rRNA genes cloned from natural samples. Detection limits were between 0.10–1.98 and 4.43– 12.54 fmole ml −1 homogenate for the 96‐well plate and array SHA respectively. Arrays printed with five of the bacterioplankton‐specific capture probes were deployed on the ESP in Monterey Bay, CA, twice in 2006 for a total of 25 days and also utilized in a laboratory time series study. Groups detected included marine alphaproteobacteria, SAR11, marine cyanobacteria, marine group I crenarchaea, and marine group II euryarchaea. To our knowledge this represents the first report of remote in situ DNA probe‐based detection of marine bacterioplankton.

Targeted transgene integration in plant cells using designed zinc finger nucleases - Charles Q. Cai; Yannick Doyon; W. Michael Ainley; Jeffrey C. Miller; Russell C. DeKelver; Erica A. Moehle; Jeremy M. Rock; Ya-Li Lee; Robbi Garrison; Lisa Schulenberg; Ryan Blue; Andrew Worden; et al. (Plant Molecular Biology, 2009)

Diffuse knapweed (Centaurea diffusa Lam.) seedling emergence and establishment in a Colorado grassland - Paul J. Meiman; Edward F. Redente; Mark W. Paschke (Plant Ecology, 2009)

Contribution of N 2 O to the greenhouse gas balance of first‐generation biofuels - EDWARD M. W. SMEETS; LEX F. BOUWMAN; ELKE STEHFEST; DETLEF P. Van VUUREN; ADAM POSTHUMA (Global Change Biology, 2009)

Assessing the residual effects of Carpobrotus edulis invasion, implications for restoration - Christiana Conser; Edward F. Connor (Biological Invasions, 2009)

Contribution of N 2 O to the greenhouse gas balance of first‐generation biofuels - EDWARD M. W. SMEETS; LEX F. BOUWMAN; ELKE STEHFEST; DETLEF P. Van VUUREN; ADAM POSTHUMA (Global Change Biology, 2009)
In this study, we analyze the impact of fertilizer‐ and manure‐induced N 2 O emissions due to energy crop production on the reduction of greenhouse gas (GHG) emissions when conventional transportation fuels are replaced by first‐generation biofuels (also taking account of other GHG emissions during the entire life cycle). We calculate the nitrous oxide (N 2 O) emissions by applying a statistical model that uses spatial data on climate and soil. For the land use that is assumed to be replaced by energy crop production (the ‘reference land‐use system’), we explore a variety of options, the most important of which are cropland for food production, grassland, and natural vegetation. Calculations are also done in the case that emissions due to energy crop production are fully additional and thus no reference is considered. The results are combined with data on other emissions due to biofuels production that are derived from existing studies, resulting in total GHG emission reduction potentials for major biofuels compared with conventional fuels. The results show that N 2 O emissions can have an important impact on the overall GHG balance of biofuels, though there are large uncertainties. The most important ones are those in the statistical model and the GHG emissions not related to land use. Ethanol produced from sugar cane and sugar beet are relatively robust GHG savers: these biofuels change the GHG emissions by −103% to −60% (sugar cane) and −58% to −17% (sugar beet), compared with conventional transportation fuels and depending on the reference land‐use system that is considered. The use of diesel from palm fruit also results in a relatively constant and substantial change of the GHG emissions by −75% to −39%. For corn and wheat ethanol, the figures are −38% to 11% and −107% to 53%, respectively. Rapeseed diesel changes the GHG emissions by −81% to 72% and soybean diesel by −111% to 44%. Optimized crop management, which involves the use of state‐of‐the‐art agricultural technologies combined with an optimized fertilization regime and the use of nitrification inhibitors, can reduce N 2 O emissions substantially and change the GHG emissions by up to −135 percent points (pp) compared with conventional management. However, the uncertainties in the statistical N 2 O emission model and in the data on non‐land‐use GHG emissions due to biofuels production are large; they can change the GHG emission reduction by between −152 and 87 pp.

Characterizing microbial diversity in production water from an Alaskan mesothermic petroleum reservoir with two independent molecular methods - Vinh D. Pham; Linda L. Hnatow; Shiping Zhang; Robert D. Fallon; Scott C. Jackson; Jean‐Francois Tomb; Edward F. DeLong; Sharon J. Keeler (Environmental Microbiology, 2009)
Summary The phylogenetic diversity of Bacteria and Archaea within a biodegraded, mesothermic petroleum reservoir in the Schrader Bluff Formation of Alaska was examined by two culture‐independent methods based on fosmid and small‐subunit rRNA gene PCR clone libraries. Despite the exclusion of certain groups by each method, there was overall no significant qualitative difference in the diversity of phylotypes recovered by the two methods. The resident Bacteria belonged to at least 14 phylum‐level lineages, including the polyphyletic Firmicutes , which accounted for 36.2% of all small‐subunit rRNA gene‐containing (SSU + ) fosmid clones identified. Members of uncultured divisions were also numerous and made up 35.2% of the SSU + fosmid clones. Clones from domain Archaea accounted for about half of all SSU + fosmids, suggesting that their cell numbers were comparable to those of the Bacteria in this microbial community. In contrast to the Bacteria , however, nearly all archaeal clones recovered by both methods were related to methanogens, especially acetoclastic methanogens, while the plurality of bacterial fosmid clones was affiliated with Synergistes ‐like acetogenic Firmicutes that possibly degrade longer‐chain carboxylic acid components in the crude oil to acetate. These data suggest that acetate may be a key intermediary metabolite in this subsurface anaerobic food chain, which leads to methane production as the primary terminal electron sink.

Development of a Smart Nano-vehicle to Target Cerebrovascular Amyloid Deposits and Brain Parenchymal Plaques Observed in Alzheimer’s Disease and Cerebral Amyloid Angiopathy - Edward K. Agyare; Geoffry L. Curran; Muthu Ramakrishnan; Caroline C. Yu; Joseph F. Poduslo; Karunya K. Kandimalla (Pharmaceutical Research, 2008)

No variation of physical performance and perceived exertion after adrenal gland stimulation by synthetic ACTH (Synacthen®) in cyclists - Norbert Baume; Graeme Steel; Tony Edwards; Eric Thorstensen; Benjamin F. Miller (European Journal of Applied Physiology, 2008)

Preparation of Active Proteins, Vaccines and Pharmaceuticals as Fine Powders using Supercritical or Near-Critical Fluids - Stephen P. Cape; Joseph A. Villa; Edward T. S. Huang; Tzung-Horng Yang; John F. Carpenter; Robert E. Sievers (Pharmaceutical Research, 2008)

Decreased adhesiveness, resistance to anoikis and suppression of GRP94 are integral to the survival of circulating tumor cells in prostate cancer - Edward W. Howard; Steve C. L. Leung; H. F. Yuen; Chee Wai Chua; Davy T. Lee; K. W. Chan; Xianghong Wang; Yong Chuan Wong (Clinical & Experimental Metastasis, 2008)

Phylogenetic analyses of ribosomal DNA‐containing bacterioplankton genome fragments from a 4000 m vertical profile in the North Pacific Subtropical Gyre - Vinh D. Pham; Konstantinos T. Konstantinidis; Tsultrim Palden; Edward F. DeLong (Environmental Microbiology, 2008)
Summary High‐throughput identification of rRNA gene‐containing clones in large insert metagenomic libraries is difficult, because of the high background of host ribosomal RNA (rRNA) and rRNA genes. To address this challenge, a membrane hybridization method was developed to identify all bacterial small subunit rRNA‐containing fosmid clones of microbial community DNA from seven different depths in the North Pacific Subtropical Gyre. Out of 101,376 clones screened, 751 rDNA‐containing clones were identified that grouped in ∼60 different clades. Several rare sequences only remotely related to known groups were detected, including a Wolbachia ‐related sequence containing a putative intron or intervening sequence, as well as seven sequences from Order Myxococcales not previously detected in pelagic habitats. Stratified, depth‐specific population structure was evident within both cultured and uncultured lineages. Conversely, some eurybathyal members of the genera Alcanivorax and Rhizobium shared identical small subunit ribosomal DNA sequences that were distributed from surface waters to the 4000 m depth. Comparison with similar analyses in Monterey Bay microbial communities revealed previously recognized, as well as some distinctive, depth‐stratified partitioning that distinguished coastal from open ocean bacterioplankton populations. While some bias was evident in fosmid clone recovery in a few particular lineages, the overall phylogenetic group recovery and distributions were consistent with previous studies, as well as with direct shotgun sequence data from the same source DNA.

Replication of association between ELAVL4 and Parkinson disease: the GenePD study - Anita L. DeStefano; Jeanne Latourelle; Mark F. Lew; Oksana Suchowersky; Christine Klein; Lawrence I. Golbe; Margery H. Mark; John H. Growdon; G. Fredrick Wooten; Ray Watts; Mark Guttman; Brad A. Racette; et al. (Human Genetics, 2008)

A meta-analysis of studies investigating the effects of lead exposure on nerve conduction - Edward F. Krieg; David W. Chrislip; W. Stephen Brightwell (Archives of Toxicology, 2008)

Upgrades to the Boundary-Layer Scheme in the Met Office Numerical Weather Prediction Model - A. R. Brown; R. J. Beare; J. M. Edwards; A. P. Lock; S. J. Keogh; S. F. Milton; D. N. Walters (Boundary-Layer Meteorology, 2008)

Dispersal of black sea bass ( Centropristis striata ) larvae on the southeast U.S. continental shelf: results of a coupled vertical larval behavior – 3D circulation model - K. P. EDWARDS; J. A. HARE; F. E. WERNER (Fisheries Oceanography, 2008)
In the marine environment, pelagic dispersal is important for determining the distribution and abundance of populations, as well as providing connections among populations. Estimates of larval dispersal from spawning grounds are important to determining temporal and spatial patterns in recruitment that may have significant influences on the dynamics of the population. We present a case study of the dispersal of Centropristis striata (black sea bass) larvae on the southeast U.S. continental shelf. We use a coupled larval behavior – 3D circulation model to compare the effects of the timing and location of spawning against that of larval vertical migration on larval dispersal. Using the results of field data on larval vertical distributions, we compare the dispersal of virtual ‘larvae’ which have ontogenetic changes in vertical behavior with that of particles fixed near the surface and near the bottom. Larvae were released at potential spawning sites four times throughout the spawning season (February through May) for 3 yr (2002–04) and tracked for the assumed larval duration (from 27 to 37 days including the egg stage). Results indicate that adult behavior, in the form of spawning time and location, may be more important than larval vertical behavior in determining larval dispersal on the inner‐ and mid‐ continental shelves of this region.

Changes in fire regimes since the Last Glacial Maximum: an assessment based on a global synthesis and analysis of charcoal data - M. J. Power; J. Marlon; N. Ortiz; P. J. Bartlein; S. P. Harrison; F. E. Mayle; A. Ballouche; R. H. W. Bradshaw; C. Carcaillet; C. Cordova; S. Mooney; P. I. Moreno; et al. (Climate Dynamics, 2008)

Bis-histidine-coordinated hemes in four-helix bundles: how the geometry of the bundle controls the axial imidazole plane orientations in transmembrane cytochromes of mitochondrial Complexes II and III and related proteins - Edward A. Berry; F. Ann Walker (JBIC Journal of Biological Inorganic Chemistry, 2008)

Sediment quality triad assessment of an industrialized estuary of the northeastern USA - Timothy J. Iannuzzi; Tina N. Armstrong; Edward R. Long; Jacqueline Iannuzzi; David F. Ludwig (Environmental Monitoring and Assessment, 2008)

Outdoor Air PCB Concentrations in Three Communities Along the Upper Hudson River, New York - Patrick M. Palmer; Erin E. Belanger; Lloyd R. Wilson; Syni-An A. Hwang; Rajinder S. Narang; Marta I. Gomez; Michael R. Cayo; Lorie A. Durocher; Edward F. Fitzgerald (Archives of Environmental Contamination and Toxicology, 2008)

Recovery of Aboveground Plant Biomass and Productivity After Fire in Mesic and Dry Black Spruce Forests of Interior Alaska - Michelle C. Mack; Kathleen K. Treseder; Kristen L. Manies; Jennifer W. Harden; Edward A. G. Schuur; Jason G. Vogel; James T. Randerson; F. Stuart Chapin (Ecosystems, 2008)

Prediction uncertainty of environmental change effects on temperate European biodiversity - Carsten F. Dormann; Oliver Schweiger; P. Arens; I. Augenstein; St. Aviron; Debra Bailey; J. Baudry; R. Billeter; R. Bugter; R. Bukácek; F. Burel; M. Cerny; et al. (Ecology Letters, 2008)
Observed patterns of species richness at landscape scale (gamma diversity) cannot always be attributed to a specific set of explanatory variables, but rather different alternative explanatory statistical models of similar quality may exist. Therefore predictions of the effects of environmental change (such as in climate or land cover) on biodiversity may differ considerably, depending on the chosen set of explanatory variables. Here we use multimodel prediction to evaluate effects of climate, land‐use intensity and landscape structure on species richness in each of seven groups of organisms (plants, birds, spiders, wild bees, ground beetles, true bugs and hoverflies) in temperate Europe. We contrast this approach with traditional best‐model predictions, which we show, using cross‐validation, to have inferior prediction accuracy. Multimodel inference changed the importance of some environmental variables in comparison with the best model, and accordingly gave deviating predictions for environmental change effects. Overall, prediction uncertainty for the multimodel approach was only slightly higher than that of the best model, and absolute changes in predicted species richness were also comparable. Richness predictions varied generally more for the impact of climate change than for land‐use change at the coarse scale of our study. Overall, our study indicates that the uncertainty introduced to environmental change predictions through uncertainty in model selection both qualitatively and quantitatively affects species richness projections.

Design and testing of ‘genome‐proxy’ microarrays to profile marine microbial communities - Virginia I. Rich; Konstantinos Konstantinidis; Edward F. DeLong (Environmental Microbiology, 2008)
Summary Microarrays are useful tools for detecting and quantifying specific functional and phylogenetic genes in natural microbial communities. In order to track uncultivated microbial genotypes and their close relatives in an environmental context, we designed and implemented a ‘genome‐proxy’ microarray that targets microbial genome fragments recovered directly from the environment. Fragments consisted of sequenced clones from large‐insert genomic libraries from microbial communities in Monterey Bay, the Hawaii Ocean Time‐series station ALOHA, and Antarctic coastal waters. In a prototype array, we designed probe sets to 13 of the sequenced genome fragments and to genomic regions of the cultivated cyanobacterium Prochlorococcus MED4. Each probe set consisted of multiple 70‐mers, each targeting an individual open reading frame, and distributed along each ∼40–160 kbp contiguous genomic region. The targeted organisms or clones, and close relatives, were hybridized to the array both as pure DNA mixtures and as additions of cells to a background of coastal seawater. This prototype array correctly identified the presence or absence of the target organisms and their relatives in laboratory mixes, with negligible cross‐hybridization to organisms having ≤ ∼75% genomic identity. In addition, the array correctly identified target cells added to a background of environmental DNA, with a limit of detection of ∼0.1% of the community, corresponding to ∼10 3 cells ml −1 in these samples. Signal correlated to cell concentration with an R 2 of 1.0 across six orders of magnitude. In addition, the array could track a related strain (at 86% genomic identity to that targeted) with a linearity of R 2 = 0.9999 and a limit of detection of ∼1% of the community. Closely related genotypes were distinguishable by differing hybridization patterns across each probe set. This array's multiple‐probe, ‘genome‐proxy’ approach and consequent ability to track both target genotypes and their close relatives is important for the array's environmental application given the recent discoveries of considerable intrapopulation diversity within marine microbial communities.

Atlantic reef fish biogeography and evolution - S. R. Floeter; L. A. Rocha; D. R. Robertson; J. C. Joyeux; W. F. Smith‐Vaniz; P. Wirtz; A. J. Edwards; J. P. Barreiros; C. E. L. Ferreira; J. L. Gasparini; A. Brito; J. M. Falcón; et al. (Journal of Biogeography, 2008)
Aim To understand why and when areas of endemism (provinces) of the tropical Atlantic Ocean were formed, how they relate to each other, and what processes have contributed to faunal enrichment. Location Atlantic Ocean. Methods The distributions of 2605 species of reef fishes were compiled for 25 areas of the Atlantic and southern Africa. Maximum‐parsimony and distance analyses were employed to investigate biogeographical relationships among those areas. A collection of 26 phylogenies of various Atlantic reef fish taxa was used to assess patterns of origin and diversification relative to evolutionary scenarios based on spatio‐temporal sequences of species splitting produced by geological and palaeoceanographic events. We present data on faunal (species and genera) richness, endemism patterns, diversity buildup (i.e. speciation processes), and evaluate the operation of the main biogeographical barriers and/or filters. Results Phylogenetic (proportion of sister species) and distributional (number of shared species) patterns are generally concordant with recognized biogeographical provinces in the Atlantic. The highly uneven distribution of species in certain genera appears to be related to their origin, with highest species richness in areas with the greatest phylogenetic depth. Diversity buildup in Atlantic reef fishes involved (1) diversification within each province, (2) isolation as a result of biogeographical barriers, and (3) stochastic accretion by means of dispersal between provinces. The timing of divergence events is not concordant among taxonomic groups. The three soft (non‐terrestrial) inter‐regional barriers (mid‐Atlantic, Amazon, and Benguela) clearly act as ‘filters’ by restricting dispersal but at the same time allowing occasional crossings that apparently lead to the establishment of new populations and species. Fluctuations in the effectiveness of the filters, combined with ecological differences among provinces, apparently provide a mechanism for much of the recent diversification of reef fishes in the Atlantic. Main conclusions Our data set indicates that both historical events (e.g. Tethys closure) and relatively recent dispersal (with or without further speciation) have had a strong influence on Atlantic tropical marine biodiversity and have contributed to the biogeographical patterns we observe today; however, examples of the latter process outnumber those of the former.

Influence of canopy structure on the survival and growth of underplanted seedlings - John M. Lhotka; Edward F. Loewenstein (New Forests, 2007)

Within-field variability of Fusarium head blight pathogens and their associated mycotoxins - X.-M. Xu; D. W. Parry; P. Nicholson; M. A. Thomsett; D. Simpson; S. G. Edwards; B. M. Cooke; F. M. Doohan; S. Monaghan; A. Moretti; G. Tocco; G. Mule; et al. (European Journal of Plant Pathology, 2007)

KILLER WHALES, WHALING, AND SEQUENTIAL MEGAFAUNAL COLLAPSE IN THE NORTH PACIFIC: A COMPARATIVE ANALYSIS OF THE DYNAMICS OF MARINE MAMMALS IN ALASKA AND BRITISH COLUMBIA FOLLOWING COMMERCIAL WHALING - Andrew W. Trites; Volker B. Deecke; Edward J. Gregr; John K.B. Ford; Peter F. Olesiuk (Marine Mammal Science, 2007)
The hypothesis that commercial whaling caused a sequential megafaunal collapse in the North Pacific Ocean by forcing killer whales to eat progressively smaller species of marine mammals is not supported by what is known about the biology of large whales, the ecology of killer whales, and the patterns of ecosystem change that took place in Alaska, British Columbia, and elsewhere in the world following whaling. A comparative analysis shows that populations of seals, sea lions, and sea otters increased in British Columbia following commercial whaling, unlike the declines noted in the Gulf of Alaska and Aleutian Islands. The declines of seals and sea lions that began in western Alaska around 1977 were mirrored by increases in numbers of these species in British Columbia. A more likely explanation is that the seal and sea lion declines and other ecosystem changes in Alaska stem from a major oceanic regime shift that occurred in 1977. Killer whales are unquestionably a significant predator of seals, sea lions, and sea otters—but not because of commercial whaling.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Do exaptations facilitate mutualistic associations between invasive and native species? - Edward B. Mondor; John F. Addicott (Biological Invasions, 2007)

The use of incidence-based species richness estimators, species accumulation curves and similarity measures to appraise ethnobotanical inventories from South Africa - Vivienne L. Williams; Edward T. F. Witkowski; Kevin Balkwill (Biodiversity and Conservation, 2007)

AAPS-FDA Workshop White Paper: Microdialysis Principles, Application and Regulatory Perspectives - Chandra S. Chaurasia; Markus Müller; Edward D. Bashaw; Eva Benfeldt; Jan Bolinder; Ross Bullock; Peter M. Bungay; Elizabeth C. M. DeLange; Hartmut Derendorf; William F. Elmquist; Margareta Hammarlund-Udenaes; Christian Joukhadar; et al. (Pharmaceutical Research, 2007)

Quantitative distribution of presumptive archaeal and bacterial nitrifiers in Monterey Bay and the North Pacific Subtropical Gyre - Tracy J. Mincer; Matthew J. Church; Lance Trent Taylor; Christina Preston; David M. Karl; Edward F. DeLong (Environmental Microbiology, 2007)
Summary The recent isolation of the ammonia‐oxidizing crenarchaeon Nitrosopumilus maritimus has expanded the known phylogenetic distribution of nitrifying phenotypes beyond the domain Bacteria . To further characterize nitrification in the marine environment and explore the potential crenarchaeal contribution to this process, we quantified putative nitrifying genes and phylotypes in picoplankton genomic libraries and environmental DNA samples from coastal and open ocean habitats. Betaproteobacteria ammonia monooxygenase subunit A ( amoA ) gene copy numbers were low or undetectable, in stark contrast to crenarchaeal amoA‐ like genes that were broadly distributed and reached up to 6 × 10 4 copies ml −1 . Unexpectedly, in the North Pacific Subtropical Gyre, a deeply branching crenarchaeal group related to a hot spring clade (pSL12) was at times abundant below the euphotic zone. Quantitative data suggested that the pSL12 relatives also contain archaeal amoA ‐like genes. In both coastal and open ocean habitats, close relatives of known nitrite‐oxidizing Nitrospina species were well represented in genomic DNA libraries and quantitative PCR profiles. Planktonic Nitrospina depth distributions correlated with those of Crenarchaea . Overall, the data suggest that amoA ‐containing Crenarchaea are more phylogenetically diverse than previously reported. Additionally, distributional patterns of planktonic Crenarchaea and Nitrospina species suggest potential metabolic interactions between these groups in the ocean's water column.

Proteorhodopsin photosystem gene clusters exhibit co‐evolutionary trends and shared ancestry among diverse marine microbial phyla - Jay McCarren; Edward F. DeLong (Environmental Microbiology, 2007)
Summary Since the recent discovery of retinylidene proteins in marine bacteria (proteorhodopsins), the estimated abundance and diversity of this gene family has expanded rapidly. To explore proteorhodopsin photosystem evolutionary and distributional trends, we identified and compared 16 different proteorhodopsin‐containing genome fragments recovered from naturally occurring bacterioplankton populations. In addition to finding several deep‐branching proteorhodopsin sequences, proteorhodopsins were found in novel taxonomic contexts, including a betaproteobacterium and a planctomycete. Approximately one‐third of the proteorhodopsin‐containing genome fragments analysed, as well as a number of recently reported marine bacterial whole genome sequences, contained a linked set of genes required for biosynthesis of the rhodopsin chromophore, retinal. Phylogenetic analyses of the retinal biosynthetic genes suggested their co‐evolution and probable coordinated lateral gene transfer into disparate lineages, including Euryarchaeota , Planctomycetales , and three different proteobacterial lineages. The lateral transfer and retention of genes required to assemble a functional proteorhodopsin photosystem appears to be a coordinated and relatively frequent evolutionary event. Strong selection pressure apparently acts to preserve these light‐dependent photosystems in diverse marine microbial lineages.

Increasing the Proportional Content of Surfactant (Cremophor EL) Relative to Lipid in Self-emulsifying Lipid-based Formulations of Danazol Reduces Oral Bioavailability in Beagle Dogs - Jean F. Cuiné; William N. Charman; Colin W. Pouton; Glenn A. Edwards; Christopher J. H. Porter (Pharmaceutical Research, 2007)

AAPS-FDA workshop white paper: Microdialysis principles, application, and regulatory perspectives report from the Joint AAPS-FDA Workshop, November 4–5, 2005, Nashville, TN - Chandra S. Chaurasia; Markus Müller; Edward D. Bashaw; Eva Benfeldt; Jan Bolinder; Ross Bullock; Peter M. Bungay; Elizabeth C. M. DeLange; Hartmut Derendorf; William F. Elmquist; Margareta Hammarlund-Udenaes; Christian Joukhadar; et al. (The AAPS Journal, 2007)

Quality of race, Hispanic ethnicity, and immigrant status in population-based cancer registry data: implications for health disparity studies - Limin X. Clegg; Marsha E. Reichman; Benjamin F. Hankey; Barry A. Miller; Yi D. Lin; Norman J. Johnson; Stephen M. Schwartz; Leslie Bernstein; Vivien W. Chen; Marc T. Goodman; Scarlett L. Gomez; John J. Graff; et al. (Cancer Causes & Control, 2007)

Guidelines on nicotine dose selection for in vivo research - Shannon G. Matta; David J. Balfour; Neal L. Benowitz; R. Thomas Boyd; Jerry J. Buccafusco; Anthony R. Caggiula; Caroline R. Craig; Allan C. Collins; M. Imad Damaj; Eric C. Donny; Phillip S. Gardiner; Sharon R. Grady; et al. (Psychopharmacology, 2007)

Improving Data Reliability Using a Non-Compliance Detection Method versus Using Pharmacokinetic Criteria - Smita A. Kshirsagar; Terrence F. Blaschke; Lewis B. Sheiner; M. Krygowski; Edward P. Acosta; Davide Verotta (Journal of Pharmacokinetics and Pharmacodynamics, 2007)

PHYSIOLOGICAL AND BEHAVIORAL DEVELOPMENT IN DELPHINID CALVES: IMPLICATIONS FOR CALF SEPARATION AND MORTALITY DUE TO TUNA PURSE‐SEINE SETS - Shawn R. Noren; Elizabeth F. Edwards (Marine Mammal Science, 2007)
Tuna purse‐seiners in the eastern tropical Pacific (ETP) capture yellowfin tuna by chasing and encircling herds of associated dolphins. This fishery has caused mortality in 14 dolphin species (20 stocks) and has led to significant depletions of at least three stocks. Although observed dolphin mortality is currently low, set frequency remains high and dolphin stocks are not recovering at expected rates. Mortality of nursing calves permanently separated from their mothers during fishery operations may be an important factor in the lack of population recovery, based on the recent discovery that calves do not accompany 75%–95% of lactating females killed in the purse‐seine nets. We assessed age‐specific potential for mother–calf separations and subsequent mortality of calves by reviewing and synthesizing published data on physiological and behavioral development in delphinids from birth through 3 yr postpartum. Results indicate that evasive behavior of mothers, coupled with the developmental state of calves, provides a plausible mechanism for set‐related mother–calf separations and subsequent mortality of calves. Potential for set‐related separation and subsequent mortality is highest for 0–12‐mo‐old dolphins and becomes progressively lower with age as immature dolphins approach adult stamina and attain independence.

Seeing red primes tomato: evidence for comparable priming from colour and colour name primes to semantically related word targets - Tanja C. W. Nijboer; Martine J. E. van Zandvoort; Edward H. F. de Haan (Cognitive Processing, 2006)

The coupling of optimal economic growth and climate dynamics - Olivier Bahn; Laurent Drouet; Neil R. Edwards; Alain Haurie; Reto Knutti; Socrates Kypreos; Thomas F. Stocker; Jean-Philippe Vial (Climatic Change, 2006)

Transdermal nicotine attenuates depression symptoms in nonsmokers: a double-blind, placebo-controlled trial - F. Joseph McClernon; F. Berry Hiott; Eric C. Westman; Jed E. Rose; Edward D. Levin (Psychopharmacology, 2006)

A COMPARISON OF BIOFOULING COMMUNITIES ASSOCIATED WITH FREE‐RANGING AND CAPTIVE FLORIDA MANATEES ( TRICHECHUS MANATUS LATIROSTRIS ) - Erin L. Bledsoe; Kendal E. Harr; Mary F. Cichra; Edward J. Phlips; Robert K. Bonde; Mark Lowe (Marine Mammal Science, 2006)

Effect of animal browse protection and fertilizer application on the establishment of planted Nuttall oak seedlings - Troy S. Taylor; Edward F. Loewenstein; Arthur H. Chappelka (New Forests, 2006)

Nutritional status of four species of giant land snails in Nigeria - O. Fagbuaro; J. A. Oso; J. B. Edward; R. F. Ogunleye (Journal of Zhejiang University-SCIENCE B, 2006)

Assistive navigational devices that incorporate principles of spatial cognition and imagery - Geoffrey Edwards; Alison F. Eardley; Francine Malouin; Marlène Viger; Reda Yaagoubi; David Lambiel (Cognitive Processing, 2006)

Challenging the importance of vision for the development of an extrinsic spatial framework: evidence from the blind and sighted - Alison F. Eardley; Geoffrey Edwards; Francine Malouin; Pierre-Emmanuel Michon (Cognitive Processing, 2006)

Preliminary evidence of reduced occipital GABA concentrations in puerperal women: a 1H-MRS study - C. Neill Epperson; Ralitza Gueorguieva; Kathryn A. Czarkowski; Stephanie Stiklus; Edward Sellers; John H. Krystal; Douglas L. Rothman; Graeme F. Mason (Psychopharmacology, 2006)

Characterization of the novel CYP2A6*21 allele using in vivo nicotine kinetics - Nael Al Koudsi; Jill C. Mwenifumbo; Edward M. Sellers; Neal L. Benowitz; Gary E. Swan; Rachel F. Tyndale (European Journal of Clinical Pharmacology, 2006)

Phosphorus Translocation by Red Deer on a Subalpine Grassland in the Central European Alps - Martin Schütz; Anita C. Risch; Gérald Achermann; Conny Thiel-Egenter; Deborah S. Page-Dumroese; Martin F. Jurgensen; Peter J. Edwards (Ecosystems, 2006)

Interactions between Widely Spaced Young Poplars (Populus spp.) and the Understorey Environment - G. B. Douglas; A. S. Walcroft; S. E. Hurst; J. F. Potter; A. G. Foote; L. E. Fung; W. R. N. Edwards; C. van den Dijssel (Agroforestry Systems, 2006)

Updated Conservation Classic - Summer Lindzey; John Doudna; Edward F. Connor (Conservation Biology, 2006)

Diet After Diagnosis and the Risk of Prostate Cancer Progression, Recurrence, and Death (United States) - June M. Chan; Crystal N. Holick; Michael F. Leitzmann; Eric B. Rimm; Walter C. Willett; Meir J. Stampfer; Edward L. Giovannucci (Cancer Causes & Control, 2006)

Zinc Toxicity Thresholds for Reclamation Forb Species - Mark W. Paschke; Laura G. Perry; Edward F. Redente (Water, Air, & Soil Pollution, 2006)

Nicotinic effects on cognitive function: behavioral characterization, pharmacological specification, and anatomic localization - Edward D. Levin; F. Joseph McClernon; Amir H. Rezvani (Psychopharmacology, 2006)

Interactions between Widely Spaced Young Poplars (Populus spp.) and Introduced Pasture Mixtures - G. B. Douglas; A. S. Walcroft; S. E. Hurst; J. F. Potter; A. G. Foote; L. E. Fung; W. R. N. Edwards; C. van den Dijssel (Agroforestry Systems, 2006)

Linkage methods in human genetics before the computer - A. W. F. Edwards (Human Genetics, 2005)

Application of Diversity Indices to Appraise Plant Availability in the Traditional Medicinal Markets of Johannesburg, South Africa - Vivienne L. Williams; Edward T. F. Witkowski; Kevin Balkwill (Biodiversity and Conservation, 2005)

Deficits in grasp versus reach during acute hemiparesis - Catherine E. Lang; Joanne M. Wagner; Amy J. Bastian; Qingli Hu; Dorothy F. Edwards; Shirley A. Sahrmann; Alexander W. Dromerick (Experimental Brain Research, 2005)

Lateralised processing of the internal and the external facial features of personally familiar and unfamiliar faces: a visual half-field study - Edward H. F. De Haan; Evelien N. M. van Kollenburg (Cognitive Processing, 2005)

Glutathione modulation of in vitro development - Edward C. Yeung; Mark F. Belmonte; Luu T. T. Tu; Claudio Stasolla (In Vitro Cellular & Developmental Biology - Plant, 2005)

A general biophysical model of larval cod ( Gadus morhua ) growth applied to populations on Georges Bank - R. G. LOUGH; L. J. BUCKLEY; F. E. WERNER; J. A. QUINLAN; K. PEHRSON EDWARDS (Fisheries Oceanography, 2005)
Field‐derived growth rates (RNA‐DNA based) of cod ( Gadus morhua ) larvae collected on the southern flank of Georges Bank were higher on average in May 1993 than May 1994, despite the apparent higher abundance of potential prey in 1994. A biophysical modeling study is presented here in which factors are examined that may have led to the difference in population mean growth. A one‐dimensional physical model, forced by winds and tides, was used to simulate the vertical structure (of currents, temperature field, and turbulent kinetic energy dissipation rate) following a column of water in a Lagrangian sense at a site on the southern flank of Georges Bank over 5‐day periods in late May of 1993 and 1994. The biophysical model and observed zooplankton abundance allowed us to explore the vertical structure and temporal (hourly) evolution of feeding and growth for cod larvae in relation to environmental conditions. Our trophodynamic model is improved over previous versions and now includes the effect of light on larval feeding response, as well as the effect of temperature on larval metabolic costs, ingestion, and digestion. Larval prey profiles, comprising four copepod species, were used from a time series of 1/4‐m 2 MOCNESS tows to define the prey field. Data from a collateral time‐series of larval gut contents (1‐m 2 MOCNESS tows) was used to define maximum ingestion (satiation level) and prey selection. Model outputs provide depth‐dependent estimates of growth, prey biomass ingested, larval length, and larval weight. Water‐column growth‐rate profiles were made for four size classes of larvae (5, 6, 7 and 9 mm) under the environmental conditions observed in May 1993 and 1994. A weighted‐mean growth rate based on the mean vertical distribution of larvae was estimated for each size class. In all cases, when using all available potential prey, the model‐derived 1994 growth rates were higher (by 3–6% day −1 ) than those for 1993. However, simulations in which 7‐mm larvae followed the field‐derived weighted mean depth over the sampling period, and were limited to their preferred Pseudocalanus prey, resulted in average growth of 12.2% day −1 for 1993 and 9.7% day −1 for 1994. These compared closely to the field growth means of 11.3% day −1 in 1993 and 9.8% day −1 in 1994. Thus, the lower observed growth in May 1994 may have resulted from depth‐dependent food limitation and prey‐selectivity coupled with the greater metabolic costs induced by the higher temperature that year.

Sleep quality deteriorates over a binge–abstinence cycle in chronic smoked cocaine users - Edward F. Pace-Schott; Robert Stickgold; Amir Muzur; Pia E. Wigren; Amie S. Ward; Carl L. Hart; Denise Clarke; Alexandra Morgan; J. Allan Hobson (Psychopharmacology, 2005)

Predominance and association of pathogenic fungi causing Fusarium ear blightin wheat in four European countries - X. -M. Xu; D. W. Parry; P. Nicholson; M. A. Thomsett; D. Simpson; S. G. Edwards; B. M. Cooke; F. M. Doohan; J. M. Brennan; A. Moretti; G. Tocco; G. Mule; et al. (European Journal of Plant Pathology, 2005)

Sex differences in the perception of affective facial expressions: Do men really lack emotional sensitivity? - Barbara Montagne; Roy P. C. Kessels; Elisa Frigerio; Edward H. F. de Haan; David I. Perrett (Cognitive Processing, 2005)

Plasma insulin-like growth factor-1 and binding protein-3 and subsequent risk of prostate cancer in the PSA era - Elizabeth A. Platz; Michael N. Pollak; Michael F. Leitzmann; Meir J. Stampfer; Walter C. Willett; Edward Giovannucci (Cancer Causes & Control, 2005)

Non-native plants in the understory of riparian forests across a land use gradient in the Southeast - Nancy J. Loewenstein; Edward F. Loewenstein (Urban Ecosystems, 2005)

Nicotine physical dependence and tolerance in the mouse following chronic oral administration - Sheri D. Grabus; Billy R. Martin; Angela M. Batman; Rachel F. Tyndale; Edward Sellers; M. Imad Damaj (Psychopharmacology, 2005)

Molecular Analysis of the Relatedness of Five Domesticated Turkey Strains - Edward J. Smith; Tuoyu Geng; Elizabeth Long; F. William Pierson; D. Phillip Sponenberg; Cal Larson; Robert Gogal (Biochemical Genetics, 2005)

Predator-induced transgenerational phenotypic plasticity in the cotton aphid - Edward B. Mondor; Jay A. Rosenheim; John F. Addicott (Oecologia, 2005)

Are gardens effective in butterfly conservation? A case study with the pipevine swallowtail, Battus philenor - Jacqueline M. Levy; Edward F. Connor (Journal of Insect Conservation, 2004)

Microbial population genomics and ecology: the road ahead - Edward F. DeLong (Environmental Microbiology, 2004)

Different SAR86 subgroups harbour divergent proteorhodopsins - Gazalah Sabehi; Oded Béjà; Marcelino T. Suzuki; Christina M. Preston; Edward F. DeLong (Environmental Microbiology, 2004)
Summary Proteorhodopsins (PRs), bacterial photoactive proton pumps, were originally detected in the uncultured marine γ‐proteobacterial SAR86 group. PRs are now known to occur in both the γ and α marine proteobacterial lineages. Recent environmental shotgun sequence analysis in the Sargasso Sea has added yet more diversity, and a potentially broader taxonomic distribution, to the PR family. Much remains to be learned, however, about within‐taxon PR variability and the broader organismal distribution of different PR types. We report here genomic analyses of large genome fragments from different subgroups of the SAR86 lineage, recovered from naturally occurring bacterioplankton populations in coastal Red Sea and open ocean Pacific waters. Sequence comparisons were performed on large bacterial artificial chromosomes (BACs) bearing both rRNA and PR genes, derived from different SAR86 subgroups. Our analyses indicated the presence of different PR sequence types within the same SAR86 rRNA subgroup. The data suggested that the distribution of particular PR types does not necessarily parallel the phylogenetic relationship inferred from highly conserved genes such as rRNA. Further analyses of the genomic regions flanking PR also revealed a potential pathway for the biosynthesis of retinal, the PR chromophore that is required to generate the functionally active photoprotein. Finally, comparison of our results with recently reported Sargasso Sea environmental shotgun sequence assemblies demonstrated the utility of BAC clones for interpreting environmental shotgun sequence data, much of which is represented in short contigs that have an overall low depth of coverage.

Effects of Direct Ocean CO2 Injection on Deep-Sea Meiofauna - James P. Barry; Kurt R. Buck; Chris F. Lovera; Linda Kuhnz; Patrick J. Whaling; Edward T. Peltzer; Peter Walz; Peter G. Brewer (Journal of Oceanography, 2004)

The Chemistry of Exploding Ants, Camponotus SPP. (Cylindricus COMPLEX) - T. H. Jones; D. A. Clark; A. A. Edwards; D. W. Davidson; T. F. Spande; R. R. Snelling (Journal of Chemical Ecology, 2004)

Nitrogen Leaching and Denitrification in Continuous Corn as Related to Residue Management and Nitrogen Fertilization - Hero T. Gollany; Jean-Alex E. Molina; C. Edward Clapp; Raymond R. Allmaras; Milegua F. Layese; John M. Baker; H. H. Cheng (Environmental Management, 2004)

Hybridization Between Canada Lynx and Bobcats: Genetic Results and Management Implications - Michael K. Schwartz; Kristine L. Pilgrim; Kevin S. McKelvey; Edward L. Lindquist; James J. Claar; Steve Loch; Leonard F. Ruggiero (Conservation Genetics, 2004)

Plasma 1,25-Dihydroxy- and 25-Hydroxyvitamin D and Subsequent Risk of Prostate Cancer - Elizabeth A. Platz; Michael F. Leitzmann; Bruce W. Hollis; Walter C. Willett; Edward Giovannucci (Cancer Causes & Control, 2004)

The effects of reduced and oxidized glutathione on white spruce somatic embryogenesis - Mark F. Belmonte; Edward C. Yeung (In Vitro Cellular & Developmental Biology - Plant, 2004)

Preparing for Climatic Change: The Water, Salmon, and Forests of the Pacific Northwest - Philip W. Mote; Edward A. Parson; Alan F. Hamlet; William S. Keeton; Dennis Lettenmaier; Nathan Mantua; Edward L. Miles; David W. Peterson; David L. Peterson; Richard Slaughter; Amy K. Snover (Climatic Change, 2003)

Novel Proteorhodopsin variants from the Mediterranean and Red Seas - Gazalah Sabehi; Ramon Massana; Joseph P. Bielawski; Mira Rosenberg; Edward F. Delong; Oded Béjà (Environmental Microbiology, 2003)
Summary Proteorhodopsins, ubiquitous retinylidene photoactive proton pumps, were recently found in the widespread uncultured SAR86 bacterial group in oceanic surface waters. To survey proteorhodopsin diversity, new degenerate sets of proteorhodopsin primers were designed based on a genomic proteorhodopsin gene sequence originating from an Antarctic fosmid library. New proteorhodopsin variants were identified in Red Sea samples that were most similar to the original green‐light absorbing proteorhodopsins found in Monterey Bay California. Unlike green‐absorbing proteorhodopsins however, these new variants contained a glutamine residue at position 105, the same site recently shown to control spectral tuning in naturally occurring proteorhodopsins. Different proteorhodopsin variants were also found in the Mediterranean Sea. These proteorhodopsins formed new and distinctive proteorhodopsin groups. Phylogenetic analyses show that some of the new variants were very different from previously characterized proteorhodopsins, and formed the deepest branching groups found so far among marine proteorhodopsins. The existence of these varied proteorhodopsin sequences suggests that this class of proteins has undergone substantial evolution. These variants could represent functionally divergent paralogous genes, derived from the same or similar species, or orthologous proteorhodopsins that are distributed amongst divergent planktonic microbial taxa.

Abundance and distribution of planktonic Archaea and Bacteria in the waters west of the Antarctic Peninsula - Matthew J. Church; Edward F. DeLong; Hugh W. Ducklow; Markus B. Karner; Christina M. Preston; David M. Karl (Limnology and Oceanography, 2003)
Polyribonucleotide probes targeting planktonic archaeal (Group I and II) and bacterial rRNA revealed that Archaea comprised a significant fraction of total prokaryote cell abundance in the marine waters west of the Antarctic Peninsula. Determinations of Archaea and Bacteria cell abundances were made during two research cruises to the Palmer Long‐Term Ecological Research region during the austral winter and summer of 1999. During the austral summer, surface water abundances of Group I (GI) Archaea were generally low, averaging 4.7 x 10 3 cells ml −1 and accounting for 1% of the total picoplankton assemblage. The abundance of GI Archaea increased significantly with depth, averaging 2.1 X 10 4 cells ml −1 and comprising 9–39% of the total picoplankton abundance in the meso‐ (150–1,000 m) and bathypelagic (1,000–3,500 m) circumpolar deep water (CDW). Relative to summertime distributions, GI cells were more evenly distributed throughout the water column during the winter, averaging 10% of the picoplankton in the surface waters and 13% in the CDW. Surface water GI abundance increased 44% between the summer and winter, coincident with a fivefold decrease in GI abundance in the deeper waters. The abundance of Group II (GII) Archaea was persistently 5 cells ml −1 and comprised 89% of the total picoplankton assemblage. Generally, GI Archaea varied seasonally in the deeper waters, whereas bacterial abundance varied more in the upper waters. The observed variability in bacterial and archaeal abundance suggests that these two groups of marine picoplankton are dynamic components of Southern Ocean microbial food webs.

Evolution of major histocompatibility complex class I genes in Cetartiodactyls - Edward C. Holmes; Ann F. C. Roberts; Karen A. Staines; Shirley A. Ellis (Immunogenetics, 2003)

Conspicuous extra‐floral nectaries are inducible in Vicia faba - Edward B. Mondor; John F. Addicott (Ecology Letters, 2003)
Mutualistic interactions are dynamic associations that vary depending on the costs and benefits to each of the interacting parties. Phenotypic plasticity in mutualistic interactions allows organisms to produce rewards to attract mutualists when the benefits of their presence outweigh the costs of producing the rewards. In ant–plant defensive mutualisms, defences are indirect as plants produce extra‐floral nectaries (EFN) to attract predatory ants to deter herbivores. Here we demonstrate that in broad bean, Vicia faba , the overall number of EFNs on a plant increases dramatically following leaf damage. In two damage treatments, removal of: (1) one‐third of one leaf in a single leaf pair or (2) one‐third of both halves of a single leaf pair, resulted in a 59 and 106% increase in the number of EFNs on the plants, respectively, over 1 week. We suggest that the increased production of visually conspicuous EFNs is an adaptive inducible response, to attract predatory arthropods when risk of herbivory increases.

Selecting in situ conservation sites for grape genetic resources in the USA - Diane S. Pavek; Warren F. Lamboy; Edward J. Garvey (Genetic Resources and Crop Evolution, 2003)

Molecular diversity among marine picophytoplankton as revealed by psbA analyses - Gil Zeidner; Christina M. Preston; Edward F. Delong; Ramon Massana; Anton F. Post; David J. Scanlan; Oded Béjà (Environmental Microbiology, 2003)
Summary Photosynthetic microorganisms play a crucial role in the marine environment. In vast areas of the oceans, marine primary productivity is performed by cells smaller than 2–3 µm (picoplankton). Here, we report on molecular analyses of the conserved photosynthetic psbA gene (coding for protein D1 of photosystem II reaction centre) as a diversity indicator of naturally occurring marine oxygenic picophytoplankton. The psbA genes proved to be good indicators of the presence of a wide variety of photosynthetic marine microbial groups, including new cyanobacterial groups and eukaryotic algae (prasinophytes). Furthermore, using environmental bacterial artificial chromosome (BAC) libraries, we were able to correlate psbA genes with small subunit rRNAs and, therefore, to confirm their phylogenetic affiliation.

The anatomy and brooding biology of Pottsiella erecta (Potts, 1884) (Ectoprocta: Gymnolaemata: Ctenostomata), with an expanded diagnosis of the Pottsiellidae - Douglas G. Smith; Sean F. Werle; Edward Klekowski (Hydrobiologia, 2003)

Incidence of Stress in Benthic Communities along the U.S. Atlantic and Gulf of Mexico Coasts within Different Ranges of Sediment Contamination from Chemical Mixtures - Jeffrey L. Hyland; W. Leonard Balthis; Virginia D. Engle; Edward R. Long; John F. Paul; J. Kevin Summers; Robert F. Van Dolah (Environmental Monitoring and Assessment, 2003)

Insect Conservation in an Urban Biodiversity Hotspot: The San Francisco Bay Area - Edward F. Connor; John Hafernik; Jacqueline Levy; Vicki Lee Moore; Jancy K. Rickman (Journal of Insect Conservation, 2002)

Genetic mapping of grapevine (Vitis vinifera L.) applied to the detection of QTLs for seedlessness and berry weight - A. Doligez; A. Bouquet; Y. Danglot; F. Lahogue; S. Riaz; C. Meredith; K. Edwards; P. This (Theoretical and Applied Genetics, 2002)

Genetic mapping of 66 new microsatellite (SSR) loci in bread wheat - P. Gupta; H. Balyan; K. Edwards; P. Isaac; V. Korzun; M. Röder; M.–F. Gautier; P. Joudrier; A. Schlatter; J. Dubcovsky; R. De la Pena; M. Khairallah; et al. (Theoretical and Applied Genetics, 2002)

Effects of aerobic fitness training on human cortical function - Arthur F. Kramer; Stanley Colcombe; Kirk Erickson; Artem Belopolsky; Edward McAuley; Neal J. Cohen; Andrew Webb; Gerald J. Jerome; David X. Marquez; Tracey M. Wszalek (Journal of Molecular Neuroscience, 2002)

Reproduction of hatchery-reared and transplanted wild bay scallops, Argopecten irradians irradians, relative to natural populations - Stephen T. Tettelbach; Christopher F. Smith; Peter Wenczel; Edward Decort (Aquaculture International, 2002)

Dry matter production and boron concentrations of vegetative and reproductive tissues of canola and sunflower plants grown in nutrient solution - A. Asad; F. P. C. Blamey; D. G. Edwards (Plant and Soil, 2002)

MUSCLE-DERIVED CD45−SCA-1+C-KIT− PROGENITOR CELLS GIVE RISE TO SKELETAL MUSCLE MYOTUBES IN VITRO - CASSANDRE L. ROYER; JONATHAN C. HOWELL; PAUL R. MORRISON; EDWARD F. SROUR; MERVIN C. YODER (In Vitro Cellular & Developmental Biology - Animal, 2002)

Towards microbial systems science: integrating microbial perspective, from genomes to biomes - Edward F. DeLong (Environmental Microbiology, 2002)

Multiple Ligand and Cell-Dependent States of Lateral Mobility of Plasmalemmal G Protein-Coupled Cholecystokinin Receptors - Belinda F. Roettger; Edward H. Hellen; Thomas P. Burghardt; Laurence J. Miller (Journal of Fluorescence, 2001)

Diversity, genetic structure and evidence of outcrossing in British populations of the rock fern Adiantum capillus‐veneris using microsatellites - K. V. Pryor; J. E. Young; F. J. Rumsey; K. J. Edwards; M. W. Bruford; H. J. Rogers (Molecular Ecology, 2001)
Microsatellites were isolated and a marker system was developed in the fern Adiantum capillus‐veneris . Polymorphic markers were then used to study the genetic diversity and structure of populations within the UK and Ireland where this species grows at the northern edge of its range, requiring a specific rock habitat and limited to a few scattered populations. Three dinucleotide loci detected a high level of diversity (23 alleles and 28 multilocus genotypes) across the UK and Ireland, with nearly all variation partitioned among rather than within populations. Of 17 populations represented by multiple samples, all except four were monomorphic. Heterozygosity was detected in three populations, all within Glamorgan, Wales (UK), showing evidence of outcrossing. We make inferences on the factors determining the observed levels and patterns of genetic variation and the possible evolutionary history of the populations.

Potassium nutrition effects on seed alkaloid concentrations, yield and mineral content of lupins (Lupinus angustifolius) - P. Gremigni; M. T. F. Wong; N. K. Edwards; D. Harris; J. Hamblin (Plant and Soil, 2001)

Ambient air levels of Aspergillus fumigatus and thermophilic actinomycetes in a residential neighborhood near a yard-waste composting facility - Gregg M. Recer; Marilyn L. Browne; Edward G. Horn; Kenneth M. Hill; William F. Boehler (Aerobiologia, 2001)

Phylogenetic analysis of ribosomal RNA operons from uncultivated coastal marine bacterioplankton - Marcelino T. Suzuki; Oded Béjà; Lance T. Taylor; Edward F. DeLong (Environmental Microbiology, 2001)
Analyses of small subunit ribosomal RNA genes (SSU rDNAs) have significantly influenced our understanding of the composition of aquatic microbial assemblages. Unfortunately, SSU rDNA sequences often do not have sufficient resolving power to differentiate closely related species. To address this general problem for uncultivated bacterioplankton taxa, we analysed and compared sequences of polymerase chain reaction (PCR)‐generated and bacterial artificial chromosome (BAC)‐derived clones that contained most of the SSU rDNAs, the internal transcribed spacer (ITS) and the large subunit ribosomal RNA gene (LSU rDNA). The phylogenetic representation in the rRNA operon PCR library was similar to that reported previously in coastal bacterioplankton SSU rDNA libraries. We observed good concordance between the phylogenetic relationships among coastal bacterioplankton inferred from SSU or LSU rDNA sequences. ITS sequences confirmed the close intragroup relationships among members of the SAR11, SAR116 and SAR86 clades that were predicted by SSU and LSU rDNA sequence analyses. We also found strong support for homologous recombination between the ITS regions of operons from the SAR11 clade.

Identification of amino acids in the leader peptide of Methanococcus voltae preflagellin that are important in posttranslational processing - Nikhil A. Thomas; Edward D. Chao; Ken F. Jarrell (Archives of Microbiology, 2001)

Application of Rhizobacteria for Induced Resistance - Geoffrey W. Zehnder; John F. Murphy; Edward J. Sikora; Joseph W. Kloepper (European Journal of Plant Pathology, 2001)

Assessing anthropogenic impact on Mediterranean sand dunes from aerial digital photography - R. H. F. Curr; A. Koh; E. Edwards; A. T. Williams; P. Davies (Journal of Coastal Conservation, 2000)

The controls on net ecosystem productivity along an Arctic transect: a model comparison with flux measurements - Mathew Williams; Werner Eugster; Edward B. Rastetter; Joseph P. Mcfadden; F. Stuart Chapin Iii (Global Change Biology, 2000)
Summary Assessments of carbon (C) fluxes in the Arctic require detailed data on both how and why these fluxes vary across the landscape. Such assessments are complicated because tundra vegetation has diverse structure and function at both local and regional scales. To investigate this diversity, the Arctic Flux Study has used the eddy covariance technique to generate ecosystem CO 2 ‐exchange data along a transect in northern Alaska. We use an extant process‐based model of the soil–plant–atmosphere continuum to make independent predictions of gross photosynthesis and foliar respiration at 9 of the sites along the transect, using data on local canopy structure and meteorology. We make two key assumptions: (i) soil respiration is constant throughout the flux measurement period, so that the diurnal cycle in CO 2 exchange is driven by canopy processes only (except at two sites where a soil respiration–temperature relationship was indicated in the data); and (ii) mosses and lichens play an insignificant role in ecosystem C exchange, even though in some locations their live biomass exceeds 300 g m −2 . We found that even with these assumptions the model could explain much of the dynamics of net ecosystem production (NEP) at sites with widely differing vegetation structure and moss/lichen cover. Errors were mostly associated with the predictions of maximum NEP; the likely cause of such discrepancies was (i) a mismatch between vegetation sampled for characterizing the canopy structure and that contained within the footprint of the eddy covariance flux measurements, or (ii) an increase in daytime soil and root respiration. Thus the model results tended to falsify our first assumption but not our second. We also note evidence for an actual reduction in NEP caused by water stress on warm, dry days at some sites. The model–flux comparison also suggests that photosynthesis may be less sensitive to low temperatures than leaf‐level gas‐exchange measurements have indicated.

Construction and analysis of bacterial artificial chromosome libraries from a marine microbial assemblage - Oded Béjà; Marcelino T. Suzuki; Eugene V. Koonin; L. Aravind; Andrew Hadd; Linh P. Nguyen; Rachel Villacorta; Mojgan Amjadi; Corey Garrigues; Stevan B. Jovanovich; Robert A. Feldman; Edward F. DeLong (Environmental Microbiology, 2000)
Cultivation‐independent surveys of ribosomal RNA genes have revealed the existence of novel microbial lineages, many with no known cultivated representatives. Ribosomal RNA‐based analyses, however, often do not provide significant information beyond phylogenetic affiliation. Analysis of large genome fragments recovered directly from microbial communities represents one promising approach for characterizing uncultivated microbial species better. To assess further the utility of this approach, we constructed large‐insert bacterial artificial chromosome (BAC) libraries from the genomic DNA of planktonic marine microbial assemblages. The BAC libraries we prepared had average insert sizes of ≈ 80 kb, with maximal insert sizes > 150 kb. A rapid screening method assessing the phylogenetic diversity and representation in the library was developed and applied. In general, representation in the libraries agreed well with previous culture‐independent surveys based on polymerase chain reaction (PCR)‐amplified rRNA fragments. A significant fraction of the genome fragments in the BAC libraries originated from as yet uncultivated microbial species, thought to be abundant and widely distributed in the marine environment. One entire BAC insert, derived from an uncultivated, surface‐dwelling euryarchaeote, was sequenced completely. The planktonic euryarchaeal genome fragment contained some typical archaeal genes, as well as unique open reading frames (ORFs) suggesting novel function. In total, our results verify the utility of BAC libraries for providing access to the genomes of as yet uncultivated microbial species. Further analysis of these BAC libraries has the potential to provide significant insight into the genomic potential and ecological roles of many indigenous microbial species, cultivated or not.

Abstracts - Danuta Babula; Malgorzata Ruminska; Jan Sadowski; Josep M. Folch; Ramona Natacha Pena; Agustina Coll; Armand Sánchez; James M. H. Kijas; Leif Andersson; Dušan Kordiš; Franc Gubenšek; Gregor Majdič; et al. (Pflügers Archiv - European Journal of Physiology, 2000)

AERIAL VIDEOGRAMMETRY FROM A TETHERED AIRSHIP TO ASSESS MANATEE LIFE‐STAGE STRUCTURE - Richard O. Flamm; Edward C. G. Owen; Caryn F. W. Owen; Randall S. Wells; Doug Nowacek (Marine Mammal Science, 2000)
A bstract Aerial videogrammetry from an airship tethered to a boat was used to assess the life‐stage structure of manatees in the Blue Waters area of the Homosassa River on the west coast of central Florida. Individual frames of videos were loaded onto a computer and lengths of manatees measured using graphics software. All images of manatees were measured independently by three observers. Measurements were transformed to total manatee lengths by calculating the ratio between the measurements of a reference object of known length and the measurement of the manatee. Length estimates were highly variable but were unbiased with respect to observer. Results of an analysis of variance suggested that the hypothesis that lengths differed among days and among observers should not be rejected. Life‐stage structures were represented in three schemes. One scheme‐which included four life stages: dependent calves, juveniles, animals in tramsition between juvenile and adult, and adults‐was included to provide the most information without sacrificing confidence in the life‐stage distribution. Overall, the video system was effective at capturing images of manatees for life‐stage characterization and, with improvements in image resolution, could become a valuable tool for photo‐identification in sight‐resight experiments.

Frontal-Lobe Involvement in Spatial Memory: Evidence from PET, fMRI, and Lesion Studies - Roy P. C. Kessels; Albert Postma; Elze M. Wijnalda; Edward H. F. de Haan (Neuropsychology Review, 2000)

Characteristics of attachment and growth of Thiobacillus caldus on sulphide minerals: a chemotactic response to sulphur minerals? - Katrina J. Edwards; Philip L. Bond; Jillian F. Banfield (Environmental Microbiology, 2000)
To further our understanding of the ecological role of sulphur‐oxidizing microorganisms in the generation of acid mine drainage (AMD), growth and attachment of the chemoautotrophic sulphur‐oxidizing bacterium, Thiobacillus caldus , on the sulphide minerals pyrite, marcasite and arsenopyrite was studied. Growth curves were estimated based on total cells detected in the system (in suspension and attached to mineral surfaces). In general, higher cell numbers were detected on surfaces than in suspension. Fluorescent in situ hybridizations to cells on surfaces at mid‐log growth confirmed that cells on surfaces were metabolically active. Total cell (both surface and solution phase) generation times on pyrite and marcasite (both FeS 2 ) were calculated to be ≈ 7 and 6 h respectively. When grown on pyrite (not marcasite), the number of T. caldus cells in the solution phase decreased, while the total number of cells (both surface and solution) increased. Additionally, marcasite supported about three times more total cells (≈ 3 × 10 9 ) than pyrite (≈ 8 × 10 8 ). This may be attributed to the dissolution rate of marcasite, which is twice that of pyrite. Epifluorescent and scanning electron microscopy (SEM) were used to analyse the cell orientation on surfaces. Results of Fourier transform analysis of fluorescent images confirmed that attachment to all three sulphides occurred in an oriented manner. Results from high‐resolution SEM imaging showed that cell orientation coincides with dissolution pit edges and secondary sulphur minerals that develop during dissolution. Preferential colonization of surfaces relative to solution and oriented cell attachment on these sulphide surfaces suggest that T. caldus may chemotactically select the optimal site for chemoautotrophic growth on sulphur (i.e. the mineral surface).

Geochemistry and tectonic significance of peridotites from the South Sandwich arc-basin system, South Atlantic - J. A. Pearce; P. F. Barker; S. J. Edwards; I. J. Parkinson; P. T. Leat (Contributions to Mineralogy and Petrology, 2000)

Pollen‐based biomes for Beringia 18,000, 6000 and 0 14 C yr bp † - M. E. Edwards; P. M. Anderson; L. B. Brubaker; T. A. Ager; A. A. Andreev; N. H. Bigelow; L. C. Cwynar; W. R. Eisner; S. P. Harrison; F.‐S. Hu; D. Jolly; A. V. Lozhkin; et al. (Journal of Biogeography, 2000)
The objective biomization method developed by Prentice et al . (1996) for Europe was extended using modern pollen samples from Beringia and then applied to fossil pollen data to reconstruct palaeovegetation patterns at 6000 and 18,000 14 C yr bp . The predicted modern distribution of tundra, taiga and cool conifer forests in Alaska and north‐western Canada generally corresponds well to actual vegetation patterns, although sites in regions characterized today by a mosaic of forest and tundra vegetation tend to be preferentially assigned to tundra. Siberian larch forests are delimited less well, probably due to the extreme under‐representation of Larix in pollen spectra. The biome distribution across Beringia at 6000 14 C yr bp was broadly similar to today, with little change in the northern forest limit, except for a possible northward advance in the Mackenzie delta region. The western forest limit in Alaska was probably east of its modern position. At 18,000 14 C yr bp the whole of Beringia was covered by tundra. However, the importance of the various plant functional types varied from site to site, supporting the idea that the vegetation cover was a mosaic of different tundra types.

Original Articles: Nitrogen Availability and Old-Field Succession in a Shortgrass Steppe - Mark W. Paschke; Terry McLendon; Edward F. Redente (Ecosystems, 2000)

Renal effects of cyclooxygenase inhibitors in volume-depleted dogs - David P. Brooks; Jerry Adams; P. Dennis DePalma; Edward F. Webb; Robert H. Palmer; Don E. Griswold (Inflammopharmacology, 2000)

Central and peripheral tissue distribution of diclofenac after subcutaneous injection in the rat - R. F. Grace; S. R. Edwards; L. E. Mather; Y. Lin; I. Power (Inflammopharmacology, 2000)

Induction of resistance in tomato against cucumber mosaic cucumovirus by plant growth-promoting rhizobacteria - Geoffrey W. Zehnder; Changbin Yao; John F. Murphy; Edward R. Sikora; Joseph W. Kloepper (BioControl, 2000)

Partitioning linear trends in age-adjusted rates - Benjamin F. Hankey; Lynn A. Ries; Carol L. Kosary; Eric J. Feuer; Ray M. Merrill; Limin X. Clegg; Brenda K. Edwards (Cancer Causes & Control, 2000)

Abstracts of presentations on selected topics at the XIVth international plant protection congress (IPPC) July 25–30, 1999 - R. Hull; H. A. Kuiper; Maryvon Y. Noordam; Marjorie A. Hoy; Jenny S. Cory; A. C. Fereres; P. Gonzalez; F. Meins; Y. Elkind; Benedicte Charrier; P. Meyer; M. Metzlaff; et al. (Phytoparasitica, 1999)

Novel Tools to Reduce Seabird Bycatch in Coastal Gillnet Fisheries - Edward F. Melvin; Julia K. Parrish; Loveday L. Conquest (Conservation Biology, 1999)
We examined several strategies to reduce seabird bycatch, primarily of Common Murres ( Uria aalge ) and Rhinoceros Auklets ( Cerorhinca monocerata ), in a coastal salmon drift gillnet fishery in Puget Sound, Washington, U.S.A. Our goal was to significantly reduce seabird bycatch without a concomitant reduction in target catch or an increase in the bycatch of any other species. We compared fish catch and seabird bycatch in nets modified to include visual alerts (highly visible netting in the upper net) or acoustic alerts (pingers) to traditional monofilament nets set throughout the normal fishing hours over a 5‐week fishing season. Catch and bycatch varied significantly as a function of gear. Relative to monofilament controls, murres responded to both visual and acoustic alerts; auklets and sockeye salmon responded to deeper visual alerts only. Seabird abundance varied across multiple temporal scales: interannually, within fishing season, and over the day. At the interannual level, seabird entanglement was linked to regional abundance on the fishing grounds, a pattern that broke down at the local level. Within season, sockeye and murre abundance were negatively correlated, suggesting that if fishery openings were scheduled on peak abundance of the target species, seabird bycatch would be significantly reduced as a function of increased target fishing efficiency. Finally, both sockeye catch and auklet entanglement were highest at dawn, whereas murre entanglement was high at both dawn and dusk. Our results identify three complementary tools to reduce seabird bycatch in the Puget Sound drift gillnet fishery—gear modifications, abundance‐based fishery openings, and time‐of‐day restrictions—for a possible reduction in seabird bycatch of up to 70–75% without a significant reduction in target fishing efficiency. Although these tools are based on local conditions and will thus vary among years and locations, all might be exportable to other coastal gillnet fisheries worldwide.

Malate metabolism by NADP-malic enzyme in plant defense - Paula Casati; María F. Drincovich; Gerald E. Edwards; Carlos S. Andreo (Photosynthesis Research, 1999)

Identification and characterization of microsatellite loci in ash ( Fraxinus excelsior L.) and their conservation in the olive family (Oleaceae) - F. Lefort; S. Brachet; N. Frascaria‐Lacoste; K. J. Edwards; G. C. Douglas (Molecular Ecology, 1999)

Abundance and polymorphism of microsatellite markers in the tea tree (Melaleuca alternifolia, Myrtaceae) - M. Rossetto; A. McLauchlan; F. C. L. Harriss; R. J. Henry; P. R. Baverstock; L. S. Lee; T. L. Maguire; K. J. Edwards (Theoretical and Applied Genetics, 1999)

Assessing Trace Element Uptake by Vegetation on a Coal Fly Ash Landfill - Peter B. Woodbury; Gail Rubin; D. C. McCune; Leonard H. Weinstein; Edward F. Neuhauser (Water, Air, & Soil Pollution, 1999)

Finite volume discretization with imposed flux continuity for the general tensor pressure equation - Michael G. Edwards; Clive F. Rogers (Computational Geosciences, 1998)

Relic permafrost structures in the Gobi of Mongolia: age and significance - Lewis A. Owen; Ben Richards; Edward J. Rhodes; W. Dickson Cunningham; Brian F. Windley; J. Badamgarav; D. Dorjnamjaa (Journal of Quaternary Science, 1998)

Effect of environmental temperature on the interactive developmental toxicity of radiofrequency radiation and 2-methoxyethanol in rats - B. K. Nelson; D. L. Conover; E. F. Krieg Jr; D. L. Snyder; R. M. Edwards (International Archives of Occupational and Environmental Health, 1998)

Growth and reproduction of Perionyx excavatus (Perr.) (Megascolecidae) as factors in organic waste management - C. A. Edwards; J. Dominguez; E. F. Neuhauser (Biology and Fertility of Soils, 1998)

Book reviews - Ewa Niewiadomska; Zbigniew Miszalski; Anna M. Rychter; Katarzyna Niemirowicz-Szczytt; W. Filek; F. Dubert; J. Chełkowski; A. Tretyn; J. Maszewski; G. Marszałkowski; Edward A. Gwóźdź (Acta Physiologiae Plantarum, 1998)

Vertical distribution and temporal variation of marine planktonic archaea in the Gerlache Strait, Antarctica, during early spring - Ramon Massana; Lance T. Taylor; Alison E. Murray; Ke Y. Wu; Wade H. Jeffrey; Edward F. DeLong (Limnology and Oceanography, 1998)
A station located in the Gerlache Strait (Antarctic Peninsula) was sampled during early spring to determine the vertical distribution of marine planktonic archaea and to further describe the dynamic environment where they live. Chlorophyll concentration indicated that sampling occurred during the early stages of austral spring algal development. As expected, prokaryote abundance was higher at surface than at depth, and prokaryotic activity estimated by leucine incorporation was low at the surface and extremely low at 500 m. The relative abundance of planktonic archaeal, eucaryal, and bacterial ribosomal RNA was determined by quantitative rRNA hybridization, and the performance of two different universal probes used to normalize group‐specific probe hybridization response was compared. Archaeal rRNA was detected in all samples analyzed, and was more abundant at depth (up to 25% of total rRNA) than at the surface. In both years, the archaeal signal decreased during the sampling period, particularly at surface. Most of the archaeal signal was attributable to group I archaea, affiliated with the kingdom Crenarchaeota. Planktonic euryarchaeotes (group II archaea) showed a larger contribution to the archaeal assemblage in surface waters than at depth. In total, our results verify that planktonic archaea are dynamic and abundant components in marine picoplankton assemblages of the Antarctic Peninsula.

The cartilage collagens: a review of their structure, organization, and role in the pathogenesis of experimental arthritis in animals and in human rheumatic disease - M. A. Cremer; Edward F. Rosloniec; Andrew H. Kang (Journal of Molecular Medicine, 1998)

Effects of climate change on nitrogen dynamics in upland soils. 1. A transplant approach - Philip Ineson; Kenneth Taylor; Anthony F. Harrison; Janet Poskitt; David G. Benham; Edward Tipping; Colin Woof (Global Change Biology, 1998)
The impact of climate change on N leaching from hill land plant/soil systems was investigated using a transplant technique involving the movement of intact lysimeter cores of three contrasting soil types down an altitudinal gradient at Great Dun Fell, Cumbria. Air and soil temperatures and precipitation were monitored at four elevations down an altitudinal transect using automatic weather stations for a period of two years. The altitudinal sequence of air temperature followed the anticipated pattern, providing mean annual temperatures at the four locations of 3.4, 5.0, 6.3 and 8.1 °C. Lapse rates of both mean air and soil temperatures over the altitudinal range 171–845 m were 6.6 (1993) and 7.0 °C km –1 (1994). Soil monthly temperature gradients for a particular soil type for each of the two years showed a seasonal range of 6.0 and 7.4 °C km –1 , respectively, and for air temperature of 4.3 and 3.1 °C km –1 . Precipitation gradients showed the expected general increase with altitude, but were less predictable. Inorganic nitrogen leaching was studied in lysimeter leachates with climatic amelioration resulting in dramatic reductions in leachate nitrate concentrations and associated total concentrations of inorganic nitrogen. Decreases in leachate nitrate concentrations were observed for all three soil types studied. Soils receiving supplemented rainfall also showed decreased N concentrations, suggesting that temperature was the main controlling factor responsible for the observed reductions. Increased N uptake by the vegetation, in response to the increases in temperature, is considered to be critical in controlling soil solution chemistry at these sites.

A study of genetic diversity in Populus nigra subsp. betulifolia in the Upper Severn area of the UK using AFLP markers - M. O. WINFIELD; G. M. ARNOLD; F. COOPER; M. LE RAY; J. WHITE; A. KARP; K.J. EDWARDS (Molecular Ecology, 1998)
A survey of amplified fragment length polymorphism (AFLP) was conducted to examine genetic diversity in 146 individuals of British, native black poplar ( Populus nigra subsp. betulifolia ) and three individuals considered by collectors to be non‐ betulifolia poplars. Using two primer pairs, a total of 147 bands were detected of which 82 (56%) were polymorphic in at least one individual. Cluster analysis and principal coordinates analysis of the calculated similarity matrix revealed a low level of genetic diversity, although a loose clustering into five groups could be identified, one of which contained the non‐ betulifolia individuals. Examination of the spatial distribution of the other four groups (all betulifolia ) revealed a general correlation between geographic proximity and genetic similarity. On the basis of the polymorphism observed, it was possible to identify a small number of individual plants which exhibit maximum diversity and might therefore be suitable for inclusion in a replanting programme designed to maintain at least the existing low level of polymorphism observed within British black poplar.

Withdrawal reactions with selective serotonin re-uptake inhibitors as reported to the WHO system - M. M. S. Stahl; M. Lindquist; M. Pettersson; I. R. Edwards; J. H. Sanderson; N. F. A. Taylor; A. P. Fletcher; J. S. Schou (European Journal of Clinical Pharmacology, 1997)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Minimum sample sizes for identifying chromosomal fragile sites from individuals: Monte Carlo estimation - I. F. Greenbaum; J. K. Fulton; Edward D. White; P. Fred Dahm (Human Genetics, 1997)

Honorary Life Members named at 81st Annual Meeting of The PAA - Allan Parker; Alfred A. Bushway; Edward F. Johnston; Therese M. Work; William H. Bohl (American Journal of Potato Research, 1997)

Disruption of grazer populations as a contributing factor to the initiation of the Texas brown tide algal bloom - Edward J. Buskey; Paul A. Montagna; Anthony F. Amos; Terry E. Whitledge (Limnology and Oceanography, 1997)
Disruption of grazer populations, or mismatches between phytoplankton blooms and population dynamics of their planktonic and benthic grazers, may play an important role in the initiation of some harmful algal blooms. The Laguna Madre of Texas has experienced a persistent, nearly monospecific phytoplankton bloom since January 1990 commonly referred to as the “brown tide.” Whole‐water samples collected in the area where the bloom began reveal the pattern of bloom initiation and dispersion during the first few months of the bloom. Enumeration of microzooplankton from these same samples also reveals that protozoan grazer populations were depressed and nearly eliminated before the bloom began. Benthic biomass and species diversity also declined before the onset of the bloom. The disruption of planktonic and benthic grazers may have been due to extreme hypersaline conditions caused by an extended period of drought (salinities > 60‰). A massive fish kill caused by an abnormal period of below freezing temperatures released a pulse of nutrients into an already disturbed environment allowing this nuisance bloom to become established. Planktonic and benthic grazers have been unable to contribute to the demise of this bloom, which has persisted for >7 yr without interruption.

Atmospheric Effects of the Emerging Mainland Chinese Transportation System at and Beyond the Regional Scale - SCOTT ELLIOTT; MEI SHEN; DONALD R. BLAKE; RONG LU; ARMISTEAD G. RUSSELL; C. Y. J. KAO; GERALD E. STREIT; XUE PENG ZHAO; EDWARD IAIN McCREARY; F. SHERWOOD ROWLAND; MICHAEL J. BROWN; RICHARD P. TURCO (Journal of Atmospheric Chemistry, 1997)

Establishment of serial persistent infections with bovine viral diarrhoea virus in cattle and sheep and changes in epitope expression related to host species - D. Paton; M. Gunn; J. Sands; F. Yappl; T. Drew; S. Vilcek; S. Edwards (Archives of Virology, 1997)

Elevated serum silicon levels in women with silicone gel breast implants - Suzanne S. Teuber; Robert L. Saunders; Georges M. Halpern; Robert F. Brucker; Victor Conte; Brian D. Goldman; Edward E. Winger; W. Graham Wood; M. Eric Gershwin (Biological Trace Element Research, 1995)

Stroke volume measurement during supine and upright cycle exercise by impedance cardiography - Jon K. Moon; Andrew R. Coggan; Mari K. Hopper; Lee E. Baker; Edward F. Coyle (Annals of Biomedical Engineering, 1994)

Induction of hepatic microsomal CYP4A activity and of peroxisomal β-oxidation by two non-steroidal anti-inflammatory drugs - Eleni Rekka; Edward O. Ayalogu; David F. V. Lewis; Gordon G. Gibson; Costas Ioannides (Archives of Toxicology, 1994)

Characterization of a DMSP-degrading bacterial isolate from the Sargasso Sea - Kathleen M. Ledyard; Edward F. DeLong; John W. H. Dacey (Archives of Microbiology, 1993)

Aquatic hazard assessment of the organophosphate insecticide fonofos - James F. Fairchild; Edward E. Little; James N. Huckins (Archives of Environmental Contamination and Toxicology, 1992)

Hypersensitive and enzyme responses in potato tuber tissue treated withVerticillium dahliae and arachidonic acid - Steven F. Vaughn; Edward C. Lulai (American Journal of Potato Research, 1992)

Comparison of fluorescent stains for the detection of suberin in potato periderm - Steven F. Vaughn; Edward C. Lulai (American Journal of Potato Research, 1991)

Vaughn and Lulai: Suberin stains comparison of fluorescent stains for the detection of suberin in potato periderm - Steven F. Vaughn; Edward C. Lulai (American Journal of Potato Research, 1991)

History of The Potato Association of America - Edward F. Johnston (American Journal of Potato Research, 1991)

Regulation of sulfate assimilation in Cytophaga johnsonae - David F. Gilmore; Walter Godchaux; Edward R. Leadbetter (Archives of Microbiology, 1989)

The effects of ochratoxin A on postimplantation rat embryos in culture - K. Mayura; John F. Edwards; Elizabeth A. Maull; Timothy D. Phillips (Archives of Environmental Contamination and Toxicology, 1989)

Genotoxic properties of municipal wastewaters in Ohio - John R. Meier; William F. Blazak; Edward S. Riccio; Barbara E. Stewart; Dolloff F. Bishop; Lyman W. Condie (Archives of Environmental Contamination and Toxicology, 1987)

Phenotype interactions in group behavior of honey bee workers (Apis mellifera L.) - Robin F. A. Moritz; Edward E. Southwick (Behavioral Ecology and Sociobiology, 1987)

Toxicity of five shale oils to fish and aquatic invertebrates - Daniel F. Woodward; Edward E. Little; Lawrence M. Smith (Archives of Environmental Contamination and Toxicology, 1987)

Complement activation by respiratory syncytial virus-infected cells - Kathryn M. Edwards; Paula N. Snyder; P. F. Wright (Archives of Virology, 1986)

Life members announced - Paul J. Eastman; Raymon E. Webb; Edward F. Johnston; Franklin E. Manzer; Edward D. Jones (American Journal of Potato Research, 1984)

The Potato Association of America Treasurer’s report (1983–1984) - Edward F. Johnston (American Journal of Potato Research, 1984)

Evolutionary relationships of superoxide dismutases and glutamine synthetases from marine species of Alteromonas, Oceanospirillum, Pseudomonas and Deleya - Edward F. DeLong; Linda Baumann; Ron D. Bowditch; Paul Baumann (Archives of Microbiology, 1984)

The potato association of America treasurer’s report (1982–1983) - Edward F. Johnston (American Journal of Potato Research, 1983)

Bloodless evaluation of blood oxygenators - Sanjiv S. Shah; Edward F. Leonard (Annals of Biomedical Engineering, 1983)

The Potato Association of America Treasurer’s Report (1981–1982) - Edward F. Johnston (American Journal of Potato Research, 1982)

The Potato Association of America Treasurer’s Report (1979–1980) - Edward F. Johnston (American Journal of Potato Research, 1980)

A determination and estimation of trend in Maine’s fresh potato shipments - Alan S. Kezis; Edward F. Johnston; Peter Baldwin (American Journal of Potato Research, 1980)

Treasurer’s report 1978–1979 - Edward F. Johnston (American Journal of Potato Research, 1979)

Preferred packaging and storage location in relation to quality problems encountered by Northeast fresh potato consumers - Alan S. Kezis; Edward F. Johnston; Robert Faunce (American Journal of Potato Research, 1979)

Treasurer’s report 1977 – 1978 - Edward F. Johnston (American Journal of Potato Research, 1978)

Maine potato farms—Size and number - Edward F. Johnston (American Journal of Potato Research, 1978)

Dislodgeable residues of ethion in Florida citrus and relationships to weather variables - H. N. Nigg; J. C. Allen; R. F. Brooks; G. J. Edwards; N. P. Thompson; Roy W. King; A. H. Blagg (Archives of Environmental Contamination and Toxicology, 1977)

The chronic toxicity of 3-chloro-4-methyl benzamine HCl to birds - Edward W. Schafer; Ronald B. Brunton; Donald J. Cunningham; Norman F. Lockyer (Archives of Environmental Contamination and Toxicology, 1977)

A multiclass, multiresidue analytical method for pesticides in water - John F. Thompson; Stuart J. Reid; Edward J. Kantor (Archives of Environmental Contamination and Toxicology, 1977)

The Potato Association of America Treasurer’s report 1975–1976 - Edward F. Johnston (American Journal of Potato Research, 1976)

The Potato Association of America Treasurer’s report 1974–1975 - Edward F. Johnston (American Journal of Potato Research, 1975)

An intravascular test device for thromboresistant materials: Analysis and preliminary experimental evaluation - Eric F. Grabowski; Anne R. Derby; Robert M. Koffsky; Robert S. Litwak; Edward F. Leonard (Annals of Biomedical Engineering, 1975)

The Potato Association of America Treasurer’s Report 1973–1974 - Edward F. Johnston (American Journal of Potato Research, 1974)

Utilization of endogenous reserves by swimming zoospores of Blastocladiella emersonii - Keller F. Suberkropp; Edward C. Cantino (Archives of Microbiology, 1973)

Primate hemoglobins: Some sequences and some proposals concerning the character of evolution and mutation - Samuel H. Boyer; Emilio F. Crosby; Andrea N. Noyes; Gail F. Fuller; Sanford E. Leslie; Lois J. Donaldson; George R. Vrablik; Edward W. Schaefer; Theodore F. Thurmon (Biochemical Genetics, 1971)

Effect of soil temperatures at harvest on the bruise resistance of potatoes - Edward F. Johnston; J. B. Wilson (American Journal of Potato Research, 1969)

Growth characteristics, interferon production and plaque formation with different lines of Edmonston measles virus - Edward Maeyer; John F. Enders (Archives of Virology, 1965)

Influence of specific compositional factors of potatoes on chipping color - Edward F. Hoover; Paul A. Xander (American Journal of Potato Research, 1963)

Improved handling and packaging methods for potatoes: How it is done in Maine - Edward F. Johnson (American Journal of Potato Research, 1961)

Potato composition and chipping quality - Edward F. Hoover; Paul A. Xander (American Journal of Potato Research, 1961)

s of papers presented at the Forty-Third annual meeting of The Potato Association of America - R. H. Bagnall; D. A. Young; Barrel R. Bienz; G. D. Brill; J. C. Campbell; G. R. Blake; Paul N. Carpenter; George O. Estes; Harold W. Gausman; Harold W. Gausman; Hawkins Arthur; Henning P. Hansen; et al. (American Journal of Potato Research, 1959)

Potato flakes. A new form of dehydrated mashed potatoes - Miles J. Willard; James Cording; R. K. Eskew; P. W. Edwards; John F. Sullivan (American Journal of Potato Research, 1956)

Four newSalmonella serotypes isolated in curacao - P. R. Edwards; F. J. Rutten; Alma C. McWhorter (Antonie van Leeuwenhoek, 1955)